Talc Particles
Patent Information
- Application Number
- JP2023562860
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-15
- Filing Date
- 2022-04-14
- Publication Date
- 2025-04-18
AI Technical Summary
Commercially available talc particles fail to achieve the same level of reinforcing properties as precipitated silica or carbon black in polymer compositions, while increasing viscosity and being costly due to the need for silane coating.
Developing microcrystalline talc particles with specific size and surface area characteristics, produced through dry-milling and classification, to enhance reinforcement in polymer compositions.
The microcrystalline talc particles significantly improve modulus, tensile strength, tear resistance, and reinforcement index of polymer compositions without increasing viscosity, offering a cost-effective alternative to traditional fillers.
Smart Images

Figure 00000078_0000 
Figure 00000078_0001 
Figure 00000078_0002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to talc particles, methods of preparing talc particles, polymer compositions comprising talc particles, methods of making polymer compositions comprising talc particles, and related uses of talc particles in polymer compositions and methods of using talc particles in polymer compositions. [Background technology]
[0002] Polymer compositions are commonly reinforced with filler materials. Elastomeric polymer compositions (such as rubber) are commonly reinforced with filler materials, particularly precipitated silica or carbon black. Such filler materials are used to improve properties such as tensile strength, elongation at break, and tear resistance of the polymer compositions. An important mechanical property of elastomeric polymer compositions is the reinforcement index M, which is the ratio of the tensile modulus at 300% elongation to the tensile modulus at 100% elongation. 300 / M 100 Reinforcing fillers such as precipitated silica and carbon black are 300 / M 100 However, such materials also tend to increase the viscosity of the elastomeric polymer composition, which is undesirable and can be expensive, especially if such materials need to be coated, for example with a silane, before incorporation into the polymer.
[0003] Talc particles have also been developed as reinforcing fillers in polymer compositions, however, commercially available talc particles have so far been unable to achieve the same level of reinforcing properties as precipitated silica or carbon black. Summary of the Invention
[0004] According to a first embodiment, the (e.g., microcrystalline) talc particles have a particle size of about 35 μm. 2 / g or more, and (a) a Sedigraph d 50and (b) a laser-induced d of about 5.0 μm or less. 50 It has one or both of the following. According to a second aspect, a method of preparing (e.g., microcrystalline) talc particles according to the first aspect includes the steps of: (a) dry-milling a (e.g., microcrystalline) talc feed material in an agitator bead mill to produce a ground (e.g., microcrystalline) talc material; and (b) classifying the ground (e.g., microcrystalline) talc material to remove a coarse fraction. According to a third aspect, a polymer composition comprises (eg microcrystalline) talc particles according to the first aspect. According to a fourth aspect, a method of making a polymer composition according to the third aspect comprises combining a polymer or polymer precursor with (eg microcrystalline) talc particles according to the first aspect.
[0005] According to a fifth embodiment, compared to a polymer composition containing the same amount of talc particles not according to the invention, (a) Elastic modulus at 50% elongation of the polymer composition, M 50 To increase; (b) The elastic modulus at 100% elongation of the polymer composition, M 100 To increase; (c) Elastic modulus at 300% elongation of the polymer composition, M 300 To increase; (d) to increase the abrasion resistance of the polymer composition; (e) the reinforcement index M of the polymer composition 300 / M 100 To increase; (f) to increase the tensile strength of the polymer composition; and / or (g) To increase the tear resistance of the polymer composition. There is provided the use of (e.g. microcrystalline) talc particles according to the first aspect in a polymer composition of the present invention.
[0006] According to a sixth aspect, compared to a reference polymer composition comprising a reference amount of talc particles not according to the invention, (a) Elastic modulus at 50% elongation of the polymer composition, M50 Increase; (b) The elastic modulus at 100% elongation of the polymer composition, M 100 Increase; (c) Elastic modulus at 300% elongation of the polymer composition, M 300 Increase; (d) increasing the wear resistance of the polymer composition; (e) the reinforcement index M of the polymer composition 300 / M 100 Increase; (f) increasing the tensile strength of the polymer composition; and / or (g) increasing the tear resistance of a polymer composition There is provided a method comprising adding (eg microcrystalline) talc particles according to the first aspect to a polymer composition in a reference amount. Those skilled in the art will recognize that, unless mutually exclusive, a feature described in connection with any one of the above embodiments may also be applied mutatis mutandis to any other embodiment. Furthermore, unless mutually exclusive, any feature described herein may be applied to any embodiment and / or may be combined with any other feature described herein. Embodiments will now be described, by way of example only, with reference to the drawings, in which: [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic diagram of a grinding / classifying circuit for making talc particles. [Diagram 2] FIG. 1 shows a plot of the crystallinity index (N(TOT) / BET specific surface area) for exemplary talc particles Examples 1 and 2 and reference talc particles T.1, T.2, T.3 and T.4. [Diagram 3] FIG. 13 shows a plot of tensile strength for filled rubber compounds F.7-F.12. [Figure 4] FIG. 13 shows a plot of elongation at break for filled rubber compounds F.7 to F.12. [Diagram 5]FIG. 13 shows a plot of tear resistance for filled rubber compounds F.7-F.12. [Figure 6] FIG. 13 shows a plot of compression set after 22 hours at 70° C. for filled rubber compounds F.7-F.12. [Figure 7] FIG. 1 shows a plot of mass of water adsorption as a function of relative humidity for talc particles A-D. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] It has surprisingly been found that talc particles that combine a relatively high BET specific surface area with a relatively small particle size are particularly effective in reinforcing polymer compositions, such as elastomeric polymer compositions.
[0009] Talc Particles As used herein, the term "talc" refers to the magnesium silicate minerals, or the mineral chlorite (magnesium aluminum silicate), which may be associated with, for example, dolomite, calcite and / or magnesite, or further synthetic talc, also known as talcose, or a mixture of the two. In certain embodiments, the talc is a magnesium silicate mineral or the mineral chlorite, or a mixture thereof. The talc may further comprise dolomite, calcite, or magnesite, or a combination thereof. The total amount of other minerals, such as dolomite, calcite, and / or magnesite in the talc may be less than about 25% by weight based on the total weight of the talc, for example, less than about 20% by weight, or less than about 15% by weight, or less than about 10% by weight, or less than about 5% by weight, or less than about 1% by weight, or less than about 0.75% by weight, or 0.5% by weight or less, based on the total weight of the talc. In certain embodiments, the talc comprises, consists essentially of, or consists of a magnesium silicate mineral. In certain embodiments, the talc is a mixture of magnesium silicate minerals and / or chlorite. Chlorite can be, for example, clinochlore ((Mg,Fe 2+ )5Al(Si3Al)O 10(OH)8). For example, the chlorite may comprise primarily clinochlore. The mass ratio of magnesium silicate mineral to chlorite may be from about 5:1 to about 1:4, e.g., from about 4:1 to about 1:1, or from about 4:1 to about 2:1, or from about 4:1 to about 2.5:1, or from about 4:1 to about 3:1, or from about 2:1, or from about 3:1, or from about 4:1. In certain embodiments, the talc comprises, consists essentially of, or consists of synthetic talc or talcose.
[0010] In one particular embodiment, talc is a hydroxylated magnesium silicate belonging to the family of layered phyllosilicates. Its elemental structure consists of MgO4(OH) octahedral layers (designated "O") sandwiched between six-ring silica tetrahedra SiO2 (designated "T"). This forms a repeating base unit made of TOT layers. These TOT layers are then combined into a c * They stack along their axes to form crystallites with a coherent crystalline structure whose size can be measured.
[0011] BET specific surface area refers to the surface area of a particle of talc particles relative to unit mass, and is determined by the amount of nitrogen adsorbed on the surface of the particle to form a monolayer that completely covers the surface of the particle according to the BET method (measured according to BET method, AFNOR standard X11-621 and 622 or ISO 9277). Details of the BET specific surface area measurement method used in the preparation of this application are shown in the examples.
[0012] Particle size characteristics can be measured in a known manner by sedimenting particulate fillers or materials in fully dispersed conditions in an aqueous medium using a Sedigraph 5100 instrument supplied by Micromeritics Instruments Corporation, Norcross, Georgia, USA (website: www.micromeritics.com), referred to herein as a "Micromeritics Sedigraph 5100 unit." Such an instrument provides a measurement and plot of the cumulative mass percentage of particles having a diameter, referred to in the art as the "equivalent sphere diameter" (esd), less than a given equivalent sphere diameter (esd) value. The mean particle size d 50 That d 50 The particle ESD determined in this manner is the value at which 50% by mass of particles have an equivalent spherical diameter less than this value. 98 , d 90 , d 75 , d 25 and d 10 That d 98 , d 90 , d 75 , d 25 Or d 10 These are the values thus determined of particle esd at which 98%, 90%, 75%, 25% and 10% by weight of the particles are present having equivalent spherical diameters less than this value.
[0013] Particle size characteristics can also be measured by wet Malvern laser scattering (standard ISO 13320-1). In this technique, the size of particles in powders, suspensions and emulsions can be measured using the diffraction of a laser beam, based on the application of Mie theory. Such instruments, for example the Malvern Mastersizer S or Malvern Mastersizer 2000 (supplied by Malvern instruments), provide measurements and plots of the cumulative volume percentage of particles having a diameter less than a given equivalent spherical diameter (esd) value, referred to in the art as the "equivalent spherical diameter" (esd). Mean particle size d 50 That d 50The particle ESD value thus determined is the value at which 50% by volume of particles have an equivalent spherical diameter less than this value. 98 , d 90 , d 75 , d 25 and d 10 That d 98 , d 90 , d 75 , d 25 Or d 10 These are the values thus determined of particle esd at which 98%, 90%, 75%, 25% and 10% by volume of particles are present having equivalent spherical diameters less than this value, respectively. For the avoidance of doubt, measurement of particle size using laser light scattering is not an equivalent method to the sedimentation method referred to above. Details of the Sedigraph and laser particle size measurement techniques used in the preparation of this application are given in the Examples. Particle size characteristics can also be measured by sieve analysis, as is well known in the art, for example using an electromagnetic vibratory sieve shaker. A suitable electromagnetic vibratory sieve shaker is D0407.2 available from Controlab, France.
[0014] The talc particles are preferably microcrystalline talc (i.e., not macrocrystalline talc). The crystal structure of the talc (e.g., whether the talc is microcrystalline or macrocrystalline) can be characterized in terms of the number of TOT layers in the talc particles and the talc particle size and / or surface area. The number of TOT layers of a talc particle can be determined by X-ray diffraction (XRD) and applying the Scherrer equation to the (002) and (006) peaks of the pattern.
[0015] For example, XRD patterns can be acquired using a PAnalytical X'PRO X-ray diffractometer using CuKα radiation with a wavelength of λ=1.5406 Å. Samples are acquired by packing an aluminum holder to obtain a quasi-random orientation. Example acquisition parameters can be 2θ range=8-80° with a step size of 0.01° and step duration of 2 seconds. The Scherrer equation is then applied to the (002) and (006) peaks of the talc pattern, which are located approximately at 2θ=9.3-9.7° and 2θ=28.3-28.9° on the XRD pattern. This equation gives c * The width of the peak at half height relative to the background line is used to calculate the coherent scattering domain of the talc crystal along the axis. The number of TOT layers in a single talc crystallite can then be estimated. This method is implemented in a paper on synthetic talc (Dumas et al., Angewandte Chemie International Edition 2016, 55, 9868-9871), the contents of which are incorporated herein by reference. The Scherrer formula is expressed as follows:
[0016]
number
[0017]
number
number
[0018]
number
[0019] Talc particles (e.g., microcrystalline talc particles) have a diameter of about 35 m 2 / g or more, for example, about 36m 2 / g or more, or about 37m 2 / g or more, or about 38m 2 / g or more, or about 39m 2 / g or more, or about 40m 2 / g or more, or about 41m 2 / g or more, or about 42m 2 / g or more, or about 43m 2 / g or more, or about 44m 2 / g or more, or about 45m 2 / g or more, or about 46m 2 / g or more, or about 47m 2 / g or more, or about 48m2 The talc particles (e.g., microcrystalline talc particles) may have a BET specific surface area of about 150 m 2 / g or less, for example, about 100m 2 / g or less, or about 80m 2 / g or less, or about 60m 2 / g or less, or about 50m 2 / g or less, or about 49m 2 / g or less, or about 45m 2 / g or less, or about 44m 2 / g or less, or about 43m 2 The talc particles (e.g., microcrystalline talc particles) may have a BET specific surface area of about 35 m 2 / g~about 150m 2 / g, for example, about 36m 2 / g~about 150m 2 / g, or about 37m 2 / g~about 150m 2 / g, or about 38m 2 / g~about 150m 2 / g, or about 39m 2 / g~about 150m 2 / g, or about 40m 2 / g~about 150m 2 / g, or about 41m 2 / g~about 150m 2 / g, or about 42m 2 / g~about 150m 2 / g, or about 43m 2 / g~about 150m 2 / g, or about 44m 2 / g~about 150m 2 / g, or about 45m 2 / g~about 150m 2 / g, or about 46m 2 / g~about 150m 2 / g, or about 47m 2 / g~about 150m 2 / g, or about 48m 2 / g~about 150m 2 / g, or about 35m 2 / g~about 100m 2 / g, or about 36m 2 / g~about 100m 2 / g, or about 37m2 / g~about 100m 2 / g, or about 38m 2 / g~about 100m 2 / g, or about 39m 2 / g~about 100m 2 / g, or about 40m 2 / g~about 100m 2 / g, or about 41m 2 / g~about 100m 2 / g, or about 42m 2 / g~about 100m 2 / g, or about 43m 2 / g~about 100m 2 / g, or about 44m 2 / g~about 100m 2 / g, or about 45m 2 / g~about 100m 2 / g, or about 46m 2 / g~about 100m 2 / g, or about 47m 2 / g~about 100m 2 / g, or about 48m 2 / g~about 100m 2 / g, or about 35m 2 / g~about 80m 2 / g, or about 36m 2 / g~about 80m 2 / g, or about 37m 2 / g~about 80m 2 / g, or about 38m 2 / g~about 80m 2 / g, or about 39m 2 / g~about 80m 2 / g, or about 40m 2 / g~about 80m 2 / g, or about 41m 2 / g~about 80m 2 / g, or about 42m 2 / g~about 80m 2 / g, or about 43m 2 / g~about 80m 2 / g, or about 44m 2 / g~about 80m 2 / g, or about 45m 2 / g~about 80m 2 / g, or about 46m 2 / g~about 80m2 / g, or about 47m 2 / g~about 150m 2 / g, or about 48m 2 / g~about 80m 2 / g, or about 35m 2 / g~about 60m 2 / g, or about 36m 2 / g~about 60m 2 / g, or about 37m 2 / g~about 60m 2 / g, or about 38m 2 / g~about 60m 2 / g, or about 39m 2 / g~about 60m 2 / g, or about 40m 2 / g~about 60m 2 / g, or about 41m 2 / g~about 60m 2 / g, or about 42m 2 / g~about 60m 2 / g, or about 43m 2 / g~about 60m 2 / g, or about 44m 2 / g~about 60m 2 / g, or about 45m 2 / g~about 60m 2 / g, or about 46m 2 / g~about 60m 2 / g, or about 47m 2 / g~about 60m 2 / g, or about 48m 2 / g~about 60m 2 / g, or about 35m 2 / g~about 50m 2 / g, or about 36m 2 / g~about 50m 2 / g, or about 37m 2 / g~about 50m 2 / g, or about 38m 2 / g~about 50m 2 / g, or about 39m 2 / g~about 50m 2 / g, or about 40m 2 / g~about 50m 2 / g, or about 41m 2 / g~about 50m 2 / g, or about 42m 2 / g~about 50m 2 / g, or about 43m 2 / g~about 50m 2 / g, or about 44m 2 / g~about 50m 2 / g, or about 45m 2 / g~about 50m 2 / g, or about 46m 2 / g~about 50m 2 / g, or about 47m 2 / g~about 50m 2 / g, or about 48m 2 / g~about 50m 2 / g, or about 35m 2 / g~approx. 49m 2 / g, or about 36m 2 / g~approx. 49m 2 / g, or about 37m 2 / g~approx. 49m 2 / g, or about 38m 2 / g~approx. 49m 2 / g, or about 39m 2 / g~approx. 49m 2 / g, or about 40m 2 / g~approx. 49m 2 / g, or about 41m 2 / g~approx. 49m 2 / g, or about 42m 2 / g~approx. 49m 2 / g, or about 43m 2 / g~approx. 49m 2 / g, or about 44m 2 / g~approx. 49m 2 / g, or about 45m 2 / g~approx. 49m 2 / g, or about 46m 2 / g~approx. 49m 2 / g, or about 47m 2 / g~approx. 49m 2 / g, or about 48m 2 / g~approx. 49m 2 / g, or about 35m 2 / g ~ approx. 45m 2 / g, or about 36m 2 / g ~ approx. 45m 2 / g, or about 37m 2 / g ~ approx. 45m 2 / g, or about 38m2 / g ~ approx. 45m 2 / g, or about 39m 2 / g ~ approx. 45m 2 / g, or about 40m 2 / g ~ approx. 45m 2 / g, or about 41m 2 / g ~ approx. 45m 2 / g, or about 42m 2 / g ~ approx. 45m 2 / g, or about 43m 2 / g ~ approx. 45m 2 / g, or about 44m 2 / g ~ approx. 45m 2 / g, or about 35m 2 / g ~ approx. 44m 2 / g, or about 36m 2 / g ~ approx. 44m 2 / g, or about 37m 2 / g ~ approx. 44m 2 / g, or about 38m 2 / g ~ approx. 44m 2 / g, or about 39m 2 / g ~ approx. 44m 2 / g, or about 40m 2 / g ~ approx. 44m 2 / g, or about 41m 2 / g ~ approx. 44m 2 / g, or about 42m 2 / g ~ approx. 44m 2 / g, or about 43m 2 / g ~ approx. 44m 2 / g, or about 35m 2 / g ~ approx. 43m 2 / g, or about 36m 2 / g ~ approx. 43m 2 / g, or about 37m 2 / g ~ approx. 43m 2 / g, or about 38m 2 / g ~ approx. 43m 2 / g, or about 39m 2 / g ~ approx. 43m 2 / g, or about 40m 2 / g ~ approx. 43m 2 / g, or about 41m 2 / g ~ approx. 43m 2 / g.
[0020] Talc particles (e.g., microcrystalline talc particles) have a diameter, as measured by Sedigraph, of about 2.0 μm or less, e.g., about 1.5 μm or less, or about 1.0 μm or less, or about 0.9 μm or less, or about 0.8 μm or less, or about 0.7 μm or less, or about 0.6 μm or less, or about 0.5 μm or less. 50 The talc particles (e.g., microcrystalline talc particles) may have a Sedigraph d of about 0.1 μm or more, e.g., about 0.3 μm or more, or about 0.4 μm or more, or about 0.5 μm or more. 50 The talc particles (e.g., microcrystalline talc particles) may have a diameter of about 0.1 μm to about 2.0 μm, for example, about 0.1 μm to about 1.5 μm, or about 0.1 μm to about 1.0 μm, or about 0.1 μm to about 0.9 μm, or about 0.1 μm to about 0.8 μm, or about 0.1 μm to about 0.7 μm, or about 0.1 μm to about 0.6 μm, or about 0.1 μm to about 0.5 μm, or about 0.3 μm to about 2.0 μm, or about 0.3 μm to about 1.5 μm, or about 0.3 μm to about 1.0 μm, or about 0.3 μm to about 0.9 μm, or about 0.3 μm to about 0.8 μm, or about 0.3 μm to about 0.7 μm, or about 0.3 μm to about 0. 6 μm, or about 0.3 μm to about 0.5 μm, or about 0.4 μm to about 2.0 μm, or about 0.4 μm to about 1.5 μm, or about 0.4 μm to about 1.0 μm, or about 0.4 μm to about 0.9 μm, or about 0.4 μm to about 0.8 μm, or about 0.4 μm to about 0.7 μm, or about 0.4 μm to about 0.6 μm, or about 0.4 μm to about 0.5 μm, or about 0.5 μm to about 2.0 μm, or about 0.5 μm to about 1.5 μm, or about 0.5 μm to about 1.0 μm, or about 0.5 μm to about 0.9 μm, or about 0.5 μm to about 0.8 μm, or about 0.5 μm to about 0.7 μm, 50 may have:
[0021] Talc particles (e.g., microcrystalline talc particles) can be laser dipped to about 5.0 μm or less, e.g., about 4.0 μm or less, or about 3.0 μm or less, or about 2.9 μm or less, or about 2.8 μm or less, or about 2.7 μm or less, or about 2.6 μm or less, or about 2.5 μm or less, or about 2.4 μm or less. 50The talc particles (e.g., microcrystalline talc particles) can have a laser d of about 1.0 μm or more, e.g., about 1.5 μm or more, or about 2.0 μm or more, or about 2.4 μm or more. 50 The talc particles (e.g., microcrystalline talc particles) may have a particle size of about 1.0 μm to about 5.0 μm, for example, about 1.0 μm to about 4.0 μm, or about 1.0 μm to about 3.0 μm, or about 1.0 μm to about 2.9 μm, or about 1.0 μm to about 2.8 μm, or about 1.0 μm to about 2.7 μm, or about 1.0 μm to about 2.6 μm, or about 1.0 μm to about 2.6 μm. about 2.5 μm, or about 1.0 μm to about 2.4 μm, or about 1.5 μm to about 5.0 μm, or about 1.5 μm to about 4.0 μm, or about 1.5 μm to about 3.0 μm, or about 1.5 μm to about 2.9 μm, or about 1.5 μm to about 2.8 μm, or about 1.5 μm to about 2.7 μm, or about 1.5 μm to about 2.6 μm, or about 1.5 μm to about 2.5 μm, or about 1.5 μm to about 2.4 μm, or about 2.0 μm to about 5.0 μm, or about 2.0 μm to about 4.0 μm, or about 2.0 μm to about 3.0 μm, or about 2.0 μm to about 2.9 μm, or about 2.0 μm to about 2.8 μm, or about 2.0 μm to about 2.7 μm, or about 2.0 μm to about 2.6 μm, or about 2.0 μm to about 2.5 μm, or about 2.0 μm to about 2.4 μm, or about 2.4 μm to about 5.0 μm, or about 2.4 μm to about 4.0 μm, or about 2.4 μm to about 3.0 μm, or about 2.4 μm to about 2.9 μm, or about 2.4 μm to about 2.8 μm, or about 2.4 μm to about 2.7 μm, or about 2.4 μm to about 2.6 μm 50 may have:
[0022] Talc particles (e.g., microcrystalline talc particles) can be laser-deposited to have a diameter of about 10.0 μm or less, e.g., about 7.0 μm or less, or about 6.0 μm or less, or about 5.0 μm or less. 95 The talc particles (e.g., microcrystalline talc particles) may have a laser d of about 3.0 μm or more, e.g., about 4.0 μm or more, or about 5 μm or more. 95The talc particles (e.g., microcrystalline talc particles) may have a diameter of about 3.0 μm to about 10.0 μm, for example, about 3.0 μm to about 7.0 μm, or about 3.0 μm to about 6.0 μm, or about 3.0 μm to about 5.0 μm, or about 4.0 μm to about 10.0 μm, or about 4.0 μm to about 7.0 μm, or about 4.0 μm to about 6.0 μm, or about 4.0 μm to about 5.0 μm, or about 5.0 μm to about 10.0 μm, or about 5.0 μm to about 7.0 μm, or about 5.0 μm to about 6.0 μm. 95 may have:
[0023] Talc particles (e.g., microcrystalline talc particles) can be laser-deposited to a diameter of about 7.0 μm or less, e.g., about 5.0 μm or less, or about 4.0 μm or less. 75 The talc particles (e.g., microcrystalline talc particles) may have a laser d of about 2.0 μm or more, e.g., about 3.0 μm or more. 75 The talc particles (e.g., microcrystalline talc particles) may have a laser d of about 2.0 μm to about 7.0 μm, for example, about 2.0 μm to about 5.0 μm, or about 2.0 μm to about 4.0 μm, or about 3.0 μm to about 7.0 μm, or about 3.0 μm to about 5.0 μm, or about 3.0 μm to about 4.0 μm. 75 may have:
[0024] Talc particles (e.g., microcrystalline talc particles) can be laser-deposited to a diameter of about 3.0 μm or less, e.g., about 2.0 μm or less, or about 1.9 μm or less, or about 1.8 μm or less. 25 The talc particles (e.g., microcrystalline talc particles) can have a laser d of about 0.5 μm or more, e.g., about 1.0 μm or more, or about 1.5 μm or more, or about 1.7 μm or more. 25The talc particles (e.g., microcrystalline talc particles) may have a diameter of about 0.5 μm to about 3.0 μm, for example, about 0.5 μm to about 2.0 μm, or about 0.5 μm to about 1.9 μm, or about 0.5 μm to about 1.8 μm, or about 1.0 μm to about 3.0 μm, or about 1.0 μm to about 2.0 μm, or about 1.0 μm to about 1.9 μm, or about 1.0 μm to about 3.0 μm. about 1.8 μm, or about 1.5 μm to about 3.0 μm, or about 1.5 μm to about 2.0 μm, or about 1.5 μm to about 1.9 μm, or about 1.5 μm to about 1.8 μm, or about 1.7 μm to about 3.0 μm, or about 1.7 μm to about 2.0 μm, or about 1.7 μm to about 1.9 μm, or about 1.7 μm to about 1.8 μm 25 may have:
[0025] Talc particles (e.g., microcrystalline talc particles) have a diameter, as measured by Sedigraph, of about 5.0 μm or less, e.g., about 4.0 μm or less, or about 3.0 μm or less, or about 2.5 μm or less, or about 2.0 μm or less. 95 The talc particles (e.g., microcrystalline talc particles) may have a d by Sedigraph of about 0.5 μm or more, e.g., about 1.0 μm or more, or about 1.4 μm or more, or about 1.7 μm or more. 95 The talc particles (e.g., microcrystalline talc particles) may have a diameter of about 0.5 μm to about 5.0 μm, for example, about 0.5 μm to about 4.0 μm, or about 0.5 μm to about 3.0 μm, or about 0.5 μm to about 2.5 μm, or about 0.5 μm to about 2.0 μm, or about 1.0 μm to about 5.0 μm, or about 1.0 μm to about 4.0 μm, or about 1.0 μm to about 3.0 μm, or about 1.0 μm to about 2.5 μm, or about 1.0 μm to about 2. 0 μm, or about 1.4 μm to about 5.0 μm, or about 1.4 μm to about 4.0 μm, or about 1.4 μm to about 3.0 μm, or about 1.4 μm to about 2.5 μm, or about 1.4 μm to about 2.0 μm, or about 1.7 μm to about 5.0 μm, or about 1.7 μm to about 4.0 μm, or about 1.7 μm to about 3.0 μm, or about 1.7 μm to about 2.5 μm, or about 1.7 μm to about 2.0 μm, as measured by Sedigraph 95 may have:
[0026] Talc particles (e.g., microcrystalline talc particles) have a diameter, as measured by Sedigraph, of about 3.0 μm or less, e.g., about 2.0 μm or less, or about 1.5 μm or less, or about 1.1 μm or less, or about 1.0 μm or less. 75 The talc particles (e.g., microcrystalline talc particles) may have a d by Sedigraph of about 0.1 μm or more, e.g., about 0.5 μm or more, or about 0.8 μm or more, or about 1.0 μm or more. 75 The talc particles (e.g., microcrystalline talc particles) may have a diameter of about 0.1 μm to about 3.0 μm, for example, about 0.1 μm to about 2.0 μm, or about 0.1 μm to about 1.5 μm, or about 0.1 μm to about 1.1 μm, or about 0.1 μm to about 1.0 μm, or about 0.5 μm to about 3.0 μm, or about 0.5 μm to about 2.0 μm, or about 0.5 μm to about 1.5 μm, or about 0.5 μm to about 1.1 μm, or about 0. 0.5 μm to about 1.0 μm, or about 0.8 μm to about 3.0 μm, or about 0.8 μm to about 2.0 μm, or about 0.8 μm to about 1.5 μm, or about 0.8 μm to about 1.1 μm, or about 0.8 μm to about 1.0 μm, or about 1.0 μm to about 3.0 μm, or about 1.0 μm to about 2.0 μm, or about 1.0 μm to about 1.5 μm, or about 1.0 μm to about 1.1 μm, as measured by Sedigraph 75 may have:
[0027] Talc particles (e.g., microcrystalline talc particles) have a diameter, as measured by Sedigraph, of about 1.0 μm or less, e.g., about 0.5 μm or less, or about 0.4 μm or less, or about 0.3 μm or less. 25 The talc particles (e.g., microcrystalline talc particles) may have a d by Sedigraph of about 0.1 μm or more, e.g., about 0.3 μm or more, or about 0.4 μm or more. 25 The talc particles (e.g., microcrystalline talc particles) may have a diameter, as measured by Sedigraph, of about 0.1 μm to about 1.0 μm, for example, about 0.1 μm to about 0.5 μm, or about 0.1 μm to about 0.4 μm, or about 0.1 μm to about 0.3 μm, or about 0.3 μm to about 1.0 μm, or about 0.3 μm to about 0.5 μm, or about 0.3 μm to about 0.4 μm, or about 0.4 μm to about 1.0 μm, or about 0.4 μm to about 0.5 μm. 25 may have:
[0028] Talc particles (e.g., microcrystalline talc particles) have a diameter of about 35 m 2 / g or more, and (a) a Sedigraph d 50 and (b) a laser-induced d of about 5.0 μm or less. 50 It may have one or both of the following: Talc particles (e.g., microcrystalline talc particles) have a diameter of about 35 m 2 / g or more, and (a) a Sedigraph d 50 (b) Laser-induced d of about 5.0 μm or less 50 and (c) about 7.5 g / m 2 For example, about 0.01 g / m or less 2 ~about 7.5g / m 2 , or about 0.01 g / m 2 ~about 4.0g / m 2 The CI may include one or more of the above CIs. Talc particles (e.g., microcrystalline talc particles) have a diameter of about 35 m 2 / g or more, and (a) a dSr of about 1.5 μm or less, for example, about 1.0 μm or less, or about 0.1 μm to about 2.0 μm, for example, about 0.1 μm to about 1.5 μm, or about 0.1 μm to about 1.0 μm, by Sedigraph. 50 and (b) a laser d of about 4.0 μm or less, e.g., about 3.0 μm or less, or about 1.0 μm to about 5.0 μm, e.g., about 1.0 μm to about 4.0 μm, or about 1.0 μm to about 3.0 μm. 50 It may have one or both of the following:
[0029] Talc particles (e.g., microcrystalline talc particles) have a diameter of about 35 m 2 / g or more, and (a) a dSr of about 1.5 μm or less, for example, about 1.0 μm or less, or about 0.1 μm to about 2.0 μm, for example, about 0.1 μm to about 1.5 μm, or about 0.1 μm to about 1.0 μm, by Sedigraph. 50(b) a laser d of about 4.0 μm or less, e.g., about 3.0 μm or less, or about 1.0 μm to about 5.0 μm, e.g., about 1.0 μm to about 4.0 μm, or about 1.0 μm to about 3.0 μm; 50 and (c) about 7.5 g / m 2 For example, about 0.01 g / m or less 2 ~about 7.5g / m 2 , or about 0.01 g / m 2 ~about 4.0g / m 2 The CI may include one or more of the above CIs. Talc particles (e.g., microcrystalline talc particles) have a diameter of about 40 m 2 / g or more, and (a) a dSr of about 1.5 μm or less, for example, about 1.0 μm or less, or about 0.1 μm to about 2.0 μm, for example, about 0.1 μm to about 1.5 μm, or about 0.1 μm to about 1.0 μm, by Sedigraph. 50 and (b) a laser d of about 4.0 μm or less, e.g., about 3.0 μm or less, or about 1.0 μm to about 5.0 μm, e.g., about 1.0 μm to about 4.0 μm, or about 1.0 μm to about 3.0 μm. 50 It may have one or both of the following:
[0030] Talc particles (e.g., microcrystalline talc particles) have a diameter of about 40 m 2 / g or more, and (a) a dSr of about 1.5 μm or less, for example, about 1.0 μm or less, or about 0.1 μm to about 2.0 μm, for example, about 0.1 μm to about 1.5 μm, or about 0.1 μm to about 1.0 μm, by Sedigraph. 50 (b) a laser d of about 4.0 μm or less, e.g., about 3.0 μm or less, or about 1.0 μm to about 5.0 μm, e.g., about 1.0 μm to about 4.0 μm, or about 1.0 μm to about 3.0 μm; 50 and (c) about 7.5 g / m 2 For example, about 0.01 g / m or less 2 ~about 7.5g / m 2 , or about 0.01 g / m 2 ~about 4.0g / m 2 The CI may be one or both of the above.
[0031] Talc particles (e.g., microcrystalline talc particles) are (A) about 35 m 2 / g or more, for example, about 40m 2 (B) (a) a BET specific surface area of about 1.5 μm or less, for example, about 1.0 μm or less, or about 0.1 μm to about 2.0 μm, for example, about 0.1 μm to about 1.5 μm, or about 0.1 μm to about 1.0 μm, measured by Sedigraph; 50 and (b) a laser d of about 4.0 μm or less, e.g., about 3.0 μm or less, or about 1.0 μm to about 5.0 μm, e.g., about 1.0 μm to about 4.0 μm, or about 1.0 μm to about 3.0 μm. 50 and (C) (a) a laser-induced d 95 (b) about 7.0 μm or less, for example, about 5.0 μm or less, or about 2.0 μm to about 7.0 μm, or about 2.0 μm to about 5.0 μm, 75 (c) about 3.0 μm or less, for example, about 2.0 μm or less, or about 0.5 μm to about 3.0 μm, or about 0.5 μm to about 2.0 μm, 25 (d) about 5.0 μm or less, for example, about 3.0 μm or less, or about 0.5 μm to about 5.0 μm, or about 0.5 μm to about 3.0 μm, according to Sedigraph 95 (e) about 3.0 μm or less, for example, about 2.0 μm or less, or about 0.1 μm to about 3.0 μm, or about 0.1 μm to about 2.0 μm, as measured by Sedigraph 75 and (f) a Sedigraph d of about 1.0 μm or less, e.g., about 0.5 μm or less, or about 0.1 μm to about 1.0 μm, or about 0.1 μm to about 0.5 μm. 25 The present invention may have one or more of the following:
[0032] Talc particles (e.g., microcrystalline talc particles) are (A) about 35 m 2 / g or more, for example, about 40m 2(B) (a) a BET specific surface area of about 1.5 μm or less, for example, about 1.0 μm or less, or about 0.1 μm to about 2.0 μm, for example, about 0.1 μm to about 1.5 μm, or about 0.1 μm to about 1.0 μm, measured by Sedigraph; 50 and (b) a laser d of about 4.0 μm or less, e.g., about 3.0 μm or less, or about 1.0 μm to about 5.0 μm, e.g., about 1.0 μm to about 4.0 μm, or about 1.0 μm to about 3.0 μm. 50 (C) (a) a laser-induced d 95 (b) about 7.0 μm or less, for example, about 5.0 μm or less, or about 2.0 μm to about 7.0 μm, or about 2.0 μm to about 5.0 μm, 75 (c) about 3.0 μm or less, for example, about 2.0 μm or less, or about 0.5 μm to about 3.0 μm, or about 0.5 μm to about 2.0 μm, 25 (d) about 5.0 μm or less, for example, about 3.0 μm or less, or about 0.5 μm to about 5.0 μm, or about 0.5 μm to about 3.0 μm, according to Sedigraph 95 (e) about 3.0 μm or less, for example, about 2.0 μm or less, or about 0.1 μm to about 3.0 μm, or about 0.1 μm to about 2.0 μm, as measured by Sedigraph 75 and (f) a Sedigraph d of about 1.0 μm or less, e.g., about 0.5 μm or less, or about 0.1 μm to about 1.0 μm, or about 0.1 μm to about 0.5 μm. 25 and (D) about 7.5 g / m 2 For example, about 0.01 g / m or less 2 ~about 7.5g / m 2 , or about 0.01 g / m 2 ~about 4.0g / m 2 The CI may be:
[0033] Talc particles (e.g., microcrystalline talc particles) have a diameter of about 40 m 2 / g ~ approx. 45m 2 / g BET specific surface area: approx. 1.5 μm to approx. 2.0 μm, measured by Sedigraph 95 and / or about 4.5 μm to about 5.2 μm, laser d 95 ; Approximately 0.8μm to approximately 1.2μm, Sedigraph 75 and / or about 3.0 μm to about 3.4 μm, laser d 75 ; Approximately 0.4μm to approximately 0.8μm, Sedigraph 50 and / or about 2.2 μm to about 2.6 μm, laser d 50 ; and about 0.1 μm to about 0.5 μm, measured by Sedigraph 25 and / or about 1.6 μm to about 2.0 μm, laser d 25 may have:
[0034] Talc particles (e.g., microcrystalline talc particles) have a diameter of about 40 m 2 / g ~ approx. 45m 2 / g BET specific surface area: approx. 1.5 μm to approx. 2.0 μm, measured by Sedigraph 95 and / or about 4.5 μm to about 5.2 μm, laser d 95 ; Approximately 0.8μm to approximately 1.2μm, Sedigraph 75 and / or about 3.0 μm to about 3.4 μm, laser d 75 ; Approximately 0.4μm to approximately 0.8μm, Sedigraph 50 and / or about 2.2 μm to about 2.6 μm, laser d 50 ; Approximately 0.1μm to approximately 0.5μm, measured by Sedigraph 25 and / or about 1.6 μm to about 2.0 μm, laser d 25 ; and approximately 7.5 g / m 2 For example, about 0.01 g / m or less 2 ~about 7.5g / m 2 , or about 0.01 g / m 2 ~about 4.0g / m 2 The CI may be:
[0035] Talc particles (e.g., microcrystalline talc particles) have a diameter of about 45 m 2 / g~about 50m 2 / g BET specific surface area; d by Sedigraph of about 1.2 μm to about 1.6 μm 95 and / or about 6.0 μm to about 6.5 μm, laser d 95 ; Approximately 0.5μm to approximately 1.0μm, Sedigraph 75 and / or about 3.5 μm to about 4.0 μm, laser d 75 ; Approximately 0.3μm to approximately 0.7μm, Sedigraph 50 and / or about 2.3 μm to about 2.7 μm, laser d 50 ; and about 0.1 μm to about 0.5 μm, measured by Sedigraph 25 and / or about 1.5 μm to about 2.0 μm, laser d 25 may have: Talc particles (e.g., microcrystalline talc particles) have a diameter of about 45 m 2 / g~about 50m 2 / g BET specific surface area; d by Sedigraph of about 1.2 μm to about 1.6 μm 95 and / or about 6.0 μm to about 6.5 μm, laser d 95 ; Approximately 0.5μm to approximately 1.0μm, Sedigraph 75 and / or about 3.5 μm to about 4.0 μm, laser d 75 ; Approximately 0.3μm to approximately 0.7μm, Sedigraph 50 and / or about 2.3 μm to about 2.7 μm, laser d 50 ; Approximately 0.1μm to approximately 0.5μm, measured by Sedigraph 25 and / or about 1.5 μm to about 2.0 μm, laser d 25 ; and approximately 7.5 g / m 2 For example, about 0.01 g / m or less 2 ~about 7.5g / m 2 , or about 0.01 g / m 2 ~about 4.0g / m 2 The CI may be:
[0036] Talc particles (e.g., microcrystalline talc particles) have a diameter of about 38 m 2 / g ~ approx. 44m2 / g BET specific surface area: approx. 1.8 μm to approx. 2.2 μm, measured by Sedigraph 95 and / or about 5.0 μm to about 5.8 μm, laser d 95 ; Approximately 0.8μm to approximately 1.5μm, Sedigraph 75 and / or about 3.2 μm to about 3.8 μm, laser d 75 ; Approximately 0.5μm to approximately 1.0μm, Sedigraph 50 and / or about 2.1 μm to about 2.7 μm, laser d 50 ; and about 0.2 μm to about 0.7 μm, measured by Sedigraph 25 and / or about 1.5 μm to about 2.0 μm, laser d 25 may have: Talc particles (e.g., microcrystalline talc particles) have a diameter of about 38 m 2 / g ~ approx. 44m 2 / g BET specific surface area: approx. 1.8 μm to approx. 2.2 μm, measured by Sedigraph 95 and / or about 5.0 μm to about 5.8 μm, laser d 95 ; Approximately 0.8μm to approximately 1.5μm, Sedigraph 75 and / or about 3.2 μm to about 3.8 μm, laser d 75 ; Approximately 0.5μm to approximately 1.0μm, Sedigraph 50 and / or about 2.1 μm to about 2.7 μm, laser d 50 ; Approximately 0.2μm to approximately 0.7μm, Sedigraph 25 and / or about 1.5 μm to about 2.0 μm, laser d 25 ; and approximately 7.5 g / m 2 For example, about 0.01 g / m or less 2 ~about 7.5g / m 2 , or about 0.01 g / m 2 ~about 4.0g / m 2 The CI may be:
[0037] Talc particles (e.g., microcrystalline talc particles) have a density of about 0.75 mg / m 2 or more, for example, about 0.8 mg / m2 or more than about 0.9 mg / m 2 or more than 1.0 mg / m 2 Talc particles (e.g., microcrystalline talc particles) may have a water adsorption at 50% relative humidity of about 2.5 mg / m 2 For example, about 2.0 mg / m 2 Less than or equal to about 1.5 mg / m 2 or less than about 1.25 mg / m 2 Talc particles (e.g., microcrystalline talc particles) may have a water adsorption at 50% relative humidity of about 0.75 mg / m 2 ~about 2.5mg / m 2 , for example, about 0.75 mg / m 2 ~about 2.0mg / m 2 , or about 0.75 mg / m 2 ~about 1.5mg / m 2 , or about 0.75 mg / m 2 ~about 1.25mg / m 2 , or about 0.8 mg / m 2 ~about 2.5mg / m 2 , or about 0.8 mg / m 2 ~about 2.0mg / m 2 , or about 0.9 mg / m 2 ~about 1.5mg / m 2 , or about 0.9 mg / m 2 ~about 1.25mg / m 2 , or about 0.9 mg / m 2 ~about 2.5mg / m 2 , or about 0.9 mg / m 2 ~about 2.0mg / m 2 , or about 0.9 mg / m 2 ~about 1.5mg / m 2 , or about 0.9 mg / m 2 ~about 1.25mg / m 2 , or about 1.0 mg / m 2 ~about 2.5mg / m 2 , or about 1.0 mg / m 2 ~about 2.0mg / m 2 , or about 1.0 mg / m 2 ~about 1.5mg / m 2 , or about 1.0 mg / m 2 ~about 1.25mg / m 2of water adsorption at 50% relative humidity.
[0038] The talc particles (e.g., microcrystalline talc particles) can have a Minolta Y whiteness of about 90 or greater, e.g., about 92 or greater, or about 93 or greater, or about 94 or greater. Minolta Y whiteness can be measured using a spectrophotometer / colorimeter such as a Konica Minolta CM-3700d (available from Konica Minolta Sensing Europe BV) using a D65 illuminant and the color space CIE LAB (1976). The talc particles (e.g., microcrystalline talc particles) have a CIELAB L of about 95 or greater, e.g., about 97 or greater. * may have: The talc particles (e.g., microcrystalline talc particles) have a CIELAB b value of about 2.0 or less, e.g., about 1.5 or less. * The talc particles (e.g., microcrystalline talc particles) may have a CIELAB b value of about 0.9 or greater, e.g., about 1.0 or greater, or about 1.1 or greater. * The talc particles (e.g., microcrystalline talc particles) may have a CIELAB b of about 0.9 to about 2.0, e.g., about 0.9 to about 1.5, or about 1.0 to about 2.0, or about 1.0 to about 1.5, or about 1.1 to about 2.0, or about 1.1 to about 1.5. * may have:
[0039] L * and b * is CIE L * a * b * The color component value in the color space scale. * is a measure of whiteness. * is a measure of yellowness. * and b * can be determined using a spectrophotometer / colorimeter such as the Konica Minolta CM-3700d (available from Konica Minolta Sensing Europe BV) using a D65 illuminant and the color space CIE LAB (1976).
[0040] Talc particles (e.g., microcrystalline talc particles) can be treated with a surface treatment agent. Surface-treated talc (e.g., microcrystalline talc) can be referred to, for example, as coated talc (e.g., microcrystalline talc). Surface treatment of talc (e.g., microcrystalline talc) can help reduce or eliminate agglomeration of talc particles (e.g., microcrystalline talc particles) and / or enhance incorporation of talc particles (e.g., microcrystalline talc particles) into polymer compositions. Suitable surface treatment agents for talc particles (e.g., microcrystalline talc particles) include compounds having hydrophobic carbon chains bearing polar groups, such as the families of amines, silanes, siloxanes, alcohols or acids and their metal salts.
[0041] In certain embodiments, the surface treatment agent is polyether or its derivative, for example, polyether-modified polysiloxane.In certain embodiments, the polyether is polyoxyalkylene (POA), for example, polyalkylene glycol (PAG) or polyalkylene oxide (PAO).As used herein, the term "polyalkylene glycol" refers to the POA with number average molecular mass less than 20,000 g / mol, and the term "polyalkylene oxide" refers to the POA with number average molecular mass above 20,000 g / mol. In a specific embodiment, the surface treatment agent comprises or is a polyalkylene glycol having a number average molecular mass of about 100 to about 15,000 g / mol, for example, about 200 to about 10,000 g / mol, or about 500 to about 9000 g / mol, or about 1000 to about 9000 g / mol, or about 2000 to about 9000 g / mol, or about 2000 to about 5000 g / mol, or about 3000 to about 5000 g / mol, or about 4000 to about 9000 g / mol, or about 6000 to about 9000 g / mol, or about 6000 to about 8500 g / mol. In certain embodiments, the polyether is a polyalkylene oxide selected from one or more of paraformaldehyde (polymethylene oxide), polytetramethylene glycol, polytetramethylene ether glycol, polyethylene oxide, polypropylene oxide, polybutylene oxide, and combinations thereof. In certain embodiments, the surface treatment comprises or is polyethylene glycol. In certain embodiments, the surface treatment comprises or is a mixture of polyethylene glycol and polypropylene glycol (PPG). In a specific embodiment, the surface treatment agent is a polyethylene glycol (PEG) having a number average molecular mass of about 200 to about 10,000 g / mol, for example, about 500 to about 9000 g / mol, or about 1000 to about 9000 g / mol, or about 2000 to about 9000 g / mol, or about 2000 to about 5000 g / mol, or about 3000 to about 5000 g / mol, or about 4000 to about 9000 g / mol, or about 6000 to about 9000 g / mol, or about 6000 to about 8500 g / mol.Exemplary PEGs include the Puriol™ series of polyglycols from BASF, such as Puriol™ 8005.
[0042] In certain embodiments, the surface treatment comprises or is a fatty acid and / or a metal salt thereof, such as stearic acid or a metal stearate, such as magnesium stearate, calcium stearate, or zinc stearate, including fatty acids with carbon chain lengths of C8 to C24 and mixtures of fatty acids with carbon chain lengths of C8 to C24.
[0043] Suitable silane-based agents include aminosilanes, such as trimethoxysilylethylamine, triethoxysilylethylamine, tripropoxysilylethylamine, tributoxysilylethylamine, trimethoxysilylpropylamine, triethoxysilylpropylamine, tripropoxysilylpropylamine, triisopropoxysilylpropylamine, tributoxysilylpropylamine, trimethoxysilylbutylamine, triethoxysilylbutylamine, tripropoxysilylbutylamine, tributoxysilylbutylamine, trimethoxysilylpentylamine, triethylenesilylpropylamine, triethylenesilylpropylamine, triethylenesilylpropylamine, tripropylene ... Examples of suitable agents having hydrocarbyl and polar groups include hydrocarbyl amines such as triethanolamine (TEA) and amino alcohol agents such as 2-amino-2-methyl-1-propanol. AMP-95® is a commercially available formulation of 2-amino-2-methyl-1-propanol that contains 5% water. Other suitable agents include 3-thiocyanatopropyltriethoxysilane and bis-(3-triethoxysilylpropyl)tetrasulfane.
[0044] The surface treatment may be added in an amount effective to achieve the desired result. In certain embodiments, the amount of surface treatment agent is about 0.1% to 5% by weight relative to the weight of the talc, such as about 0.1% to 2% by weight relative to the weight of the talc.
[0045] The polymeric composition may include about 0.5 phr or more, such as about 1.0 phr or more, or about 1.5 phr or more, or about 2.0 phr or more of a surface treatment agent (e.g., a silane-based agent). The polymeric composition may include about 5.0 phr or less, such as about 3.0 phr or less, or about 2.5 phr or less, or about 2.3 phr or less, or about 2.2 phr or less of a surface treatment agent (e.g., a silane-based agent). The polymer composition may include from about 0.5 phr to about 5.0 phr, for example, from about 0.5 phr to about 3.0 phr, or from about 0.5 phr to about 2.5 phr, or from about 1.0 phr to about 5.0 phr, or from about 1.0 phr to about 3.0 phr, or from about 1.0 phr to about 2.5 phr, or from about 1.5 phr to about 5.0 phr, or from about 1.5 phr to about 3.0 phr, or from about 1.5 phr to about 2.0 phr, or from about 2.0 phr to about 5.0 phr, or from about 2.0 phr to about 3.0 phr, or from about 2.0 phr to about 3.0 phr.
[0046] The surface treatment agent can be applied by adding to the talc particles (e.g., microcrystalline talc particles) and mixing using conventional methods. The surface treatment agent can be applied during the preparation of the talc particles (e.g., microcrystalline talc particles) from a relatively coarse talc (e.g., microcrystalline talc) starting material and prior to adding the talc particles (e.g., microcrystalline talc particles) to the polymer composition. Less surface treatment agent may be required to successfully incorporate talc particles (e.g., microcrystalline talc particles) into a polymer composition than is required to incorporate an equivalent (e.g., the same) amount (e.g., by weight) of silica or carbon black into the same polymer composition. In some embodiments, the talc particles (e.g., microcrystalline talc particles) are not treated with a surface treatment agent at all (i.e., the talc particles (e.g., microcrystalline talc particles) are uncoated talc (e.g., microcrystalline talc)).
[0047] Method for making talc particles Talc particles (e.g., microcrystalline talc particles) can be made by (a) grinding a talc feed material (e.g., a microcrystalline talc feed material) to produce a ground talc material (e.g., a ground microcrystalline talc material); and (b) classifying the ground talc material (e.g., the ground microcrystalline talc material) to remove a coarse fraction. The talc feed material (e.g., microcrystalline talc feed material) can be dry ground. The talc feed material (e.g., microcrystalline talc feed material) can be (e.g., dry) ground using an agitator mill, such as an agitator bead mill (i.e., a dry agitator bead mill). The agitator bead mill can be a horizontal agitator bead mill. A suitable agitator bead mill is the NETZSCH Ecutec PAMIR 30 agitator bead mill (available from NETZSCH-Feinmahltechnik GmbH, Germany). The NETZSCH Ecutec PAMIR 30 agitator bead mill has an installed power of 22 kW, an absorbed power of 6-8 kW (when used with ceramic beads, e.g., alumina beads having a diameter of about 4 mm to about 6 mm and a bulk density of about 2 kg / L), and an operating speed of 400 rpm.
[0048] The talc feed material (e.g., microcrystalline talc feed material) can be ground (e.g., dry) using grinding media (e.g., in an agitator bead mill). For example, the talc feed material (e.g., microcrystalline talc feed material) can be ground (e.g., dry) in an agitator bead mill using grinding media comprising grinding beads. The grinding beads can have a diameter of about 2 mm or more, e.g., about 4 mm or more. The grinding beads can have a diameter of about 20 mm or less, e.g., about 15 mm or less, or about 10 mm or less, or about 8 mm or less, or about 6 mm or less. The grinding beads can have a diameter of about 2 mm to about 20 mm, e.g., about 2 mm to about 15 mm, or about 2 mm to about 10 mm, or about 2 mm to about 8 mm, or about 2 mm to about 6 mm, or about 4 mm to about 10 mm, or about 4 mm to about 8 mm, or about 4 mm to about 6 mm. The grinding beads can be made of ceramic (e.g., alumina or stabilized zirconia, such as cerium- or yttrium-stabilized zirconia), plastic, or metal (e.g., steel). The grinding media can have a media volume ratio (MVR), which is the ratio of the grinding bead volume to the total volume of the grinding media, of about 20% to about 80%.
[0049] The agitator mill (e.g., an agitator bead mill) may be operated at a speed of about 100 rpm or more, for example, about 200 rpm or more, or about 300 rpm or more, or about 400 rpm or more. The agitator mill (e.g., an agitator bead mill) may be operated at a speed of about 1000 rpm or less, for example, about 600 rpm or less, or about 500 rpm or less, or about 400 rpm or less. The agitator mill (e.g., an agitator bead mill) may be operated at a speed of about 100 rpm to about 1000 rpm, for example, about 200 rpm to about 600 rpm, or about 300 rpm to about 500 rpm, for example, about 400 rpm.
[0050] The agitator mill (e.g., an agitator bead mill) can be operated with a specific grinding energy of about 100 kWh / t or more, e.g., about 200 kWh / t or more, or about 300 kWh / t or more, or about 400 kWh / t or more, or about 500 kWh / t or more. The agitator mill (e.g., an agitator bead mill) can be operated with a specific grinding energy of about 1000 kWh / t or less, e.g., about 900 kWh / t or less, or about 800 kWh / t or less, or about 700 kWh / t or less, or about 600 kWh / t or less, or about 500 kWh / t or less, or about 400 kWh / t or less. The stirred mill (e.g., stirred bead mill) can be operated at a specific grinding energy of about 100 kWh / t to about 800 kWh / t, e.g., about 200 kWh / t to about 700 kWh / t, or about 300 kWh / t to about 600 kWh / t, or about 300 kWh / t to about 400 kWh / t, or about 500 kWh / t to about 600 kWh / t.
[0051] Classification refers to a process in which particles of a ground talc material (e.g., ground microcrystalline talc material) are separated by size. Classification can be by any suitable method, including, for example, air classification, sieve analysis, and sedimentation. Classification can be, for example, dry classification. Preferably, the ground talc material (e.g., ground microcrystalline talc material) is classified using air classification. A suitable air classifier is the NETZSCH Ecutec BORA 50 Turbo Air Classifier (available from NETZSCH-Feinmahltechnik GmbH, Germany). The NETZSCH Ecutec BORA 50 Turbo Air Classifier has a maximum air flow rate of 1800 m 3 / hour, maximum rotor speed 8700rpm, installed power 10kW, maximum supply capacity 1800kg / hour and main fan installed power 30kW.
[0052] In the methods described herein, a portion of the largest particles (i.e., the coarse fraction) of a ground talc material (e.g., a ground microcrystalline talc material) is removed by classification. Thus, the talc particles (e.g., microcrystalline talc particles) of the present invention comprise (e.g., consist essentially of, or consist of) the fine talc particles remaining after the larger particles have been removed. In other words, the ground talc material (e.g., ground microcrystalline talc material) can be classified to separate the material into two fractions. The fine fraction is the talc particles (e.g., microcrystalline talc particles) of the present invention. The coarse fraction can be considered a by-product. The coarse fraction can be ground and classified again.
[0053] The proportion of larger particles to be removed can be selected depending on the target particle size distribution of the talc particles (e.g., microcrystalline talc particles). For example, about 10% to about 99.5% by weight of the largest particles, e.g., about 10% to about 99% by weight, or about 10% to about 95% by weight, or about 20% to about 99.5% by weight, or about 20% to about 99% by weight, or about 20% to about 95% by weight, or about 30% to about 99.5% by weight, or about 30% to about 99% by weight, or about 30% to about 95% by weight, or about 40% to about 99.5% by weight, or about 40% to about 99% by weight, or about 40% to about 95% by weight, or about 50% to about 99.5% by weight, or about 50% to about 99% by weight, or about 50% to about 95% by weight. %, or about 60% by mass to about 99.5% by mass, or about 60% by mass to about 99% by mass, or about 60% by mass to about 95% by mass, or about 70% by mass to about 99.5% by mass, or about 70% by mass to about 99% by mass, or about 70% by mass to about 95% by mass, or about 80% by mass to about 99.5% by mass, or about 80% by mass to about 99% by mass, or about 80% by mass to about 95% by mass, or about 80% by mass to about 90% by mass, or about 90% by mass to about 99.5% by mass, or about 90% by mass to about 99% by mass, or about 90% by mass to about 95% by mass can be removed to produce talc particles (e.g., microcrystalline talc particles).
[0054] The amount of fine fraction produced can be directly correlated to the speed of the classifier turbine. The faster the classifier speed, the lower the yield (%) of fine product. The faster the classifier speed, the lower the top cut of the fine fraction (e.g., d 95 Or d 98 ) is lower. Thus, the speed of the classification turbine can be adjusted depending on the desired particle size and product yield. The classification turbine may be operated at a speed of about 1000 rpm or more, e.g., about 2000 rpm or more, or about 3000 rpm or more, or about 4000 rpm or more, or about 5000 rpm or more, or about 6000 rpm or more, or about 7000 rpm or more, or about 8000 rpm or more. The classification turbine may be operated at a speed of about 15000 rpm or less, e.g., about 14000 rpm or less, or about 13000 rpm or less, or about 12000 rpm or less, or about 11000 rpm or less, or about 10000 rpm or less, or about 9000 rpm or less, or about 8000 rpm or less, or about 7000 rpm or less, or about 6000 rpm or less. The classification turbine may be operated at a speed of about 1000 rpm to about 15000 rpm, for example, about 2000 rpm to about 14000 rpm, or about 3000 rpm to about 13000 rpm, or about 4000 rpm to about 12000 rpm, or about 4000 rpm to about 11000 rpm, or about 4000 rpm to about 10000 rpm, or about 4000 rpm to about 9000 rpm, or about 5000 rpm to about 10000 rpm, or about 5000 rpm to about 9000 rpm, or about 6000 rpm to about 10000 rpm, or about 6000 rpm to about 9000 rpm.
[0055] The classification turbine may be operated at a peripheral speed of about 10 m / s or more, e.g., about 20 m / s or more, or about 30 m / s or more, or about 40 m / s or more, or about 50 m / s or more, or about 60 m / s or more, or about 70 m / s or more, or about 80 m / s or more. The classification turbine may be operated at a peripheral speed of about 100 m / s or less, e.g., about 90 m / s or less, or about 80 m / s or less, or about 70 m / s or less. The classification turbine may be operated at a peripheral speed of about 10 m / s to about 100 m / s, e.g., about 20 m / s to about 90 m / s, or about 30 m / s to about 80 m / s.
[0056] The amount of fine fraction produced can also be correlated with other operating parameters of the classifier turbine, such as air flow rate. The classifier turbine is approximately 500 m 3 / hour or more, for example, about 750m 3 / hour or more, or about 1000m 3 The classifier turbine can be operated at air flows of about 2500 m3 / hour or less, for example, about 2000m 3 / hour or less, or about 1500m 3 The classifier turbine can be operated at an air flow rate of about 500 m 3 / hour~about 2500m 3 / hour, for example, about 500m 3 / hour~about 2000m 3 / hour or about 500m 3 / hour~about 1500m 3 / hour or about 750m 3 / hour~about 2500m 3 / hour or about 750m 3 / hour~about 2000m 3 / hour or about 750m 3 / hour~about 1500m 3 / hour or about 1000m 3 / hour~about 2500m 3 / hour or about 1000m 3 / hour~about 2000m 3 / hour or about 1000m 3 / hour~about 1500m 3 It can be operated at an air flow rate of 1 / hour. The classification turbine may be operated with a fines yield of about 3% or more, e.g., about 4% or more, or about 5% or more, or about 6% or more, or about 7% or more, or about 8% or more, or about 9% or more, or about 10% or more. The classification turbine may be operated with a fines yield of about 20% or less, e.g., about 15% or less, or about 12% or less, or about 11% or less. The classification turbine may be operated with a fines yield of about 3% to about 20%, e.g., about 4% to about 15%, or about 5% to about 12%, or about 6% to about 12%, or about 7% to about 11%.
[0057] The method may include returning the coarse fraction removed by classification for further grinding. For example, the method may include returning the coarse fraction to the mill (e.g., an agitator bead mill) for further dry grinding. For example, the mill (e.g., an agitator bead mill) and the classifier (e.g., an air classifier) may be arranged to form a grinding / classifying circuit in which (a) the mill (e.g., an agitator bead mill) continuously or periodically supplies the ground talc material (e.g., ground microcrystalline talc material) to the classifier (e.g., an air classifier) for classification, and (b) the coarse fraction is continuously or periodically returned from the classifier (e.g., an air classifier) to the mill (e.g., an agitator bead mill) for further grinding.
[0058] An exemplary grinding / classifying circuit 1 is shown diagrammatically in FIG. 1. Talc feed material 2 is fed from an input hopper 3 to an agitator bead mill 4 for grinding. Optional grinding aid 5 may be fed to the agitator bead mill 4 from a grinding aid store 6. The ground talc material 7 is discharged by the agitator bead mill 4 to an air classifier 8. The air classifier 8 separates the ground talc material 7 into a coarse fraction 9 that is fed back to the agitator bead mill 4, and a fine fraction 10 that is fed to a discharge hopper 11. Talc particle product 12 may be removed from the discharge hopper 11. Movement of the material through the system is assisted using airflow generated by air inlets 13, 14, and 15, air mover 16, and air outlet 17.
[0059] The method includes increasing the BET surface area of the talc particles (e.g., microcrystalline talc particles) by about 10 m (compared to the BET surface area of the talc feed material (e.g., microcrystalline talc feed material) before grinding). 2 / g or more, for example, about 20m 2 / g or more, or about 30m 2 / g or more. The method may include increasing the BET surface area of the talc particles (e.g., microcrystalline talc particles) by about 100% or more (compared to the BET surface area of the talc feed material (e.g., microcrystalline talc feed material) before milling), e.g., by about 200% or more, or by about 300% or more. The method may include increasing the BET surface area of the talc particles (compared to the BET surface area of the talc feed material (e.g., microcrystalline talc feed material) before milling), by about 2 times or more, e.g., by about 3 times or more, or by about 4 times or more.
[0060] The method is the separation of talc particles by Sedigraph 50 (a) of the talc feed material (e.g., microcrystalline talc feed material) before grinding, measured by Sedigraph 50 The method may include reducing the diameter of the talc particles by about 5 μm or more, e.g., about 6 μm or more, or about 7 μm or more, or about 8 μm or more, or about 9 μm or more, or about 10 μm or more, or about 50 μm or more, or about 100 μm or more, or about 1 mm or more, or about 5 mm or more (compared to d by Sedigraph). 50 (a) of the talc feed material (e.g., microcrystalline talc feed material) before grinding, measured by Sedigraph 50 The method may include reducing the d(2) of the talc particles by about 50% or more, e.g., about 60% or more, or about 70% or more, or about 80% or more, or about 90% or more, or about 95% or more, or about 99% or more (compared to about 50% or more, e.g., about 60% or more, or about 70% or more, or about 80% or more, or about 90% or more, or about 95% or more, or about 99% or more. 50 (a) of the talc feed material (e.g., microcrystalline talc feed material) before grinding, measured by Sedigraph 50 In some embodiments, the method may include reducing the amount of the ion exchange reaction (compared to about 1 / 2 or more), e.g., about 5 or more, or about 7 or more, or about 10 or more, or about 12 or more, or about 20 or more, or about 30 or more, or about 40 or more, or about 50 or more, or about 100 or more.
[0061] The method is laser delamination of talc particles. 50 (a) of a talc feed material (e.g., a microcrystalline talc feed material) prior to milling by a laser;50 The method may include reducing the diameter of the talc particles by about 5 μm or more, e.g., about 6 μm or more, or about 7 μm or more, or about 8 μm or more, or about 9 μm or more, or about 10 μm or more, or about 50 μm or more, or about 100 μm or more, or about 1 mm or more, or about 5 mm or more (compared to about 1 mm or more). 50 (a) of a talc feed material (e.g., a microcrystalline talc feed material) prior to milling by a laser; 50 The method may include reducing the number of talc particles by about 50% or more, e.g., about 60% or more, or about 70% or more, or about 80% or more, or about 90% or more, or about 95% or more, or about 99% or more (compared to about 50% or more, e.g., about 60% or more, or about 70% or more, or about 80% or more, or about 90% or more, or about 95% or more, or about 99% or more). 50 (a) of a talc feed material (e.g., a microcrystalline talc feed material) prior to milling by a laser; 50 by about 2-fold or more, e.g., about 3-fold or more, or about 4-fold or more, or about 5-fold or more, or about 7-fold or more, or about 10-fold or more, or about 12-fold or more, or about 20-fold or more, or about 30-fold or more, or about 40-fold or more, or about 50-fold or more, or about 100-fold or more.
[0062] Talc Supply Material The talc feed material can be a microcrystalline talc feed material. Talc feedstock (e.g., microcrystalline talc feedstock) has a density of about 7.5 g / m 2 For example, about 7.0 g / m 2 or less than 6.0 g / m 2 Less than or equal to about 5.0 g / m 2 or less than about 4.0 g / m 2 Less than or equal to about 3.0 g / m 2 Less than or equal to about 2.0 g / m 2 or less than about 1.5 g / m 2 The talc feed material (e.g., a microcrystalline talc feed material) may have a crystallinity index, CI, of about 0.01 g / m 2 More than, for example, about 0.1 g / m 2 or more, or about 0.5 g / m 2The talc feed material (e.g., microcrystalline talc feed material) may have a crystallinity index, CI, of about 0.01 g / m 2 ~about 7.5g / m 2 , or about 0.01 g / m 2 ~Approx. 7.0g / m 2 , or about 0.01 g / m 2 ~about 6.0g / m 2 , or about 0.01 g / m 2 ~Approx. 5.0g / m 2 , or about 0.01 g / m 2 ~about 4.0g / m 2 , or about 0.01 g / m 2 ~About 3.0g / m 2 , or about 0.01 g / m 2 ~about 2.0g / m 2 , or about 0.01 g / m 2 ~Approx. 1.5g / m 2 , or about 0.1 g / m 2 ~about 7.5g / m 2 , or about 0.1 g / m 2 ~about 6.0g / m 2 , or about 0.1 g / m 2 ~about 4.0g / m 2 , or about 0.1 g / m 2 ~about 2.0g / m 2 , or about 0.5 g / m 2 ~about 7.5g / m 2 , or about 0.5 g / m 2 ~about 6.0g / m 2 , or about 0.5 g / m 2 ~about 4.0g / m 2 , or about 0.5 g / m 2 ~about 2.0g / m 2 The crystallinity index, CI, may be:
[0063] The talc feed material (e.g., microcrystalline talc feed material) has a d by Sedigraph of about 5.0 μm or more, e.g., about 6.0 μm or more, or about 7.0 μm or more, or about 7.5 μm or more. 50 The maximum d of the talc feed material (e.g., microcrystalline talc feed material) may be 50Alternatively, the talc feed material (e.g., microcrystalline talc feed material) may have a d measured by sieving of about 20 mm or less, or about 10 mm or less, or about 5 mm or less, or about 1 mm or less, or about 100 μm or less. 50 The talc feed material (e.g., microcrystalline talc feed material) may have a d by Sedigraph of about 50 μm or less, or about 20.0 μm or less, or about 15.0 μm or less, or about 10.0 μm or less, or about 9.0 μm or less, or about 8.5 μm or less, or about 8.0 μm or less. 50 The talc feed material (e.g., microcrystalline talc feed material) may have a diameter of about 5.0 μm to about 20 mm, e.g., about 5.0 μm to about 15 mm, or about 5.0 μm to about 10 mm, e.g., about 6.0 μm to about 10 mm, or about 7.0 μm to about 10 mm, or about 7.5 μm to about 10 mm, or about 5.0 μm to about 5 mm, or about 6.0 μm to about 5 mm, or about 7.0 μm to about 5 mm, or about 7.5 μm to about 5 mm, or about 5.0 μm to about 1 mm, or about 6.0 μm to about 1 mm, or about 7.0 μm to about 1 mm, or about 7.5 μm to about 1 mm, or about 5.0 μm to about 100 μm, or about 6.0 μm to about 100 μm, or about 7.0 μm to about 100 μm, or about 7.5 μm to about 100 μm, or about 5.0 μm to about 20.0 μm, or about 6.0 μm to about 20.0 μm, or about 7.0 μm to about 20.0 μm, or about 7 0.5 μm to about 20.0 μm, or about 5.0 μm to about 15.0 μm, or about 6.0 μm to about 15.0 μm, or about 7.0 μm to about 15.0 μm, or about 7.5 μm to about 15.0 μm, or about 5.0 μm to about 10.0 μm, or about 6.0 μm to about 10.0 μm, or about 7.0 μm to about 10.0 μm, or about 7.5 μm to about 10.0 μm, or about 5.0 μm to about 9.0 μm, or about 6.0 μm to about 9.0 μm, or about 7.0 μm to about 9.0 μm, or about 7.5 μm to about 9.0 μm, or about 5.0 μm to about 8.5 μm, or about 6.0 μm to about 8.5 μm, or about 7.0 μm to about 8.5 μm, or about 7.5 μm to about 8.5 μm, or about 5.0 μm to about 8.0 μm, or about 6.0 μm to about 8.0 μm, or about 7.0 μm to about 8.0 μm, or about 7.5 μm to about 8.0 μm, 50The values are from Sedigraph and for d > 50 μm 50 The value of d is determined by screening. 50 may have:
[0064] The talc feed material (e.g., microcrystalline talc feed material) can be laser polished to a diameter of about 5.0 μm or greater, e.g., about 7.0 μm or greater, or about 9.0 μm or greater, or about 10.0 μm or greater. 50 The maximum d of the talc feed material (e.g., microcrystalline talc feed material) may be 50 Alternatively, the talc feed material (e.g., microcrystalline talc feed material) may have a d measured by sieving of about 20 mm or less, or about 10 mm or less, or about 5 mm or less. 50 The talc feed material (e.g., microcrystalline talc feed material) may have a laser d of about 1 mm or less, or about 200 μm or less, or about 40.0 μm or less, or about 30.0 μm or less, or about 20.0 μm or less, or about 15.0 μm or less, or about 12.0 μm or less, or about 11.0 μm or less. 50The talc feed material (e.g., microcrystalline talc feed material) may have a diameter of about 5.0 μm to about 20 mm, e.g., about 7.0 μm to about 20 mm, or about 9.0 μm to about 20 mm, or about 10.0 μm to about 20 mm, or about 5.0 μm to about 10 mm, or about 7.0 μm to about 10 mm, or about 9.0 μm to about 10 mm, or about 10.0 μm to about 10 mm, or about 5.0 μm to about 1 mm, or about 7.0 μm to about 1 mm, or about 9.0 μm to about 1 mm, or about 10.0 μm to about 1 mm, or about 5.0 μm to about 200 μm, or about 7.0 μm to about 200 μm, or about 9.0 μm to about 200 μm, or about 10.0 μm to about 200 μm, or about 5.0 μm to about 40.0 μm, or about 7.0 μm to about 40.0 μm, or about 9.0 μm to about 40.0 μm, or about 10.0 μm to about 40.0 μm, or about 5.0 μm to about 40.0 μm, or about 7.0 μm to about 40.0 μm, or about 9.0 μm m to about 40.0 μm, or about 10.0 μm to about 40.0 μm, or about 5.0 μm to about 30.0 μm, or about 7.0 μm to about 30.0 μm, or about 9.0 μm to about 30.0 μm, or about 10.0 μm to about 30.0 μm, or about 5.0 μm to about 20.0 μm, or about 7.0 μm to about 20.0 μm, or about 9.0 μm to about 20.0 μm, or about 10.0 μm to about 20.0 μm, or about 5.0 μm to about 15.0 μm, or about 7.0 μm m to about 15.0 μm, or about 9.0 μm to about 15.0 μm, or about 10.0 μm to about 15.0 μm, or about 5.0 μm to about 12.0 μm, or about 7.0 μm to about 12.0 μm, or about 9.0 μm to about 12.0 μm, or about 10.0 μm to about 12.0 μm, or about 5.0 μm to about 11.0 μm, or about 7.0 μm to about 11.0 μm, or about 9.0 μm to about 11.0 μm, or about 10.0 μm to about 11.0 μm, 50 The values of d by laser and d > 1 mm 50 The value of d is determined by screening. 50 may have:
[0065] The talc feed material (eg, a microcrystalline talc feed material) can have a Minolta Y brightness of about 80 or greater, such as about 85 or greater, or about 86 or greater. The talc feed material (e.g., a microcrystalline talc feed material) may have a CIELAB L of about 85 or greater, e.g., about 90 or greater, or about 94 or greater. * may have: The talc feed material (e.g., a microcrystalline talc feed material) may have a CIELAB a of about 1.0 or less, e.g., about 0.5 or less, or about 0.3 or less, or about 0.2 or less, or about 0.1 or less. * may have:
[0066] The talc feed material (e.g., a microcrystalline talc feed material) may have a CIELAB b value of about 1.0 or greater, e.g., about 2.0 or greater, or about 2.5 or greater, or about 2.6 or greater. * The talc feed material (e.g., a microcrystalline talc feed material) may have a CIELAB b of about 4.0 or less, e.g., about 3.0 or less, or about 2.7 or less, or about 2.6 or less. * The talc feed material (e.g., a microcrystalline talc feed material) may have a CIELAB b of about 1.0 to about 4.0, e.g., about 2.0 to about 4.0, or about 2.5 to about 4.0, or about 2.6 to about 4.0, or about 1.0 to about 3.0, or about 2.0 to about 3.0, or about 2.5 to about 3.0, or about 2.6 to about 3.0, or about 1.0 to about 2.7, or about 2.0 to about 2.7, or about 2.5 to about 2.7, or about 2.6 to about 2.7, or about 1.0 to about 2.6, or about 2.0 to about 2.6, or about 2.5 to about 2.6. * may have:
[0067] The talc feed material (e.g., microcrystalline talc feed material) is about 30 m 2 / g or less, for example, about 20m 2 / g or less, or about 10m 2 / g or less, or about 9.5m 2 The talc feed material (e.g., microcrystalline talc feed material) may have a BET specific surface area of about 1 m 2 / g or more, for example, about 5m 2 The talc feed material (e.g., microcrystalline talc feed material) may have a BET specific surface area of about 1 m 2 / g ~ approx. 30m 2 / g, for example, about 1m 2 / g~about 20m 2 / g, or about 1m 2 / g~about 10m 2 / g, or about 1m 2 / g ~ approx. 9.5m 2 / g, or about 5m 2 / g ~ approx. 30m 2 / g, or about 5m 2 / g~about 20m 2 / g, or about 5m 2 / g~about 10m 2 / g, or about 5m 2 / g ~ approx. 9.5m 2 / g.
[0068] A talc feed material (e.g., a microcrystalline talc feed material) can have a talc content (i.e., magnesium silicate content) of about 60% or more, e.g., about 70% or more, or about 80% or more, or about 90% or more, or about 95% or more, or about 99% or more of the talc (i.e., magnesium silicate). A talc feed material (e.g., a microcrystalline talc feed material) can have a talc content (i.e., magnesium silicate content) of 100% or less of the talc (i.e., magnesium silicate), e.g., about 99% or less, or about 95% or less, or about 90% or less, or about 80% or less of the talc (i.e., magnesium silicate). The talc feed material (e.g., microcrystalline talc feed material) may be about 60% to about 100%, or about 70% to about 100%, or about 80% to about 100%, or about 90% to about 100%, or about 95% to about 100%, or about 99% to about 100%, or about 60% to about 99%, or about 70% to about 99%, or about 80% to about 99%, or about 90% to about 99%, or about The talc (i.e., magnesium silicate content) may be from 95% to about 99%, or from about 60% to about 95%, or from about 70% to about 95%, or from about 80% to about 95%, or from about 90% to about 95%, or from about 60% to about 90%, or from about 70% to about 90%, or from about 80% to about 90%, for example, about 80% talc (i.e., magnesium silicate content).
[0069] The talc feed material (e.g., microcrystalline talc feed material) may have a chlorite content of about 40% or less, e.g., about 30% or less, or about 20% or less, or about 10% or less, or about 5% or less, or about 1% or less. The talc feed material (e.g., microcrystalline talc feed material) may have a chlorite content of about 60% to about 100%, e.g., about 70% to about 100%, or about 80% to about 100%, or about 90% to about 100%, or about 95% to about 100%, or about 99% to about 100%, or about 60% to about 99%, or about 70% to about 99%, or about 80% to about 99%, or about 90% to about 99%, or about 95% to about 99%. or about 60% to about 95%, or about 70% to about 95%, or about 80% to about 95%, or about 90% to about 95%, or about 60% to about 90%, or about 70% to about 90%, or about 80% to about 90%, e.g., about 80% talc; and optionally about 40% or less, e.g., about 30% or less, or about 20% or less, or about 10% or less, or about 5% or less, or about 1% or less of chlorite. The talc feed material (e.g., microcrystalline talc feed material) can comprise about 60% to about 99%, e.g., about 70% to about 99%, or about 80% to about 99%, or about 90% to about 99%, or about 95% to about 99%, or about 60% to about 95%, or about 70% to about 95%, or about 80% to about 95%, or about 90% to about 95%, or about 60% to about 90%, or about 70% to about 90%, or about 80% to about 90%, e.g., about 80% talc, the remainder being chlorite and normal impurities.
[0070] Talc feedstock (e.g., microcrystalline talc feedstock) has a talc content of about 0.75 mg / m 2 or more, for example, about 0.8 mg / m 2 or more than about 0.9 mg / m 2 or more than 1.0 mg / m 2 The talc feed material (e.g., microcrystalline talc feed material) may have a water adsorption at 50% relative humidity of about 2.5 mg / m 2 For example, about 2.0 mg / m 2 Less than or equal to about 1.5 mg / m 2 or less than about 1.25 mg / m 2 The talc feed material (e.g., a microcrystalline talc feed material) may have a water adsorption at 50% relative humidity of about 0.75 mg / m2 ~about 2.5mg / m 2 , for example, about 0.75 mg / m 2 ~about 2.0mg / m 2 , or about 0.75 mg / m 2 ~about 1.5mg / m 2 , or about 0.75 mg / m 2 ~about 1.25mg / m 2 , or about 0.8 mg / m 2 ~about 2.5mg / m 2 , or about 0.8 mg / m 2 ~about 2.0mg / m 2 , or about 0.9 mg / m 2 ~about 1.5mg / m 2 , or about 0.9 mg / m 2 ~about 1.25mg / m 2 , or about 0.9 mg / m 2 ~about 2.5mg / m 2 , or about 0.9 mg / m 2 ~about 2.0mg / m 2 , or about 0.9 mg / m 2 ~about 1.5mg / m 2 , or about 0.9 mg / m 2 ~about 1.25mg / m 2 , or about 1.0 mg / m 2 ~about 2.5mg / m 2 , or about 1.0 mg / m 2 ~about 2.0mg / m 2 , or about 1.0 mg / m 2 ~about 1.5mg / m 2 , or about 1.0 mg / m 2 ~about 1.25mg / m 2 of water adsorption at 50% relative humidity.
[0071] The talc feed material may have a diameter of (a) about 5.0 μm to about 20 mm, e.g., about 5.0 μm to about 10 mm, about 5.0 μm to about 5 mm, or about 5.0 μm to about 1 mm, or about 5.0 μm to about 100 μm, or about 5.0 μm to about 20.0 μm, or about 5.0 μm to about 10.0 μm, that is, a diameter of 50 μm or less. 50 The values are from Sedigraph and for d > 50 μm 50 The value of d is determined by screening.50 (b) about 5.0 μm to about 20 mm, e.g., about 5.0 μm to about 10 mm, or about 5.0 μm to about 1 mm, or about 5.0 μm to about 200 μm, or about 5.0 μm to about 40.0 μm, or about 5.0 μm to about 20.0 μm, d of 1 mm or less 50 The values of d by laser and d > 1 mm 50 The value of d is determined by screening. 50 (c) a Minolta Y whiteness of about 80 or greater, e.g., about 85 or greater; (d) a CIELAB L whiteness of about 85 or greater, e.g., about 90 or greater. * (e) a CIELAB a of about 1.0 or less, e.g., about 0.5 or less; * (f) a CIELAB b of about 1.0 to about 4.0, for example, about 2.0 to about 3.0 * ;(g) approx. 30m 2 / g or less, for example, about 20m 2 / g or less, or about 10m 2 / g or less; and / or (h) a talc content of about 60% or more, e.g., about 80% or more, of talc, and an optional chlorite content of about 40% or less, e.g., about 20% or less, of chlorite.
[0072] The talc feed material may have a diameter of (a) about 5.0 μm to about 20 mm, e.g., about 5.0 μm to about 10 mm, about 5.0 μm to about 5 mm, or about 5.0 μm to about 1 mm, or about 5.0 μm to about 100 μm, or about 5.0 μm to about 20.0 μm, or about 5.0 μm to about 10.0 μm, that is, a diameter of 50 μm or less. 50 The values are from Sedigraph and for d > 50 μm 50 The value of d is determined by screening. 50 (b) about 5.0 μm to about 20 mm, e.g., about 5.0 μm to about 10 mm, or about 5.0 μm to about 1 mm, or about 5.0 μm to about 200 μm, or about 5.0 μm to about 40.0 μm, or about 5.0 μm to about 20.0 μm, d of 1 mm or less 50 The values of d by laser and d > 1 mm 50 The value of d is determined by screening. 50(c) a Minolta Y whiteness of about 80 or greater, e.g., about 85 or greater; (d) a CIELAB L whiteness of about 85 or greater, e.g., about 90 or greater. * (e) a CIELAB a of about 1.0 or less, e.g., about 0.5 or less; * (f) a CIELAB b of about 1.0 to about 4.0, for example, about 2.0 to about 3.0 * ;(g) approx. 30m 2 / g or less, for example, about 20m 2 / g or less, or about 10m 2 (h) a talc content of about 60% or more, e.g., about 80% or more, of talc, and an optional chlorite content of about 40% or less, e.g., about 20% or less, of chlorite; and / or (i) about 7.5 g / m 2 For example, about 0.01 g / m or less 2 ~about 7.5g / m 2 , or about 0.01 g / m 2 ~about 4.0g / m 2 The talc feedstock may be a microcrystalline talc feedstock having a CI of
[0073] The talc feed material may have a diameter of (a) about 5.0 μm to about 20 mm, e.g., about 5.0 μm to about 10 mm, or about 5.0 μm to about 5 mm, or about 5.0 μm to about 1 mm, or about 5.0 μm to about 100 μm, or about 5.0 μm to about 20.0 μm, or about 5.0 μm to about 10.0 μm, with a diameter of 50 μm or less. 50 The values are from Sedigraph and for d > 50 μm 50 The value of d is determined by screening. 50 (b) about 5.0 μm to about 20 mm, e.g., about 5.0 μm to about 10 mm, or about 5.0 μm to about 1 mm, or about 5.0 μm to about 200 μm, or about 5.0 μm to about 40.0 μm, or about 5.0 μm to about 20.0 μm, with a d of 1 mm or less 50 The values of d by laser and d > 1 mm 50 The value of d is determined by screening. 50 (c) a Minolta Y whiteness of about 80 or greater, e.g., about 85 or greater; (d) a CIELAB L whiteness of about 85 or greater, e.g., about 90 or greater. *(e) a CIELAB a of about 1.0 or less, e.g., about 0.5 or less; * (f) a CIELAB b of about 1.0 to about 4.0, for example, about 2.0 to about 3.0 * ;(g) approx. 30m 2 / g or less, for example, about 20m 2 / g or less, or about 10m 2 / g or less; and (h) a talc content of about 60% or more, e.g., about 80% or more, of talc, and an optional chlorite content of about 40% or less, e.g., about 20% or less, of chlorite.
[0074] The talc feed material may have a diameter of (a) about 5.0 μm to about 20 mm, e.g., about 5.0 μm to about 10 mm, or about 5.0 μm to about 5 mm, or about 5.0 μm to about 1 mm, or about 5.0 μm to about 100 μm, or about 5.0 μm to about 20.0 μm, or about 5.0 μm to about 10.0 μm, with a diameter of 50 μm or less. 50 The values are from Sedigraph and for d > 50 μm 50 The value of d is determined by screening. 50 (b) about 5.0 μm to about 20 mm, e.g., about 5.0 μm to about 10 mm, or about 5.0 μm to about 1 mm, or about 5.0 μm to about 200 μm, or about 5.0 μm to about 40.0 μm, or about 5.0 μm to about 20.0 μm, with a d of 1 mm or less 50 The values of d by laser and d > 1 mm 50 The value of d is determined by screening. 50 (c) a Minolta Y whiteness of about 80 or greater, e.g., about 85 or greater; (d) a CIELAB L whiteness of about 85 or greater, e.g., about 90 or greater. * (e) a CIELAB a of about 1.0 or less, e.g., about 0.5 or less; * (f) a CIELAB b of about 1.0 to about 4.0, for example, about 2.0 to about 3.0 * ;(g) approx. 30m 2 / g or less, for example, about 20m 2 / g or less, or about 10m 2(h) a talc content of about 60% or more, e.g., about 80% or more, of talc, and an optional chlorite content of about 40% or less, e.g., about 20% or less, of chlorite; and (i) about 7.5 g / m 2 For example, about 0.01 g / m or less 2 ~about 7.5g / m 2 , or about 0.01 g / m 2 ~about 4.0g / m 2 The talc feedstock may be a microcrystalline talc feedstock having a CI of
[0075] Polymer Composition The talc particles described herein can be used as a filler in a polymer composition. The talc particles can be used as an extender filler or a functional filler. As used herein, the term "functional filler" is understood to mean an additive incorporated into a polymer composition for the purpose of enhancing one or more of its physical (e.g., mechanical) properties. "Extender fillers" typically do not significantly change the properties of the polymer composition and essentially serve to reduce costs. Thus, also provided herein is a polymer composition comprising the talc particles described herein (e.g., microcrystalline talc particles).
[0076] In certain embodiments, talc particles (e.g., microcrystalline talc particles) may be used as a functional filler in a polymer composition, for example, to modify or enhance one or more mechanical properties of the polymer composition. In certain embodiments, talc particles (e.g., microcrystalline talc particles) are used as an extender filler, for example, to supplement or replace other filler materials that may be more expensive or more difficult to incorporate into polymer compositions. In certain embodiments, talc particles (eg, microcrystalline talc particles) function as both an extender filler and a functional filler.
[0077] The polymer composition may comprise about 5 phr (i.e., parts per hundred rubber) or more, such as about 10 phr or more, or about 20 phr or more, or about 30 phr or more, or about 40 phr or more, or about 50 phr or more, or about 60 phr or more, or about 70 phr or more, or about 80 phr or more, or about 90 phr or more, or about 100 phr or more of talc particles (e.g., microcrystalline talc particles). The polymer composition may comprise about 300 phr or less, such as about 200 phr or less, or about 150 phr or less, or about 100 phr or less of talc particles (e.g., microcrystalline talc particles).The polymer composition may have an average molecular weight of from about 5 phr to about 300 phr, for example, from about 10 phr to about 300 phr, or from about 20 phr to about 300 phr, or from about 30 phr to about 300 phr, or from about 40 phr to about 300 phr, or from about 50 phr to about 300 phr, or from about 60 phr to about 300 phr, or from about 70 phr to about 300 phr, or from about 80 phr to about 300 phr, or from about 90 phr to about 300 phr, or from about 100 phr to about 300 phr. , or about 5 phr to about 200 phr, or about 10 phr to about 200 phr, or about 20 phr to about 200 phr, or about 30 phr to about 200 phr, or about 40 phr to about 200 phr, or about 50 phr to about 200 phr, or about 60 phr to about 200 phr, or about 70 phr to about 200 phr, or about 80 phr to about 200 phr, or about 90 phr to about 200 phr, or about 100 phr to about 200 phr, or about 5 phr to about 200 phr about 150 phr, or about 10 phr to about 150 phr, or about 20 phr to about 150 phr, or about 30 phr to about 150 phr, or about 40 phr to about 150 phr, or about 50 phr to about 150 phr, or about 60 phr to about 150 phr, or about 70 phr to about 150 phr, or about 80 phr to about 150 phr, or about 90 phr to about 150 phr, or about 100 phr to about 150 phr, or about 5 phr to about 100 phr, or may contain about 10 phr to about 100 phr, or about 20 phr to about 100 phr, or about 30 phr to about 100 phr, or about 40 phr to about 100 phr, or about 50 phr to about 100 phr, or about 60 phr to about 100 phr, or about 70 phr to about 100 phr, or about 80 phr to about 100 phr, or about 90 phr to about 100 phr, or about 100 phr to about 100 phr of talc particles (e.g., microcrystalline talc particles).
[0078] The polymer composition may include a filler other than talc particles (e.g., microcrystalline talc particles). For example, the polymer composition may include one or more minerals other than talc particles (e.g., microcrystalline talc particles). For example, the polymer composition may include synthetic silica or silicate (e.g., precipitated silica or silicate), natural silica or silicate, clay minerals (e.g., hydrous kandite clays such as kaolin, halloysite, or ball clay), carbon black, metal hydroxides such as aluminum trihydroxide or magnesium dihydroxide, alkaline earth metal carbonates or sulfates such as calcium carbonate, magnesium carbonate, dolomite, gypsum, anhydrous (calcined) kandite clays such as metakaolin or fully calcined kaolin, mica, perlite, feldspar, nepheline syenite, wollastonite, diatomaceous earth, barite, and / or glass.
[0079] In certain embodiments, the polymer composition comprises, in addition to the talc particles (e.g., microcrystalline talc particles), precipitated silica, a clay mineral such as kaolin or ball clay, diatomaceous earth, and / or carbon black. In certain embodiments, the polymer composition comprises, in addition to the talc particles (e.g., microcrystalline talc particles), precipitated silica. In certain embodiments, the polymer composition comprises, in addition to the talc particles (e.g., microcrystalline talc particles), a clay mineral such as kaolin or ball clay. In certain embodiments, the polymer composition comprises, in addition to the talc particles (e.g., microcrystalline talc particles), diatomaceous earth. In certain embodiments, the polymer composition comprises, in addition to the talc particles (e.g., microcrystalline talc particles), carbon black. In certain embodiments, the polymer composition comprises, in addition to the talc particles (e.g., microcrystalline talc particles), precipitated silica and a clay mineral such as kaolin or ball clay. In certain embodiments, the polymer composition comprises, in addition to the talc particles (e.g., microcrystalline talc particles), precipitated silica and diatomaceous earth. In certain embodiments, the polymer composition can include talc other than the talc particles of the present invention (e.g., microcrystalline talc particles).In certain embodiments, the polymer composition does not include talc other than the talc particles of the present invention (e.g., microcrystalline talc particles). Filler compounds other than talc particles (e.g., microcrystalline talc particles) can be included during the preparation of the polymer composition or, alternatively, during the preparation of the talc particles (e.g., microcrystalline talc particles), for example, the talc particles (e.g., microcrystalline talc particles) can be mixed and blended with other filler compounds and combined with a surface treatment agent. In certain embodiments, the amount of other filler compounds is present in an amount less than about 100 phr, such as less than about 50 phr, or less than about 25 phr.
[0080] The polymer composition may include any natural or synthetic polymer or mixtures thereof. The polymer may be, for example, thermoplastic or thermoset. As used herein, the term "polymer" includes homopolymers and / or copolymers, as well as crosslinked and / or entangled polymers. The term "precursor" as it may be applied to a polymer component will be readily understood by those skilled in the art. For example, a suitable precursor may include one or more of a monomer, a crosslinker, a cure system including a crosslinker and a promoter, or any combination thereof. When talc particles (e.g., microcrystalline talc particles) are mixed with a precursor of a polymer, a polymer composition is then formed by curing and / or polymerizing the precursor components to form the desired polymer (e.g., vulcanizing a rubber).
[0081] The polymers, including homopolymers and / or copolymers, included in the polymer composition of the present invention may be crosslinked dimers, trimers, or tetramers of one or more of the following monomers: acrylic acid, methacrylic acid, methyl methacrylate, and alkyl acrylates having 1 to 18 carbon atoms in the alkyl group, styrene, substituted styrenes, divinylbenzene, diallyl phthalate, butadiene, vinyl acetate, acrylonitrile, methacrylonitrile, maleic anhydride, esters of maleic or fumaric acid, tetrahydrophthalic acid or anhydride, itaconic acid or anhydride, and esters of itaconic acid. It may be prepared with or without crotonic acid, neopentyl glycol, propylene glycol, butanediol, ethylene glycol, diethylene glycol, dipropylene glycol, glycerol, cyclohexanedimethanol, 1,6 hexanediol, trimethyolpropane, pentaerythritol, phthalic anhydride, isophthalic acid, terephthalic acid, hexahydrophthalic anhydride, adipic or succinic acid, azelaic acid and dimer fatty acid, toluene diisocyanate and diphenylmethane diisocyanate.
[0082] The polymer may be selected from one or more of polymethyl methacrylate (PMMA), polyacetal, polycarbonate, polyvinyl, polyacrylonitrile, polybutadiene, polystyrene, polyacrylate, polyethylene, polypropylene, epoxy polymer, unsaturated polyester, polyurethane, polycyclopentadiene, ethylene vinyl acetate, butyl rubber, hydrogenated nitrile butadiene rubber (NBR), natural rubber, polychloroprene, fluoroelastomer, polyvinyl acetate, ethylene-propylene-diene-methylene (EPDM), and copolymers thereof. Suitable polymers also include liquid rubbers such as silicone.
[0083] In certain embodiments, the polymer composition comprises an elastomer, such as a synthetic or natural rubber, e.g., styrene-butadiene rubber (e.g., the polymer content of the polymer composition is an elastomer, such as a synthetic or natural rubber, e.g., styrene-butadiene rubber). A polymer composition may comprise one single polymer (i.e., the polymer content of the polymer composition may consist essentially of, or consist of, one single polymer), or it may comprise two or more different polymers (i.e., the polymer content of the polymer composition may consist essentially of, or consist of, two or more different polymers).
[0084] The polymer composition may include styrene-butadiene rubber. The polymer content of the polymer composition may consist essentially of, consist of, or be styrene-butadiene rubber. The polymer composition may include a butadiene rubber. The polymer content of the polymer composition may consist essentially of, consist of, or be butadiene rubber. The polymer composition may include styrene-butadiene rubber and butadiene rubber. The polymer content of the polymer composition may consist essentially of, consist of, or can be styrene-butadiene rubber and butadiene rubber. The polymer composition may include styrene-butadiene rubber and butadiene rubber provided in a weight ratio of about 1:2 to about 2:1, e.g., about 1:1.5 to about 1.5:1, or about 1:1 (i.e., the polymer content of the polymer composition may consist essentially of, consist of, or can be styrene-butadiene rubber and butadiene rubber provided in a weight ratio of about 1:2 to about 2:1, e.g., about 1:1.5 to about 1.5:1, or about 1:1).
[0085] The polymer composition may further comprise one or more additives. The one or more additives may be selected from thickeners, emulsifiers, viscosity modifiers, softeners, plasticizers (such as polyethylene glycol), activators (such as zinc oxide), accelerators (such as 2-mercaptobenzothiazole (MBT), mercaptobenzothiazole disulfide (MBTS) or tetramethylthiuram disulfide (DTMT)), rubber processing oils (such as naphthenic oils), flame retardants (such as aluminum hydroxide), antibacterial agents, fungicides (such as propionic acid), hydrophobic agents (such as silicone oils), stearic acid, sulfur, and / or thermal conductivity modifiers (such as graphite), or any combination thereof. The polymer composition may comprise a total of about 50 phr or less of such additives, such as about 40 phr or less, or about 30 phr or less. The polymer composition may comprise a total of about 1 phr or more, such as about 10 phr or more, of such additives. The polymer composition may contain a total of from about 1 phr to about 50 phr of such additives, for example, from about 1 phr to about 40 phr, or from about 1 phr to about 30 phr, or from about 10 phr to about 50 phr, or from about 10 phr to about 40 phr, or from about 10 phr to about 30 phr.
[0086] The polymer composition may comprise from about 50 phr to about 150 phr, e.g., from about 75 phr to about 125 phr of a polymer (e.g., an elastomeric polymer such as rubber); and from about 50 phr to about 150 phr, e.g., from about 75 phr to about 125 phr of talc particles (e.g., microcrystalline talc particles). The polymer composition may further comprise from about 20 phr or less, e.g., from about 15 phr or less, or from about 10 phr or less, e.g., from about 1 phr to about 10 phr of one or more additives (e.g., PEG, zinc oxide, stearic acid, accelerators, sulfur, etc.); and / or from about 5 phr to about 40 phr, e.g., from about 10 phr to about 30 phr of rubber processing oil. The polymer composition may not comprise any mineral filler other than the talc particles (e.g., microcrystalline talc particles).
[0087] The polymer composition may comprise from about 50 phr to about 150 phr, e.g., from about 75 phr to about 125 phr of a polymer (e.g., an elastomeric polymer such as rubber); from about 10 phr to about 100 phr, e.g., from about 10 phr to about 60 phr of precipitated silica; and from about 10 phr to about 100 phr, e.g., from about 10 phr to about 80 phr of talc particles (e.g., microcrystalline talc particles). The polymer composition may further comprise from about 20 phr or less, e.g., from about 15 phr or less, or from about 10 phr or less, e.g., from about 1 phr to about 10 phr of one or more additives (e.g., PEG, zinc oxide, stearic acid, accelerators, sulfur, etc.); and / or from about 5 phr to about 40 phr, e.g., from about 10 phr to about 30 phr of rubber processing oil. The polymer composition may be free of mineral fillers other than precipitated silica and talc particles (eg, microcrystalline talc particles).
[0088] The polymer composition may include about 50 phr to about 150 phr, for example, about 75 phr to about 125 phr of a polymer (e.g., an elastomeric polymer such as rubber); about 10 phr to about 100 phr, for example, about 10 phr to about 60 phr of precipitated silica; and about 10 phr to about 100 phr, for example, about 10 phr to about 80 phr, or about 10 phr to about 50 phr of talc particles (e.g., microcrystalline talc particles). The polymer composition may further include about 0.5 phr to about 5 phr, for example, about 1 phr to about 3 phr of a surface treatment agent (e.g., a silane-based surface treatment agent). The polymer composition may not include mineral fillers other than precipitated silica and talc particles (e.g., microcrystalline talc particles). The polymer composition may include about 50 phr to about 150 phr, for example, about 75 phr to about 125 phr of a polymer (e.g., an elastomeric polymer such as rubber); about 20 phr to about 55 phr, for example, about 30 phr to about 45 phr of precipitated silica; and about 8 phr to about 55 phr, for example, about 10 phr to about 50 phr, or about 12 phr to about 48 phr of talc particles (e.g., microcrystalline talc particles). The polymer composition may further include about 0.5 phr to about 5 phr, for example, about 1 phr to about 3 phr of a surface treatment agent (e.g., a silane-based surface treatment agent). The polymer composition may not include mineral fillers other than precipitated silica and talc particles (e.g., microcrystalline talc particles).
[0089] The polymer composition may include about 50 phr to about 150 phr, for example, about 75 phr to about 125 phr of styrene-butadiene rubber and / or butadiene rubber; about 20 phr to about 55 phr, for example, about 30 phr to about 45 phr of precipitated silica; and about 8 phr to about 55 phr, for example, about 10 phr to about 50 phr, or about 12 phr to about 48 phr of talc particles (e.g., microcrystalline talc particles). The polymer composition may further include about 0.5 phr to about 5 phr, for example, about 1 phr to about 3 phr of a surface treatment agent (e.g., a silane-based surface treatment agent). The polymer composition may not include mineral fillers other than precipitated silica and talc particles (e.g., microcrystalline talc particles).
[0090] The polymer composition may include an elastomer (e.g., rubber) and may have a t measured using a rotorless cure tester according to ISO 6502 (Part 3) for about 0.5 minutes or more, e.g., about 1 minute or more, or about 2 minutes or more. 90 The polymer composition may have a vulcanization time (i.e., time to 90% vulcanization) of about 30 minutes or less, e.g., about 20 minutes or less, or about 10 minutes or less, about 5 minutes or less, or about 3 minutes or less, as measured using a rotorless vulcanization tester according to ISO 6502 (Part 3). 90The polymer composition may include an elastomer (e.g., rubber) and may have a vulcanization time of about 0.5 to about 30 minutes, e.g., about 0.5 to about 20 minutes, or about 0.5 to about 10 minutes, or about 1 to about 5 minutes, or about 1 to about 3 minutes, or about 2 to about 10 minutes, or about 2 to about 5 minutes, or about 2 to about 3 minutes, as measured using a rotorless vulcanization tester according to ISO 6502 (Part 3). 90 It may have a vulcanization time.
[0091] The polymer composition may have a crosslink density of about 5 or more, for example, about 6 or more, or about 7 or more, or about 8 or more, or about 9 or more, or about 10 or more, or about 12 or more, or about 14 or more, or about 15 or more, or about 16 or more, or about 18 or more, or about 20 or more, or about 30 or more, or about 35 or more, or about 40 or more, or about 41 or more, or about 42 or more, or about 45 or more, or about 46 or more, as measured using a rotorless vulcanization tester according to ISO 6502 (Part 3). The polymer composition may have a crosslink density, measured using a rotorless vulcanization tester according to ISO 6502 (Part 3), of about 55 or less, for example, about 50 or less, or about 47 or less, or about 46 or less, or about 43 or less, or about 42 or less, or about 41 or less, or about 30 or less, or about 20 or less, or about 19 or less, or about 18 or less, or about 17 or less, or about 16 or less, or about 15 or less, or about 14 or less, or about 13 or less, or about 12 or less, or about 11 or less, or about 10 or less, or about 9 or less, or about 8 or less.The polymer composition may have a viscosity of about 5 to about 55, for example, about 6 to about 55, or about 7 to about 55, or about 8 to about 55, or about 9 to about 55, or about 10 to about 55, or about 12 to about 55, or about 14 to about 55, or about 15 to about 55, or about 16 to about 55, or about 18 to about 55, or about 20 to about 55, or about 30 to about 55, or about 35 to about 55, about 40 to about 55, or about 41 to about 55, or about 42 to about 55, or about 45 to about 55, or about 46 to about 55, or about 35 to about 50, or about 40 to about 50, or about 41 to about 50, or about 42 to about 50, or about 45 to about 50, or about 46 to about 50, or about 35 to about 47, or about 40 to about 47, or about 41 to about 47, or about 42 to about 47, or about 45 to about 47, or about 46 to about 47, or about 35 to about 46, or about 40 to about 46, or about 41 to about 46, or about 42 to about 46, or about 45 to about 46, or about 35 to about 43, or about 40 to about 43, or about 41 to about 43, or about 42 to about 43, or about 35 to about 42, or about 40 to about 42, or about 41 to about 42, or about 35 to about 41, or about 40 to about 41, or about 5 to about 10, or about 6 to about 10, or about 7 to about 10, or about 8 to about 10, or about 5 to about 9, or about 6 to about 9, or about 7 to about 9, or about 10 to about 20, or about 12 to about 20, or about 14 to about 20, or about 15 to about 20, or about 16 to about 20, or about 10 to about 19, or about 12 to about 19, or about 14 to about 19, or about 15 to about 19, or about 16 to about 19, or about 10 to about 18, or about 12 to about 18, or about 14 to about 18, or about 15 to about 18, or about 16 to about 18.
[0092] The polymeric composition may have a Mooney viscosity at 100° C., measured using a shear disc viscometer according to ISO 289-1, of about 100 Mooney Units (MU) or less, e.g., about 90 MU or less, or about 80 MU or less, or about 70 MU or less, or about 60 MU or less, or about 50 MU or less, or about 38 MU or less, or about 37 MU or less, or about 35 MU or less, or about 33 MU or less. The polymeric composition may have a Mooney viscosity at 100° C., measured using a shear disc viscometer according to ISO 289-1, of about 20 MU or more, e.g., about 25 MU or more, or about 30 MU or more, or about 32 MU or more, or about 35 MU or more, or about 36 MU or more.The polymer composition has an average hydrolysis concentration of about 20MU to about 100MU, for example, about 20MU to about 90MU, or about 20MU to about 80MU, or about 20MU to about 70MU, or about 20MU to about 60MU, or about 20MU to about 50MU, about 25MU to about 90MU, or about 25MU to about 80MU, or about 25MU to about 70MU, or about 25MU to about 60MU, or about 25MU to about 50MU, about 30MU to about 90MU, or about 30MU to about 80MU, or about 30MU to about 70MU, or about 30MU to about 60MU. 0MU, or about 30MU to about 50MU, about 35MU to about 90MU, or about 35MU to about 80MU, or about 35MU to about 70MU, or about 35MU to about 60MU, or about 35MU to about 50MU, about 40MU to about 90MU, or about 40MU to about 80MU, or about 40MU to about 70MU, or about 40MU to about 60MU, or about 40MU to about 50MU, about 25MU to about 50MU, or about 30MU to about 50MU, or about 32MU to about 50MU, or about 35MU to about 50MU, or about 36 MU to about 50MU, or about 20MU to about 40MU, or about 25MU to about 40MU, or about 30MU to about 40MU, or about 32MU to about 40MU, or about 35MU to about 40MU, or about 36MU to about 40MU, or about 20MU to about 38MU, or about 25MU to about 38MU, or about 30MU to about 38MU, or about 32MU to about 38MU, or about 35MU to about 38MU, or about 36MU to about 38MU, or about 20MU to about 37MU, or about 25MU to about 37MU, or about 30MU The polymer may have a Mooney viscosity at 100° C., measured using a shear disc viscometer according to ISO 289-1, of from about 37 MU to about 37 MU, or from about 32 MU to about 37 MU, or from about 35 MU to about 37 MU, or from about 36 MU to about 37 MU, or from about 20 MU to about 35 MU, or from about 25 MU to about 35 MU, or from about 30 MU to about 35 MU, or from about 32 MU to about 35 MU, or from about 20 MU to about 33 MU, or from about 25 MU to about 33 MU, or from about 30 MU to about 33 MU, or from about 32 MU to about 33 MU.
[0093] The polymeric composition may have a storage modulus G' (of complex dynamic modulus G = G' + iG'') at 150% elongation obtained using a moving die rheometer according to ISO 13145 of about 15 kPa or more, e.g., about 20 kPa or more. The polymeric composition may have a storage modulus G' at 150% elongation obtained using a moving die rheometer according to ISO 13145 of about 50 kPa or less, e.g., about 40 kPa or less, or about 35 kPa or less, or about 32 kPa or less. The polymer composition may have a storage modulus G' at 150% elongation, obtained using a moving die rheometer according to ISO 13145, of about 15 kPa to about 50 kPa, e.g., about 15 kPa to about 40 kPa, or about 15 kPa to about 35 kPa, or about 15 kPa to about 32 kPa, or about 20 kPa to about 50 kPa, or about 20 kPa to about 40 kPa, or about 20 kPa to about 35 kPa, or about 20 kPa to about 32 kPa.
[0094] The polymer composition may have a storage modulus G' (of complex dynamic modulus G = G' + iG'') measured after curing at 60°C at 1 Hz obtained using a moving die rheometer according to ISO 13145 of about 50 kPa or more, e.g., about 75 kPa or more, or about 100 kPa or more, or about 200 kPa or more, or about 300 kPa or more. The polymer composition may have a storage modulus G' (of complex dynamic modulus G = G' + iG'') measured after curing at 60°C at 1 Hz obtained using a moving die rheometer according to ISO 13145 of about 1000 kPa or less, for example, about 900 kPa or less, or about 800 kPa or less, or about 700 kPa or less, or about 600 kPa or less, or about 500 kPa or less, or about 400 kPa or less, or about 350 kPa or less, or about 300 kPa or less, or about 200 kPa or less, or about 150 kPa or less. The polymer composition may have a storage modulus G' (of complex dynamic modulus G=G'+iG'') measured after curing at 60° C. at 1 Hz obtained using a moving die rheometer according to ISO 13145 of from about 50 kPa to about 1000 kPa, e.g., from about 100 kPa to about 400 kPa, or from about 100 kPa to about 350 kPa, or from about 250 kPa to about 400 kPa, or from about 300 kPa to about 400 kPa, or from about 100 kPa to about 200 kPa.
[0095] The polymer composition may have a loss modulus G'' (of complex dynamic modulus G=G'+iG'') measured after curing at 60° C. at 1 Hz obtained using a moving die rheometer according to ISO 13145 of about 10 kPa or more, e.g., about 20 kPa or more, or about 30 kPa or more, or about 40 kPa or more, or about 50 kPa or more, or about 100 kPa or more, or about 120 kPa or more, or about 130 kPa or more, or about 140 kPa or more, or about 150 kPa or more, or about 160 kPa or more. The polymer composition may have a loss modulus G'' (of complex dynamic modulus G=G'+iG'') measured after curing at 60° C. at 1 Hz obtained using a moving die rheometer according to ISO 13145 of about 400 kPa or less, for example, about 300 kPa or less, or about 200 kPa or less, or about 180 kPa or less, or about 170 kPa or less, or about 160 kPa or less, or about 150 kPa or less, or about 140 kPa or less, or about 100 kPa or less, or about 75 kPa or less, or about 60 kPa or less, or about 50 kPa or less. The polymer composition may have a storage modulus G'' (complex dynamic modulus G=G'+iG'') measured after curing at 60° C. at 1 Hz obtained using a moving die rheometer according to ISO 13145 of about 10 kPa to about 400 kPa, or about 10 kPa to about 100 kPa, or about 10 kPa to about 75 kPa, or about 20 kPa to about 60 kPa, or about 30 kPa to about 60 kPa, or about 30 kPa to about 40 kPa to about 60 kPa, or about 100 kPa to about 200 kPa, or about 120 kPa to about 180 kPa, or about 130 kPa to about 170 kPa.
[0096] The polymeric composition may have a tan δ (defined as the ratio of G″ to G′) measured after curing at 60° C. at 1 Hz obtained using a moving die rheometer according to ISO 13145 having a magnitude of about 0.80 or less, or about 0.70 or less, or about 0.60 or less, or about 0.50 or less, or about 0.40 or less. The polymeric composition may have a tan δ (defined as the ratio of G″ to G′) measured after curing at 60° C. at 1 Hz obtained using a moving die rheometer according to ISO 13145 having a magnitude of about 0.10 or more, such as about 0.20 or more, or about 0.30 or more, or about 0.40 or more, or about 0.50 or more. The polymer composition may have a tan δ (defined as the ratio of G″ to G′) measured after curing at 60° C. at 1 Hz obtained using a moving die rheometer according to ISO 13145 having a magnitude of about 0.10 to about 0.80, e.g., about 0.20 to about 0.70, or about 0.30 to about 0.60, or about 0.30 to about 0.40, or about 0.40 to about 0.60, or about 0.40 to about 0.50.
[0097] The polymer composition has a viscosity of about 1.0 kg / m 3 More than, for example, about 1.10 kg / m 3 or more, or about 1.20 kg / m 3 or more, or about 1.25 kg / m 3 or more, or about 1.30 kg / m 3 or more, or about 1.33 kg / m 3 The polymer composition may have a density, measured in accordance with ISO 2781, of about 1.50 kg / m or more. 3 For example, about 1.45 kg / m 3 or less than 1.40 kg / m 3 or less than 1.35 kg / m 3 or less than 1.34 kg / m 3 The polymer composition may have a density, measured according to ISO 2781, of about 1.0 kg / m 3 ~Approx. 1.50kg / m 3 , for example, about 1.10 kg / m 3 ~Approx. 1.50kg / m 3 , or about 1.20 kg / m3 ~Approx. 1.50kg / m 3 , or about 1.0 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.10 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.0 kg / m 3 ~Approx. 1.35kg / m 3 , 1.10kg / m 3 ~Approx. 1.35kg / m 3 , 1.20kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.50kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.50kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.50kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.45kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.45kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.45kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.45kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.33 kg / m3 ~Approx. 1.35kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.34kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.34kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.34kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.34kg / m 3 The material may have a density, measured in accordance with ISO 2781, of 1000 ppm.
[0098] The polymer composition has a modulus of elasticity at 50% elongation (i.e., tensile modulus), M, measured according to ISO 37, of about 0.5 MPa or more, e.g., about 0.8 MPa or more, or about 0.9 MPa or more, or about 1.0 MPa or more, or about 1.1 MPa or more, or about 1.2 MPa or more. 50 The polymeric composition may have a modulus at 50% elongation (i.e., tensile modulus), M, measured according to ISO 37, of about 1.7 MPa or less, e.g., about 1.6 MPa or less, or about 1.5 MPa or less, or about 1.4 MPa or less, or about 1.3 MPa or less, or about 1.2 MPa or less, or about 1.1 MPa or less. 50The polymer composition may have a pressure of about 0.5 MPa to about 1.7 MPa, for example, about 0.5 MPa to about 1.6 MPa, or about 0.5 MPa to about 1.5 MPa, or about 0.8 MPa to about 1.7 MPa, or about 0.8 MPa to about 1.6 MPa, or about 0.8 MPa to about 1.5 MPa, or about 0.9 MPa to about 1.7 MPa, or about 0.9 MPa to about 1.6 MPa, or about 0.9 MPa to about 1.5 MPa, or about 1.0 MPa to about 1.5 MPa, or about 1.1 MPa to about 1.5 MPa, or about 1.2 MPa to about 1.5 MPa, or about 0.5 MPa to about 1.4 MPa, or about 0.8 MPa to about 1.4 MPa, or about 0.9 MPa to about 1.4 MPa, or about 1.0 MPa to about 1.4 MPa, or about 1.1 MPa to about 1.4 MPa, or about 1.2 MPa to about 1.4 MPa, or about 0.5 MPa to about 1.3 MPa, or about 0.8 MPa to about 1.3 MPa, or about 0.9 MPa to about 1.3 MPa, or about 1.0 MPa to about 1.3 MPa, or about 1.1 MPa to about 1.3 MPa, or about 1.2 MPa to about 1.3 MPa, or about 0.5 MPa to about 1.2 MPa, or about 0.8 MPa to about 1.2 MPa, or about 0.9 MPa to about 1.2 MPa, or about 1.0 MPa to about 1.2 MPa, or about 1.1 MPa to about 1.2 MPa, or about 0.5 MPa to about 1.1 MPa, or about 0.8 MPa to about 1.1 MPa, or about 0.9 MPa to about 1.1 MPa, or about 1.0 MPa to about 1.1 MPa 50 may have:
[0099] The polymer composition has a modulus at 100% elongation (i.e., tensile modulus), M, measured according to ISO 37, of about 1.0 MPa or more, e.g., about 1.2 MPa or more, or about 1.4 MPa or more, or about 1.5 MPa or more, or about 1.6 MPa or more, or about 1.8 MPa or more. 100 The polymeric composition may have a modulus at 100% elongation (i.e., tensile modulus), M, measured according to ISO 37, of about 2.5 MPa or less, e.g., about 2.4 MPa or less, or about 2.2 MPa or less, or about 2.0 MPa or less, or about 1.9 MPa or less, or about 1.8 MPa or less, or about 1.6 MPa or less. 100The polymer composition may have a pressure of about 1.0 MPa to about 2.5 MPa, for example, about 1.2 MPa to about 2.5 MPa, or about 1.4 MPa to about 2.5 MPa, or about 1.5 MPa to about 2.5 MPa, or about 1.6 MPa to about 2.5 MPa, or about 1.8 MPa to about 2.5 MPa, or about 1.0 MPa to about 2.4 MPa, or about 1.2 MPa to about 2.4 MPa, or about 1.4 MPa to about 2.4 MPa, or about 1.5 MPa to about 2.4 MPa. , or about 1.6 MPa to about 2.4 MPa, or about 1.8 MPa to about 2.4 MPa, or about 1.0 MPa to about 2.2 MPa, or about 1.2 MPa to about 2.2 MPa, or about 1.4 MPa to about 2.2 MPa, or about 1.5 MPa to about 2.2 MPa, or about 1.6 MPa to about 2.2 MPa, or about 1.8 MPa to about 2.2 MPa, or about 1.0 MPa to about 2.0 MPa, or about 1.2 MPa to about 2.0 MPa, or about 1.4 M Pa to about 2.0 MPa, or about 1.5 MPa to about 2.0 MPa, or about 1.6 MPa to about 2.0 MPa, or about 1.8 MPa to about 2.0 MPa, or about 1.0 MPa to about 1.9 MPa, or about 1.2 MPa to about 1.9 MPa, or about 1.4 MPa to about 1.9 MPa, or about 1.5 MPa to about 1.9 MPa, or about 1.6 MPa to about 1.9 MPa, or about 1.8 MPa to about 1.9 MPa, or about 1.0 MPa to about 1.8 M MPa, or about 1.2 MPa to about 1.8 MPa, or about 1.4 MPa to about 1.8 MPa, or about 1.5 MPa to about 1.8 MPa, or about 1.6 MPa to about 1.8 MPa, or about 1.0 MPa to about 1.6 MPa, or about 1.2 MPa to about 1.6 MPa, or about 1.4 MPa to about 1.6 MPa, or about 1.5 MPa to about 1.6 MPa 100 may have:
[0100] The polymeric composition has a modulus at 300% elongation (i.e., tensile modulus), M, measured according to ISO 37, of about 1.5 MPa or more, e.g., about 1.6 MPa or more, or about 2.0 MPa or more, or about 2.2 MPa or more, or about 2.4 MPa or more, or about 2.5 MPa or more, or about 2.6 MPa or more, or about 2.8 MPa or more, or about 2.9 MPa or more, or about 3.0 MPa or more, or about 3.1 MPa or more, or about 3.2 MPa or more, or about 3.3 MPa or more. 300 The polymeric composition may have a modulus at 300% elongation (i.e., tensile modulus), M, measured according to ISO 37, of about 9.0 MPa or less, e.g., about 8.5 MPa or less, or about 8.0 MPa or less, or about 7.5 MPa or less, or about 7.0 MPa or less, or about 6.5 MPa or less, or about 6.0 MPa or less, or about 5.5 MPa or less, or about 5.0 MPa or less, or about 4.5 MPa or less, or about 4.0 MPa or less, or about 3.5 MPa or less, or about 3.4 MPa or less, or about 3.3 MPa or less, or about 3.2 MPa or less, or about 3.1 MPa or less, or about 3.0 MPa or less, or about 2.9 MPa or less, or about 2.7 MPa or less, or about 2.6 MPa or less. 300The polymer composition may have a pressure of about 1.5 MPa to about 9.0 MPa, for example, about 1.5 MPa to about 8.5 MPa, or about 1.5 MPa to about 8.0 MPa, or about 1.5 MPa to about 7.5 MPa, or about 1.5 MPa to about 7.0 MPa, or about 1.5 MPa to about 6.5 MPa, or about 1.5 MPa to about 6.0 MPa, or about 1.5 MPa to about 5.5 MPa, or about 1.5 MPa to about 5.0 MPa, for example, about 1.5 MPa to about 4.5 MPa, or about 1.5 MPa to about 4.0 MPa, or about 1.5 MPa to about 3.5 MPa, or about 1.5 MPa to about 3.4 MPa, or About 1.5 MPa to about 3.3 MPa, or about 1.5 MPa to about 3.2 MPa, or about 1.5 MPa to about 3.1 MPa, or about 1.5 MPa to about 3.0 MPa, or about 1.5 MPa to about 2.9 MPa, or about 1.5 MPa to about 2.7 MPa, or about 1.5 MPa to about 2.6 MPa, or about 1.6 MPa to about 5.5 MPa, or about 1.6 MPa to about 5.0 MPa, or about 1.6 MPa to about 4.5 MPa, or about 1.6 MPa to about 4.0 MPa, or about 1.6 MPa to about 3.5 MPa, or about 1.6 MPa to about 3.4 MPa, or about 1.6 MPa to about 3.3 M Pa, or about 1.6 MPa to about 3.2 MPa, or about 1.6 MPa to about 3.1 MPa, or about 1.6 MPa to about 3.0 MPa, or about 1.6 MPa to about 2.9 MPa, or about 1.6 MPa to about 2.7 MPa, or about 1.6 MPa to about 2.6 MPa, or about 2.0 MPa to about 5.5 MPa, or about 2.0 MPa to about 5.0 MPa, or about 2.0 MPa to about 4.5 MPa, or about 2.0 MPa to about 4.0 MPa, or about 2.0 MPa to about 3.5 MPa, or about 2.0 MPa to about 3.4 MPa, or about 2.0 MPa to about 3.3 MPa, or about 2.0 MPa to about About 3.2 MPa, or about 2.0 MPa to about 3.1 MPa, or about 2.0 MPa to about 3.0 MPa, or about 2.0 MPa to about 2.9 MPa, or about 2.0 MPa to about 2.7 MPa, or about 2.0 MPa to about 2.6 MPa, or about 2.2 MPa to about 4.5 MPa, or about 2.4 MPa to about 4.5 MPa, or about 2.5 MPa to about 4.5 MPa, or about 2.6 MPa to about 4.5 MPa, or about 2.8 MPa to about 4.5 MPa, or about 2.9 MPa to about 4.5 MPa, or about 3.0 MPa to about 4.5 MPa, or about 3.1 MPa to about 4.5 MPa, or about 3.2 MPa to about 4.5 MPa, or about 3.3 MPa to about 4.5 MPa, or about 2.0 MPa to about 4.0 MPa, or about 2.2 MPa to about 4.0 MPa, or about 2.4 MPa to about 4.0 MPa, or about 2.5 MPa to about 4.0 MPa, or about 2.6 MPa to about 4.0 MPa, or about 2.8 MPa to about 4.0 MPa, or about 2.9 MPa to about 4.0 MPa, or about 3.0 MPa to about 4.0 MPa, or about 3.1 MPa to about 4.0 MPa, or about 3.2 MPa to about 4.0 MPa, or about 3.3 MPa to about 4.0 MPa, or about 2.0 MPa to about 3.5 MPa, or about 2.2MPa to about 3.5MPa, or about 2.4MPa to about 3.5MPa, or about 2.5MPa to about 3.5MPa, or about 2.6MPa to about 3.5MPa, or about 2.8MPa to about 3.5MPa, or about 2.9MPa to about 3.5MPa, or about 3.0MPa to about 3.5MPa, or about 3.1MPa to about 3.5MPa, or about 3.2MPa to about 3.5MPa, or about 3.3MPa to about 3.5MPa, or about 2.0MPa to about 3.4MPa, or about 2.2MPa to about 3.4MPa, or about 2.4MPa to about 3.4MPa, or about 2.5MPa to about 3.4MPa, or about 2.6MPa to about 3.4MPa, or about 2.8MPa to about 3.4MPa, or about 2.9MPa to about 3.4MPa, or about 3.0MPa to about 3.4MPa, or about 3.1MPa to about 3.4MPa, or about 3.2MPa to about 3.4MPa, or about 3.3MPa to about 3.4MPa, or about 2.0MPa to about 3.3MPa, or about 2.2MPa to about 3.3MPa, or about 2.4MPa to about 3.3MPa, or about 2.5MPa to about 3.3MPa, or about 2.6MPa to about 3.3MPa, or about 2.8MPa to about 3.3MPa, or about 2.9MPa to about 3.3MPa Pa, or about 3.0 MPa to about 3.3 MPa, or about 3.1 MPa to about 3.3 MPa, or about 3.2 MPa to about 3.3 MPa, or about 2.0 MPa to about 3.2 MPa, or about 2.2 MPa to about 3.2 MPa, or about 2.4 MPa to about 3.2 MPa, or about 2.5 MPa to about 3.2 MPa, or about 2.6 MPa to about 3.2 MPa, or about 2.8 MPa to about 3.2 MPa, or about 2.9 MPa to about 3.2 MPa, or about 3.0 MPa to about 3.2 MPa, or about 3.1 MPa to about 3.2 MPa, or about 2.0 MPa to about 3.1 MPa, or about 2.2 MPa to about 3.1 MPa, or about 2.4 MPa to about 3.1 MPa, or about 2.5 MPa to about 3.1 MPa, or about 2.6 MPa to about 3.1 MPa, or about 2.8 MPa to about 3.1 MPa, or about 2.9 MPa to about 3.1 MPa, or about 3.0 MPa to about 3.1 MPa, or about 2.0 MPa to about 3.0 MPa, or about 2.2 MPa to about 3.0 MPa, or about 2.4 MPa to about 3.0 MPa, or about 2.5 MPa to about 3.0 MPa, or about 2.6 MPa to about 3.0 MPa, or about 2.8 MPa to about 3.0 MPa, or about 2.9 MPa to about 3.0 MPa, or about 2.0 MPa to about 2.9 MPa, or about 2.2 MPa to about 2.9 MPa, or about 2.4 MPa to about 2.9 MPa, or about 2.5 MPa to about 2.9 MPa, or about 2.6 MPa to about 2.9 MPa, or about 2.8 MPa to about 2.9 MPa, or about 2.0 MPa to about 2.7 MPa, or about 2.2 MPa to about 2.7 MPa, or about 2.4 MPa to about 2.7 MPa, or about 2.5 MPa to about 2.7 MPa, or about 2.6 MPa to about 2.7 MPa, or about 2.0 MPa to about 2.6 MPa, or about 2.2 MPa to about 2.6 MPa, or about 2.4 MPa to about 2.6 MPa, or about 2.5 MPa to about 2.6 MPa 300 may have:
[0101] The polymer composition has a reinforcement index, M, of about 1.45 or more, e.g., about 1.50 or more, or about 1.60 or more, or about 1.62 or more, or about 1.70 or more, or about 1.80 or more, or about 1.90 or more. 300 / M 100 The polymer composition may have a reinforcement index, M, of about 3.10 or less, e.g., about 3.0 or less, or about 2.90 or less, or about 2.80 or less, or about 2.70 or less, or about 2.60 or less, or about 2.40 or less, or about 2.50 or less, or about 2.30 or less, or about 2.10 or less, or about 2.00 or less, or about 1.94 or less, or about 1.90 or less, or about 1.80 or less, or about 1.70 or less. 300 / M 100The polymer composition may have a molecular weight of about 1.45 to about 3.10, for example, about 1.45 to about 3.0, or about 1.45 to about 2.90, or about 1.45 to about 2.80, or about 1.45 to about 2.70, or about 1.45 to about 2.60, or about 1.45 to about 2.40, or about 1.45 to about 2.50, or about 1.45 to about 2.30, or about 1.45 to about 2.10, or about 1.45 to about 2.00, or about 1.45 to about 1.94, or about 1.45 to about 1.90, or about 1.45 to about 1.80, or about 1.45 to about 1.70, or about 1.50 to about 3.10, or about 1.50 to about 3.0, or about 1.50 to about 2.90, or about 1.50 to about 2.80, or about 1.50 to about 2.70, or about 1.50 to about 2.60, or about 1.50 to about 2.40, or about 1.50 to about 2.50, or about 1.50 to about 2.30, or about 1.50 to about 2.10, or about 1.50 to about 2.00, or about 1.50 to about 1.94, or about 1.50 to about 1.90, or about 1.50 to about 1.80, or about 1.50 to about 1.70, or about 1.50 to about 2.50, or about 1.60 to about 2.50, or about 1.62 to about 2.50, or about 1.70 to about 2.50, or about 1.80 to about 2.50 , or about 1.90 to about 2.50, or about 1.50 to about 2.30, or about 1.60 to about 2.30, or about 1.62 to about 2.30, or about 1.70 to about 2.30, or about 1.80 to about 2.30, or about 1.90 to about 2.30, or about 1.50 to about 2.10, or about 1.60 to about 2.10, or about 1.62 to about 2.10, or about 1.70 to about 2.10, or about 1.80 to about 2.10, or about 1.90 to about 2.10, or about 1.50 to about 2.00, or about 1.60 to about 2.00, or about 1.62 to about 2.00, or about 1.70 to about 2.00, or about 1.80 to about 2.00, or about 1.90 to about 2.00, or about 1.50 to about 1.94, or about 1.60 to about 1.94, or about 1.62 to about 1.94, or about 1.70 to about 1.94, or about 1.80 to about 1.94, or about 1.90 to about 1.94, or about 1.50 to about 1.90, or about 1.60 to about 1.90, or about 1.62 to about 1.90, or about 1.70 to about 1.90, or about 1.80 to about 1.90, or about 1.50 to about 1.80, or about 1.60 to about 1.80, or about 1.62 to about 1.80, or about 1.70 to about 1.80, or about 1.50 to about 1.70, or about 1.60 to about 1.70, or about 1.62 to about 1.70, reinforcement index M. 300 / M 100 may have:
[0102] The polymeric composition may have a tensile strength, measured according to ISO 37, of about 3 MPa or more, for example, about 4 MPa or more, or about 5 MPa or more, or about 6 MPa or more, or about 7 MPa or more, about 8 MPa or more, or about 9 MPa or more, or about 9.3 MPa or more, or about 10 MPa or more. The polymeric composition may have a tensile strength, measured according to ISO 37, of about 15 MPa or less, for example, about 12 MPa or less, or about 11 MPa or less, or about 10.8 MPa or less, or about 10 MPa or less, or about 8 MPa or less, or about 7 MPa or less, or about 6 MPa or less, or about 5 MPa or less. The polymer composition may have a pressure of from about 3 MPa to about 15 MPa, for example, from about 4 MPa to about 15 MPa, or from about 5 MPa to about 15 MPa, or from about 6 MPa to about 15 MPa, or from about 6 MPa to about 12 MPa, or from about 6 MPa to about 11 MPa, or from about 6 MPa to about 10.8 MPa, or from about 6 MPa to about 10 MPa, or from about 8 MPa to about 15 MPa, or from about 9 MPa to about 15 MPa, or from about 9.3 MPa to about 15 MPa, or from about 10 MPa to about 15 MPa, or from about 8 MPa to about 12 MPa, or from about 9 MPa to about 12 MPa, or from about 9.3 MPa to about 15 MPa. The material may have a tensile strength, measured according to ISO 37, of about 10 MPa to about 12 MPa, or about 8 MPa to about 11 MPa, or about 9 MPa to about 11 MPa, or about 9.3 MPa to about 11 MPa, or about 10 MPa to about 11 MPa, or about 8 MPa to about 10.8 MPa, or about 9 MPa to about 10.8 MPa, or about 9.3 MPa to about 10.8 MPa, or about 10 MPa to about 10.8 MPa, or about 8 MPa to about 10 MPa, or about 9 MPa to about 10 MPa, or about 9.3 MPa to about 10 MPa.
[0103] The polymeric composition may have an elongation at break, measured according to ISO 37, of about 400% or more, such as about 500% or more, or about 600% or more, or about 700% or more, or about 710% or more, or about 1000% or more. The polymeric composition may have an elongation at break, measured according to ISO 37, of about 1500% or less, such as about 1200% or less, or about 1100% or less, or about 1010% or less, or about 800% or less. The polymer composition may be from about 400% to about 1500%, for example, from about 500 to about 1500%, or from about 400% to about 600%, or from about 400% to about 500%, or from about 600% to about 1500%, or from about 700% to about 1500%, or from about 710% to about 1500%, or from about 1000% to about 1500%, or from about 500% to about 1200%, or from about 600% to about 1200%, or from about 700% to about 1200%, or from about 710% to about 1200%, or from about 1000% to about 1200%, or from about 500% to about 1100%, Or it may have an elongation at break measured in accordance with ISO 37 of about 600% to about 1100%, or about 700% to about 1100%, or about 710% to about 1100%, or about 1000% to about 1100%, or about 500% to about 1010%, or about 600% to about 1010%, or about 700% to about 1010%, or about 710% to about 1010%, or about 1000% to about 1010%, or about 500% to about 800%, or about 600% to about 800%, or about 700% to about 800%, or about 710% to about 800%.
[0104] The polymer composition may have a tear resistance, measured according to ISO 34, of about 15 N / mm or more, for example, about 16 N / mm or more, or about 17 N / mm or more, or about 18 N / mm or more, or about 19 N / mm or more, or about 20 N / mm or more, or about 25 N / mm or more, or about 29 N / mm or more, or about 30 N / mm or more. The polymer composition may have a tear resistance, measured according to ISO 34, of about 40 N / mm or less, for example, about 35 N / mm or less, or about 32 N / mm or less, or about 30 N / mm or less. The polymer composition has a stiffness of about 15 N / mm to about 40 N / mm, for example, about 16 N / mm to about 40 N / mm, or about 17 N / mm to about 40 N / mm, or about 18 N / mm to about 40 N / mm, or about 19 N / mm to about 40 N / mm, or about 20 N / mm to about 40 N / mm, or about 25 N / mm to about 40 N / mm, or about 29 N / mm to about 40 N / mm, or about 30 N / mm to about 40 N / mm, or about 20 N / mm to about 35 N / mm, or about 25 N / mm The elastic modulus may have a tear resistance, measured according to ISO 34, of about 29 N / mm to about 35 N / mm, or about 30 N / mm to about 35 N / mm, or about 20 N / mm to about 32 N / mm, or about 25 N / mm to about 32 N / mm, or about 29 N / mm to about 32 N / mm, or about 30 N / mm to about 32 N / mm, or about 20 N / mm to about 30 N / mm, or about 25 N / mm to about 30 N / mm, or about 29 N / mm to about 30 N / mm.
[0105] The polymer composition may have a Shore A hardness, measured according to ISO 7619-1, of about 30 or more, e.g., about 40 or more, or about 50 or more. The polymer composition may have a Shore A hardness, measured according to ISO 7619-1, of about 70 or less, e.g., about 60 or less, or about 55 or less, or about 52 or less. The polymer composition may have a Shore A hardness, measured according to ISO 7619-1, of about 30 to about 70, e.g., about 40 to about 70, or about 50 to about 70, or about 30 to about 60, or about 40 to about 60, or about 50 to about 60, or about 30 to about 55, or about 40 to about 55, or about 50 to about 55, or about 30 to about 52, or about 40 to about 52, or about 50 to about 52.
[0106] The polymeric composition may have a compression set, measured according to ISO 815, of about 5% or more, e.g., about 10% or more, or about 20% or more, or about 30% or more, or about 35% or more, or about 38% or more. The polymeric composition may have a compression set, measured according to ISO 815, of about 50% or less, e.g., about 45% or less, or about 43% or less, or about 30% or less, or about 20% or less, or about 15% or less, or about 10% or less. The polymer composition may have a compression set, measured according to ISO 815, of about 5% to about 50%, e.g., about 10% to about 50%, or about 5% to about 10%, or about 20% to about 50%, or about 30% to about 50%, or about 35% to about 50%, or about 38% to about 50%, or about 10% to about 45%, or about 20% to about 45%, or about 30% to about 45%, or about 35% to about 45%, or about 38% to about 45%, or about 10% to about 43%, or about 20% to about 43%, or about 30% to about 43%, or about 35% to about 43%, or about 38% to about 43%.
[0107] The polymeric composition may exhibit an abrasion amount when tested according to ISO 4649 of about 0.100 g or more, e.g., about 0.120 g or more, or about 0.150 g or more, or about 0.200 g or more, or about 0.210 g or more, or about 0.250 g or more, or about 0.300 g or more. The polymeric composition may exhibit an abrasion amount when tested according to ISO 4649 of about 0.450 g or less, e.g., about 0.425 g or less, or about 0.400 g or less, or about 0.300 g or less. The polymer composition may be from about 0.100 g to about 0.450 g, for example, from about 0.120 g to about 0.450 g, or from about 0.150 g to about 0.450 g, or from about 0.200 g to about 0.450 g, or from about 0.210 g to about 0.450 g, or from about 0.250 g to about 0.450 g, or from about 0.300 g to about 0.450 g, or from about 0.200 g to about 0.425 g, or from about 0.210 g to about 0.425 g, or from about 0.250 g to about 0.425 g, Or about 0.300g to about 0.425g, or about 0.200g to about 0.400g, or about 0.210g to about 0.400g, or about 0.250g to about 0.400g, or about 0.300g to about 0.400g, or about 0.200g to about 0.300g, or about 0.210g to about 0.300g, or about 0.250g to about 0.300g, or about 0.300g to about 0.300g.
[0108] The polymer composition is about 0.10 cm 3 More than, for example, about 0.15 cm 3 More than 0.25 cm 3 More than or equal to 0.30 cm 3 The polymer composition may have an abrasion resistance of about 0.60 cm or more according to ISO 4649. 3 Less than, for example, about 0.55 cm 3 Less than or equal to 0.50 cm 3 Less than or equal to 0.40 cm 3 Less than or equal to 0.35 cm 3 Less than or equal to 0.30 cm 3 Less than or equal to 0.25 cm 3 Less than or equal to 0.20 cm 3 The polymer composition may have an abrasion resistance according to ISO 4649 of about 0.10 cm3 ~about 0.60cm 3 , for example, about 0.15 cm 3 ~about 0.60cm 3 , or about 0.20 cm 3 ~about 0.60cm 3 , or about 0.25 cm 3 ~about 0.60cm 3 , or about 0.30 cm 3 ~about 0.60cm 3 , or about 0.20 cm 3 ~ approx. 0.55cm 3 , or about 0.25 cm 3 ~ approx. 0.55cm 3 , or about 0.30 cm 3 ~ approx. 0.55cm 3 , about 0.20cm 3 ~about 0.50cm 3 , or about 0.25 cm 3 ~about 0.50cm 3 , or about 0.30 cm 3 ~about 0.50cm 3 It may have abrasion resistance according to ISO 4649.
[0109] The polymer composition includes (a) an elastomer (e.g., rubber) and has a t measured using a rotorless cure tester according to ISO 6502 (Part 3) of about 0.5 to about 30 minutes, e.g., about 0.5 to about 20 minutes, or about 0.5 to about 10 minutes, or about 1 to about 5 minutes, or about 1 to about 3 minutes, or about 2 to about 10 minutes, or about 2 to about 5 minutes, or about 2 to about 3 minutes. 90(b) a vulcanization time of about 10 to about 55, e.g., about 20 to about 55, or about 30 to about 55, or about 35 to about 55, about 40 to about 55, or about 41 to about 55, or about 42 to about 55, or about 45 to about 55, or about 46 to about 55, or about 35 to about 50, or about 40 to about 50, or about 41 to about 50, or about 42 to about 50, or about 45 to about 50, or about 46 to about 50, or about 35 to about 47, or about 40 to about 47, or about 41 to about 47, or about 42 to about 47, or about 45 to about 47, or about 46 to about 47, or about 35 to about 46, or about 40 to about 46, or about 41 to about 46, or about 42 to about 46, or about 45 to about 46, or about 35 to about 43, or about 40 to about 43, or about 41 to about 43, or about 42 to about 43, or about 35 to about 42, or about 40 to about 42, or about 41 to about 42, or about 35 to about 41, or about 40 to about 41;(c) about 20MU to about 100MU, for example, about 20MU to about 90MU, or about 20MU to about 80MU, or about 20MU to about 70MU, or about 20MU to about 60MU, or about 20MU to about 50MU, about 25MU to about 90MU, or about 25MU to about 80MU, or about 25MU to about 70MU, or about 25MU to about 60MU, or about 25MU to about 50MU, about 30MU to about 90MU, or about 30MU to about 80MU, or about 30MU to about 70MU, or about 30MU to about 60MU, or is about 30MU to about 50MU, about 35MU to about 90MU, or about 35MU to about 80MU, or about 35MU to about 70MU, or about 35MU to about 60MU, or about 35MU to about 50MU, about 40MU to about 90MU, or about 40MU to about 80MU, or about 40MU to about 70MU, or about 40MU to about 60MU, or about 40MU to about 50MU, about 25MU to about 50MU, or about 30MU to about 50MU, or about 32MU to about 50MU, or about 35MU to about 50MU, or about 36MU to about about 50MU, or about 20MU to about 40MU, or about 25MU to about 40MU, or about 30MU to about 40MU, or about 32MU to about 40MU, or about 35MU to about 40MU, or about 36MU to about 40MU, or about 20MU to about 38MU, or about 25MU to about 38MU, or about 30MU to about 38MU, or about 32MU to about 38MU, or about 35MU to about 38MU, or about 36MU to about 38MU, or about 20MU to about 37MU, or about 25MU to about 37MU, or about 30MU to about 37MU, or about 32MU to about 37MU, or about 35MU to about 37MU, or about 36MU to about 37MU, or about 20MU to about 35MU, or about 25MU to about 35MU, or about 30MU to about 35MU, or about 32MU to about 35MU, or about 20MU to about 33MU, or about 25MU to about 33MU, or about 30MU to about 33MU, or about 32MU to about 33MU;(d) a storage modulus G' (of complex dynamic modulus G = G' + iG'') at 150% elongation, obtained using a moving die rheometer according to ISO 13145, of about 15 kPa to about 50 kPa, e.g., about 15 kPa to about 40 kPa, or about 15 kPa to about 35 kPa, or about 15 kPa to about 32 kPa, or about 20 kPa to about 50 kPa, or about 20 kPa to about 40 kPa, or about 20 kPa to about 35 kPa, or about 20 kPa to about 32 kPa; (e) about 1.0 kg / m; 3 ~Approx. 1.50kg / m 3 , for example, about 1.10 kg / m 3 ~Approx. 1.50kg / m 2 , or about 1.20 kg / m 3 ~Approx. 1.50kg / m 3 , or about 1.0 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.10 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.0 kg / m 3 ~Approx. 1.35kg / m 3 , 1.10kg / m 3 ~Approx. 1.35kg / m 3 , 1.20kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.50kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.50kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.50kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.45kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.45kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.45kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.45kg / m 3 , or about 1.20 kg / m 3~Approx. 1.40kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.34kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.34kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.34kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.34kg / m 3(f) a density, measured according to ISO 2781, of from about 0.5 MPa to about 1.7 MPa, for example, from about 0.5 MPa to about 1.6 MPa, or from about 0.5 MPa to about 1.5 MPa, or from about 0.8 MPa to about 1.7 MPa, or from about 0.8 MPa to about 1.6 MPa, or from about 0.8 MPa to about 1.5 MPa, or from about 0.9 MPa to about 1.7 MPa, or from about 0.9 MPa to about 1.6 MPa, or from about 0.9 MPa to about 1.5 MPa, or from about 1.0 MPa to about 1.5 MPa, or from about 1.1 MPa to about 1.5 MPa, or from about 1.2 MPa to about 1.5 MPa, or from about 0.5 MPa to about 1.4 MPa, or from about 0.8 MPa to about 1.4 MPa, or from about 0.9 MPa to about 1.4 MPa, or from about 1.0 MPa to about 1.4 MPa, or from about 1.1 MPa to about 1.4 MPa, or about 1.2 MPa to about 1.4 MPa, or about 0.5 MPa to about 1.3 MPa, or about 0.8 MPa to about 1.3 MPa, or about 0.9 MPa to about 1.3 MPa, or about 1.0 MPa to about 1.3 MPa, or about 1.1 MPa to about 1.3 MPa, or about 1.2 MPa to about 1.3 MPa, or about 0.5 MPa to about 1.2 MPa, or about 0.8 MPa to about 1.2 MPa, or about 0.9 MPa to about 1.2 MPa, or about 1.0 MPa to about 1.2 MPa, or about 1.1 MPa to about 1.2 MPa, or about 0.5 MPa to about 1.1 MPa, or about 0.8 MPa to about 1.1 MPa, or about 0.9 MPa to about 1.1 MPa, or about 1.0 MPa to about 1.1 MPa 50(g) about 1.0 MPa to about 2.5 MPa, for example, about 1.2 MPa to about 2.5 MPa, or about 1.4 MPa to about 2.5 MPa, or about 1.5 MPa to about 2.5 MPa, or about 1.6 MPa to about 2.5 MPa, or about 1.8 MPa to about 2.5 MPa, or about 1.0 MPa to about 2.4 MPa, or about 1.2 MPa to about 2.4 MPa, or about 1.4 MPa to about 2.4 MPa, or about 1.5 MPa to about 2.4 MPa. , or about 1.6 MPa to about 2.4 MPa, or about 1.8 MPa to about 2.4 MPa, or about 1.0 MPa to about 2.2 MPa, or about 1.2 MPa to about 2.2 MPa, or about 1.4 MPa to about 2.2 MPa, or about 1.5 MPa to about 2.2 MPa, or about 1.6 MPa to about 2.2 MPa, or about 1.8 MPa to about 2.2 MPa, or about 1.0 MPa to about 2.0 MPa, or about 1.2 MPa to about 2.0 MPa, or about 1.4 M Pa to about 2.0 MPa, or about 1.5 MPa to about 2.0 MPa, or about 1.6 MPa to about 2.0 MPa, or about 1.8 MPa to about 2.0 MPa, or about 1.0 MPa to about 1.9 MPa, or about 1.2 MPa to about 1.9 MPa, or about 1.4 MPa to about 1.9 MPa, or about 1.5 MPa to about 1.9 MPa, or about 1.6 MPa to about 1.9 MPa, or about 1.8 MPa to about 1.9 MPa, or about 1.0 MPa to about 1.8 M MPa, or about 1.2 MPa to about 1.8 MPa, or about 1.4 MPa to about 1.8 MPa, or about 1.5 MPa to about 1.8 MPa, or about 1.6 MPa to about 1.8 MPa, or about 1.0 MPa to about 1.6 MPa, or about 1.2 MPa to about 1.6 MPa, or about 1.4 MPa to about 1.6 MPa, or about 1.5 MPa to about 1.6 MPa 100(h) about 1.5 MPa to about 5.5 MPa, or about 1.5 MPa to about 5.0 MPa, for example, about 1.5 MPa to about 4.5 MPa, or about 1.5 MPa to about 4.0 MPa, or about 1.5 MPa to about 3.5 MPa, or about 1.5 MPa to about 3.4 MPa, or about 1.5 MPa to about 3.3 MPa, or about 1.5 MPa to about 3.2 MPa, or about 1.5 MPa to about 3.1 MPa, or about 1.5 MPa to about 3.0 MPa, or about 1.5 MPa to about 2.9 MPa, or about 1.5 MPa to about 2.7 MPa, or about 1.5 MPa to about 2.6 MPa, or about 1.6 MPa to about 5.5 MPa, or about 1.6 MPa to about 5.0 MPa, or about 0.6MPa to about 4.5MPa, or about 1.6MPa to about 4.0MPa, or about 1.6MPa to about 3.5MPa, or about 1.6MPa to about 3.4MPa, or about 1.6MPa to about 3.3MPa, or about 1.6MPa to about 3.2MPa, or about 1.6MPa to about 3.1MPa, or about 1.6MPa to about 3.0MPa, or about 1.6MPa to about 2.9MPa, or about 1.6MPa to about 2.7MPa, or about 1.6MPa to about 2.6MPa, or about 2.0MPa to about 5.5MPa, or about 2.0MPa to about 5.0MPa, or about 2.0MPa to about 4.5MPa, or about 2.0MPa to about 4.0MPa, or about 2.0MPa to about 3.5MPa, or about 2.0 MPa to about 3.4 MPa, or about 2.0 MPa to about 3.3 MPa, or about 2.0 MPa to about 3.2 MPa, or about 2.0 MPa to about 3.1 MPa, or about 2.0 MPa to about 3.0 MPa, or about 2.0 MPa to about 2.9 MPa, or about 2.0 MPa to about 2.7 MPa, or about 2.0 MPa to about 2.6 MPa, or about 2.2 MPa to about 4.5 MPa, or about 2.4 MPa to about 4.5 MPa, or about 2.5 MPa to about 4.5 MPa, or about 2.6 MPa to about 4.5 MPa, or about 2.8 MPa to about 4.5 MPa, or about 2.9 MPa to about 4.5 MPa, or about 3.0 MPa to about 4.5 MPa, or about 3.1 MPa to about 4.5 MPa, or about 3.2 MPa to about 4.5 MPa, or about 3.3 MPa to about 4.5 MPa, or about 2.0 MPa to about 4.0 MPa, or about 2.2 MPa to about 4.0 MPa, or about 2.4 MPa to about 4.0 MPa, or about 2.5 MPa to about 4.0 MPa, or about 2.6 MPa to about 4.0 MPa, or about 2.8 MPa to about 4.0 MPa, or about 2.9 MPa to about 4.0 MPa, or about 3.0 MPa to about 4.0 MPa, or about 3.1 MPa to about 4.0 MPa, or about 3.2 MPa to about 4.0MPa, or about 3.3MPa to about 4.0MPa, or about 2.0MPa to about 3.5MPa, or about 2.2MPa to about 3.5MPa, or about 2.4MPa to about 3.5MPa, or about 2.5MPa to about 3.5MPa, or about 2.6MPa to about 3.5MPa, or about 2.8MPa to about 3.5MPa, or about 2.9MPa to about 3.5MPa, or about 3.0MPa to about 3.5MPa, or about 3.1MPa to about 3.5MPa, or about 3.2MPa to about 3.5MPa, or about 3.3MPa to about 3.5MPa, or about 2.0MPa to about 3.4MPa, or about 2.2MPa a to about 3.4 MPa, or about 2.4 MPa to about 3.4 MPa, or about 2.5 MPa to about 3.4 MPa, or about 2.6 MPa to about 3.4 MPa, or about 2.8 MPa to about 3.4 MPa, or about 2.9 MPa to about 3.4 MPa, or about 3.0 MPa to about 3.4 MPa, or about 3.1 MPa to about 3.4 MPa, or about 3.2 MPa to about 3.4 MPa, or about 3.3 MPa to about 3.4 MPa, or about 2.0 MPa to about 3.3 MPa, or about 2.2 MPa to about 3.3 MPa, or about 2.4 MPa to about 3.3 MPa, or about 2.5 MPa to about 3.3 MPa, or about 2.6 MPa to about 3.3 MPa, or about 2.8 MPa to about 3.3 MPa, or about 2.9 MPa to about 3.3 MPa, or about 3.0 MPa to about 3.3 MPa, or about 3.1 MPa to about 3.3 MPa, or about 3.2 MPa to about 3.3 MPa, or about 2.0 MPa to about 3.2 MPa, or about 2.2 MPa to about 3.2 MPa, or about 2.4 MPa to about 3.2 MPa, or about 2.5 MPa to about 3.2 MPa, or about 2.6 MPa to about 3.2 MPa, or about 2.8 MPa to about 3.2 MPa, or about 2.9 MPa to about 3.2 MPa, or about 3.0 MPa to about 3.2 MPa, or about 3.1 MPa to about 3.2 MPa, or about 2.0 MPa to about 3.1 MPa, or about 2.2 MPa to about 3.1 MPa, or about 2.4 MPa to about 3.1 MPa, or about 2.5 MPa to about 3.1 MPa, or about 2.6 MPa to about 3.1 MPa, or about 2.8 MPa to about 3.1 MPa, or about 2.9 MPa to about 3.1 MPa, or about 3.0 MPa to about 3.1 MPa, or about 2.0 MPa to about 3.0 MPa, or about 2.2 MPa to about 3.0 MPa, or about 2.4 MPa to about 3.0 MPa, or about 2.5 MPa to about 3.0 MPa, or about 2.6 MPa to about 3.0 MPa, or about 2.8 MPa to about 3.0 MPa, or about 2.9 MPa to about 3.0 MPa, or about 2.0 MPa to about 2.9 MPa, or about 2.2 MPa to about 2.9 MPa, or about 2.4 MPa to about 2.9 MPa, or about 2.5 MPa to about 2.9 MPa, or about 2.6 MPa to about 2.9 MPa, or about 2.8 MPa to about 2.9 A modulus of elasticity at 300% elongation (i.e., tensile modulus), measured according to ISO 37, of about 2.9 MPa, or about 2.0 MPa to about 2.7 MPa, or about 2.2 MPa to about 2.7 MPa, or about 2.4 MPa to about 2.7 MPa, or about 2.5 MPa to about 2.7 MPa, or about 2.6 MPa to about 2.7 MPa, or about 2.0 MPa to about 2.6 MPa, or about 2.2 MPa to about 2.6 MPa, or about 2.4 MPa to about 2.6 MPa, or about 2.5 MPa to about 2.6 MPa, 300(i) about 1.45 to about 3.10, for example, about 1.45 to about 3.0, or about 1.45 to about 2.90, or about 1.45 to about 2.80, or about 1.45 to about 2.70, or about 1.45 to about 2.60, or about 1.45 to about 2.40, or about 1.45 to about 2.50, or about 1.45 to about 2.30, or about 1.45 to about 2.10, or about 1.45 to about 2.00, or about 1.45 to about 1.94, or about 1.45 to about 1.90, or about 1.45 to about 1.80, or about 1.45 to about 1.70, or about 1.50 to about 3.10, or about 1.50 to about 3.0, or about 1. 0.50 to about 2.90, or about 1.50 to about 2.80, or about 1.50 to about 2.70, or about 1.50 to about 2.60, or about 1.50 to about 2.40, or about 1.50 to about 2.50, or about 1.50 to about 2.30, or about 1.50 to about 2.10, or about 1.50 to about 2.00, or about 1.50 to about 1.94, or about 1.50 to about 1.90, or about 1.50 to about 1.80, or about 1.50 to about 1.70, or about 1.50 to about 2.50, or about 1.60 to about 2.50, or about 1.62 to about 2.50, or about 1.70 to about 2.50, or about 1.80 to about 2.50, or about 1.90 to about 2.50, or about 1.50 to about 2.30, or about 1.60 to about 2.30, or about 1.62 to about 2.30, or about 1.70 to about 2.30, or about 1.80 to about 2.30, or about 1.90 to about 2.30, or about 1.50 to about 2.10, or about 1.60 to about 2.10, or about 1.62 to about 2.10, or about 1.70 to about 2.10, or about 1.80 to about 2.10, or about 1.90 to about 2.10, or about 1.50 to about 2.00, or about 1.60 to about 2.00, or about 1.62 to about 2.00, or about 1.70 to about 2.00, or about 1.80 to about 2.00 , or about 1.90 to about 2.00, or about 1.50 to about 1.94, or about 1.60 to about 1.94, or about 1.62 to about 1.94, or about 1.70 to about 1.94, or about 1.80 to about 1.94, or about 1.90 to about 1.94, or about 1.50 to about 1.90, or about 1.60 to about 1.90, or about 1.62 to about 1.90, or about 1.70 to about 1.90, or about 1.80 to about 1.90, or about 1.50 to about 1.80, or about 1.60 to about 1.80, or about 1.62 to about 1.80, or about 1.70 to about 1.80, or about 1.50 to about 1.70, or about 1.60 to about 1.70, or a reinforcement index, M, of about 1.62 to about 1.70. 300 / M 100(j) about 6 MPa to about 15 MPa, for example, about 6 MPa to about 12 MPa, or about 6 MPa to about 11 MPa, or about 6 MPa to about 10.8 MPa, or about 6 MPa to about 10 MPa, or about 8 MPa to about 15 MPa, or about 9 MPa to about 15 MPa, or about 9.3 MPa to about 15 MPa, or about 10 MPa to about 15 MPa, or about 8 MPa to about 12 MPa, or about 9 MPa to about 12 MPa, or about 9.3 MPa to about 12 MPa, or about 10 MPa to about 12 MPa, or about 8 MPa to about 11 MPa, or about 9 MPa to about 11 MPa, or about 9.3 MPa to about 11 MPa, or about 10 MPa to about 11 MPa, or about 8 MPa to about 10.8 MPa, or about 9 MPa to about 10.8 MPa, or about 9 MPa to about 10.8 MPa, or about 9.3 MPa to about 10.8 MPa, or about 10 MPa to about 10.8 MPa, or about 8 MPa to about 10 MPa, or about 9 MPa to about 10 MPa, or about 9.3 MPa to about 10 MPa, according to ISO 37 (k) a tensile strength measured from about 500% to about 1500%, e.g., from about 600% to about 1500%, or from about 700% to about 1500%, or from about 710% to about 1500%, or from about 1000% to about 1500%, or from about 500% to about 1200%, or from about 600% to about 1200%, or from about 700% to about 1200%, or from about 710% to about 1200%, or from about 1000% to about 1200%, or from about 500% to about 1100%, or from about 600% to about 1100%, or may have an elongation at break, measured according to ISO 37, of about 700% to about 1100%, or about 710% to about 1100%, or about 1000% to about 1100%, or about 500% to about 1010%, or about 600% to about 1010%, or about 700% to about 1010%, or about 710% to about 1010%, or about 1000% to about 1010%, or about 500% to about 800%, or about 600% to about 800%, or about 700% to about 800%, or about 710% to about 800%;(l) about 20 N / mm to about 40 N / mm, for example, about 25 N / mm to about 40 N / mm, or about 29 N / mm to about 40 N / mm, or about 30 N / mm to about 40 N / mm, or about 20 N / mm to about 35 N / mm, or about 25 N / mm to about 35 N / mm, or about 29 N / mm to about 35 N / mm, or about 30 N / mm to about 35 N / mm, or about 20 N / mm to about 32 N / mm, or about 25 N / mm to about 32 N / mm, or about 29 N / mm to about 32 N / mm, or about 30 N / mm to about 32 N / mm, or about 20 N / mm to about 30 N / mm, or about 25 N / mm to about 3 (m) a Shore A hardness, measured according to ISO 7619-1, of about 30 to about 70, e.g., about 40 to about 70, or about 50 to about 70, or about 30 to about 60, or about 40 to about 60, or about 50 to about 60, or about 30 to about 55, or about 40 to about 55, or about 50 to about 55, or about 30 to about 52, or about 40 to about 52, or about 50 to about 52; (n) a Shore A hardness, measured according to ISO 7619-1, of about 10% to about 50%, e.g., about 20% to about 50%, or about 30% to about 50%, or about 35% to about (o) a compression set, measured according to ISO 815, of about 0.200 g to about 0.450 g, e.g., about 0.210 g to about 0.450 g, or about 0.250 g to about 0.450 g, or about 0.300 g to about 0.450 g, or about 0.200 g to about 0.450 g, or about 0.300 g to about 0.450 g, or about 0.200 g to about 0.450 g, and / or (p) about 0.20 cm;3 ~about 0.60cm 3 , for example, about 0.25 cm 3 ~about 0.60cm 3 , or about 0.30 cm 3 ~about 0.60cm 3 , or about 0.20 cm 3 ~ approx. 0.55cm 3 , or about 0.25 cm 3 ~ approx. 0.55cm 3 , or about 0.30 cm 3 ~ approx. 0.55cm 3 , about 0.20cm 3 ~about 0.50cm 3 , or about 0.25 cm 3 ~about 0.50cm 3 , or about 0.30 cm 3 ~about 0.50cm 3 It may have abrasion resistance according to ISO 4649.
[0110] The polymer composition includes (a) an elastomer (e.g., rubber) and has a t measured using a rotorless cure tester according to ISO 6502 (Part 3) of about 0.5 to about 30 minutes, e.g., about 0.5 to about 20 minutes, or about 0.5 to about 10 minutes, or about 1 to about 5 minutes, or about 1 to about 3 minutes, or about 2 to about 10 minutes, or about 2 to about 5 minutes, or about 2 to about 3 minutes. 90(b) a vulcanization time of about 10 to about 55, e.g., about 20 to about 55, or about 30 to about 55, or about 35 to about 55, about 40 to about 55, or about 41 to about 55, or about 42 to about 55, or about 45 to about 55, or about 46 to about 55, or about 35 to about 50, or about 40 to about 50, or about 41 to about 50, or about 42 to about 50, or about 45 to about 50, or about 46 to about 50, or about 35 to about 47, or about 40 to about 47, or about 41 to about 47, or about 42 to about 47, or about 45 to about 47, or about 46 to about 47, or about 35 to about 46, or about 40 to about 46, or about 41 to about 46, or about 42 to about 46, or about 45 to about 46, or about 35 to about 43, or about 40 to about 43, or about 41 to about 43, or about 42 to about 43, or about 35 to about 42, or about 40 to about 42, or about 41 to about 42, or about 35 to about 41, or about 40 to about 41;(c) about 20MU to about 100MU, for example, about 20MU to about 90MU, or about 20MU to about 80MU, or about 20MU to about 70MU, or about 20MU to about 60MU, or about 20MU to about 50MU, about 25MU to about 90MU, or about 25MU to about 80MU, or about 25MU to about 70MU, or about 25MU to about 60MU, or about 25MU to about 50MU, about 30MU to about 90MU, or about 30MU to about 80MU, or about 30MU to about 70MU, or about 30MU to about 60MU, or is about 30MU to about 50MU, about 35MU to about 90MU, or about 35MU to about 80MU, or about 35MU to about 70MU, or about 35MU to about 60MU, or about 35MU to about 50MU, about 40MU to about 90MU, or about 40MU to about 80MU, or about 40MU to about 70MU, or about 40MU to about 60MU, or about 40MU to about 50MU, about 25MU to about 50MU, or about 30MU to about 50MU, or about 32MU to about 50MU, or about 35MU to about 50MU, or about 36MU to about about 50MU, or about 20MU to about 40MU, or about 25MU to about 40MU, or about 30MU to about 40MU, or about 32MU to about 40MU, or about 35MU to about 40MU, or about 36MU to about 40MU, or about 20MU to about 38MU, or about 25MU to about 38MU, or about 30MU to about 38MU, or about 32MU to about 38MU, or about 35MU to about 38MU, or about 36MU to about 38MU, or about 20MU to about 37MU, or about 25MU to about 37MU, or about 30MU to about 37MU, or about 32MU to about 37MU, or about 35MU to about 37MU, or about 36MU to about 37MU, or about 20MU to about 35MU, or about 25MU to about 35MU, or about 30MU to about 35MU, or about 32MU to about 35MU, or about 20MU to about 33MU, or about 25MU to about 33MU, or about 30MU to about 33MU, or about 32MU to about 33MU;(d) a storage modulus G' (of complex dynamic modulus G = G' + iG'') at 150% elongation, obtained using a moving die rheometer according to ISO 13145, of about 15 kPa to about 50 kPa, e.g., about 15 kPa to about 40 kPa, or about 15 kPa to about 35 kPa, or about 15 kPa to about 32 kPa, or about 20 kPa to about 50 kPa, or about 20 kPa to about 40 kPa, or about 20 kPa to about 35 kPa, or about 20 kPa to about 32 kPa; (e) about 1.0 kg / m; 3 ~Approx. 1.50kg / m 3 , for example, about 1.10 kg / m 3 ~Approx. 1.50kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.50kg / m 3 , or about 1.0 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.10 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.0 kg / m 3 ~Approx. 1.35kg / m 3 , 1.10kg / m 3 ~Approx. 1.35kg / m 3 , 1.20kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.50kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.50kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.50kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.45kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.45kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.45kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.45kg / m 3 , or about 1.20 kg / m 3~Approx. 1.40kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.40kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.35kg / m 3 , or about 1.20 kg / m 3 ~Approx. 1.34kg / m 3 , or about 1.25 kg / m 3 ~Approx. 1.34kg / m 3 , or about 1.30 kg / m 3 ~Approx. 1.34kg / m 3 , or about 1.33 kg / m 3 ~Approx. 1.34kg / m 3(f) a density, measured according to ISO 2781, of from about 0.5 MPa to about 1.7 MPa, for example, from about 0.5 MPa to about 1.6 MPa, or from about 0.5 MPa to about 1.5 MPa, or from about 0.8 MPa to about 1.7 MPa, or from about 0.8 MPa to about 1.6 MPa, or from about 0.8 MPa to about 1.5 MPa, or from about 0.9 MPa to about 1.7 MPa, or from about 0.9 MPa to about 1.6 MPa, or from about 0.9 MPa to about 1.5 MPa, or from about 1.0 MPa to about 1.5 MPa, or from about 1.1 MPa to about 1.5 MPa, or from about 1.2 MPa to about 1.5 MPa, or from about 0.5 MPa to about 1.4 MPa, or from about 0.8 MPa to about 1.4 MPa, or from about 0.9 MPa to about 1.4 MPa, or from about 1.0 MPa to about 1.4 MPa, or from about 1.1 MPa to about 1.4 MPa, or about 1.2 MPa to about 1.4 MPa, or about 0.5 MPa to about 1.3 MPa, or about 0.8 MPa to about 1.3 MPa, or about 0.9 MPa to about 1.3 MPa, or about 1.0 MPa to about 1.3 MPa, or about 1.1 MPa to about 1.3 MPa, or about 1.2 MPa to about 1.3 MPa, or about 0.5 MPa to about 1.2 MPa, or about 0.8 MPa to about 1.2 MPa, or about 0.9 MPa to about 1.2 MPa, or about 1.0 MPa to about 1.2 MPa, or about 1.1 MPa to about 1.2 MPa, or about 0.5 MPa to about 1.1 MPa, or about 0.8 MPa to about 1.1 MPa, or about 0.9 MPa to about 1.1 MPa, or about 1.0 MPa to about 1.1 MPa 50(g) about 1.0 MPa to about 2.5 MPa, for example, about 1.2 MPa to about 2.5 MPa, or about 1.4 MPa to about 2.5 MPa, or about 1.5 MPa to about 2.5 MPa, or about 1.6 MPa to about 2.5 MPa, or about 1.8 MPa to about 2.5 MPa, or about 1.0 MPa to about 2.4 MPa, or about 1.2 MPa to about 2.4 MPa, or about 1.4 MPa to about 2.4 MPa, or about 1.5 MPa to about 2.4 MPa. , or about 1.6 MPa to about 2.4 MPa, or about 1.8 MPa to about 2.4 MPa, or about 1.0 MPa to about 2.2 MPa, or about 1.2 MPa to about 2.2 MPa, or about 1.4 MPa to about 2.2 MPa, or about 1.5 MPa to about 2.2 MPa, or about 1.6 MPa to about 2.2 MPa, or about 1.8 MPa to about 2.2 MPa, or about 1.0 MPa to about 2.0 MPa, or about 1.2 MPa to about 2.0 MPa, or about 1.4 M Pa to about 2.0 MPa, or about 1.5 MPa to about 2.0 MPa, or about 1.6 MPa to about 2.0 MPa, or about 1.8 MPa to about 2.0 MPa, or about 1.0 MPa to about 1.9 MPa, or about 1.2 MPa to about 1.9 MPa, or about 1.4 MPa to about 1.9 MPa, or about 1.5 MPa to about 1.9 MPa, or about 1.6 MPa to about 1.9 MPa, or about 1.8 MPa to about 1.9 MPa, or about 1.0 MPa to about 1.8 M MPa, or about 1.2 MPa to about 1.8 MPa, or about 1.4 MPa to about 1.8 MPa, or about 1.5 MPa to about 1.8 MPa, or about 1.6 MPa to about 1.8 MPa, or about 1.0 MPa to about 1.6 MPa, or about 1.2 MPa to about 1.6 MPa, or about 1.4 MPa to about 1.6 MPa, or about 1.5 MPa to about 1.6 MPa 100(h) about 1.5 MPa to about 5.5 MPa, or about 1.5 MPa to about 5.0 MPa, for example, about 1.5 MPa to about 4.5 MPa, or about 1.5 MPa to about 4.0 MPa, or about 1.5 MPa to about 3.5 MPa, or about 1.5 MPa to about 3.4 MPa, or about 1.5 MPa to about 3.3 MPa, or about 1.5 MPa to about 3.2 MPa, or about 1.5 MPa to about 3.1 MPa, or about 1.5 MPa to about 3.0 MPa, or about 1.5 MPa to about 2.9 MPa, or about 1.5 MPa to about 2.7 MPa, or about MPa to about 2.6 MPa, or about 1.6 MPa to about 5.5 MPa, or about 1.6 MPa to about 5.0 MPa, or about 1.6 MPa to about 4.5 MPa, or about 1.6 MPa to about 4.0 MPa, or about 1.6 MPa to about 3.5 MPa, or about 1.6 MPa to about 3.4 MPa, or about 1.6 MPa to about 3.3 MPa, or about 1.6 MPa to about 3.2 MPa, or about 1.6 MPa to about 3.1 MPa, or about 1.6 MPa to about 3.0 MPa, or about 1.6 MPa to about 2.9 MPa, or about 1.6 MPa to about 2.7 MPa, or about 0.6MPa to about 2.6MPa, or about 2.0MPa to about 5.5MPa, or about 2.0MPa to about 5.0MPa, or about 2.0MPa to about 4.5MPa, or about 2.0MPa to about 4.0MPa, or about 2.0MPa to about 3.5MPa, or about 2.0MPa to about 3.4MPa, or about 2.0MPa to about 3.3MPa, or about 2.0MPa to about 3.2MPa, or about 2.0MPa to about 3.1MPa, or about 2.0MPa to about 3.0MPa, or about 2.0MPa to about 2.9MPa, or about 2.0MPa to about 2.7MPa, or about 2.0MPa to about 2.6MPa, or about 2.2MPa to about 4.5MPa, or about 2.4MPa to about 4.5MPa, or about 2.5MPa to about 4.5MPa, or about 2.6MPa to about 4.5MPa, or about 2.8MPa to about 4.5MPa, or about 2.9MPa to about 4.5MPa, or about 3.0MPa to about 4.5MPa, or about 3.1MPa to about 4.5MPa, or about 3.2MPa to about 4.5MPa, or about 3.3MPa to about 4.5MPa, or about 2.0MPa to about 4.0MPa, or about 2.2MPa to about 4.0MPa, or about 2.4 MPa to about 4.0 MPa, or about 2.5 MPa to about 4.0 MPa, or about 2.6 MPa to about 4.0 MPa, or about 2.8 MPa to about 4.0 MPa, or about 2.9 MPa to about 4.0 MPa, or about 3.0 MPa to about 4.0 MPa, or about 3.1 MPa to about 4.0 MPa, or about 3.2 MPa to about 4.0 MPa, or about 3.3 MPa to about 4.0 MPa, or about 2.0 MPa to about 3.5 MPa, or about 2.2 MPa to about 3.5 MPa, or about 2.4 MPa to about 3.5 MPa, or about 2.5 MPa to about 3.5 MPa, or about 2.6 MPa to about 3.5 MPa, or about 2.8 MPa to about 3.5 MPa, or about 2.9 MPa to about 3.5 MPa, or about 3.0 MPa to about 3.5 MPa, or about 3.1 MPa to about 3.5 MPa, or about 3.2 MPa to about 3.5 MPa, or about 3.3 MPa to about 3.5 MPa, or about 2.0 MPa to about 3.4 MPa, or about 2.2 MPa to about 3.4 MPa, or about 2.4 MPa to about 3.4 MPa, or about 2.5 MPa to about 3.4 MPa, or about 2.6 MPa to about 3.4 MPa, or about 2.8 MPa to about 3.4 MPa, or about 2.9 MPa to about 3.4 MPa, or about 3.0 MPa to about 3.4MPa, or about 3.1MPa to about 3.4MPa, or about 3.2MPa to about 3.4MPa, or about 3.3MPa to about 3.4MPa, or about 2.0MPa to about 3.3MPa, or about 2.2MPa to about 3.3MPa, or about 2.4MPa to about 3.3MPa, or about 2.5MPa to about 3.3MPa, or about 2.6MPa to about 3.3MPa, or about 2.8MPa to about 3.3MPa, or about 2.9MPa to about 3.3MPa, or about 3.0MPa to about 3.3MPa, or about 3.1MPa to about 3.3MPa, or about 3.2MPa to about 3.3MPa, or about 2.0MPa a to about 3.2 MPa, or about 2.2 MPa to about 3.2 MPa, or about 2.4 MPa to about 3.2 MPa, or about 2.5 MPa to about 3.2 MPa, or about 2.6 MPa to about 3.2 MPa, or about 2.8 MPa to about 3.2 MPa, or about 2.9 MPa to about 3.2 MPa, or about 3.0 MPa to about 3.2 MPa, or about 3.1 MPa to about 3.2 MPa, or about 2.0 MPa to about 3.1 MPa, or about 2.2 MPa to about 3.1 MPa, or about 2.4 MPa to about 3.1 MPa, or about 2.5 MPa to about 3.1 MPa, or about 2.6 MPa to about 3.1 MPa, or about 2.8 MPa to about 3.1 MPa, or about 2.9 MPa to about 3.1 MPa, or about 3.0 MPa to about 3.1 MPa, or about 2.0 MPa to about 3.0 MPa, or about 2.2 MPa to about 3.0 MPa, or about 2.4 MPa to about 3.0 MPa, or about 2.5 MPa to about 3.0 MPa, or about 2.6 MPa to about 3.0 MPa, or about 2.8 MPa to about 3.0 MPa, or about 2.9 MPa to about 3.0 MPa, or about 2.0 MPa to about 2.9 MPa, or about 2.2 MPa to about 2.9 MPa, or about 2.4 MPa to about 2.9 MPa, or about 2.5 MPa to about 2.9 MPa, or from about 2.6 MPa to about 2.9 MPa, or from about 2.8 MPa to about 2.9 MPa, or from about 2.0 MPa to about 2.7 MPa, or from about 2.2 MPa to about 2.7 MPa, or from about 2.4 MPa to about 2.7 MPa, or from about 2.5 MPa to about 2.7 MPa, or from about 2.6 MPa to about 2.7 MPa, or from about 2.0 MPa to about 2.6 MPa, or from about 2.2 MPa to about 2.6 MPa, or from about 2.4 MPa to about 2.6 MPa, or from about 2.5 MPa to about 2.6 MPa 300(i) about 1.45 to about 3.10, for example, about 1.45 to about 3.0, or about 1.45 to about 2.90, or about 1.45 to about 2.80, or about 1.45 to about 2.70, or about 1.45 to about 2.60, or about 1.45 to about 2.40, or about 1.45 to about 2.50, or about 1.45 to about 2.30, or about 1.45 to about 2.10, or about 1.45 to about 2.00, or about 1.45 to about 1.94, or about 1.45 to about 1.90, or about 1.45 to about 1.80, or about 1.45 to about 1.70, or about 1.50 to about 3.10, or about 1.50 to about 3.0, or about 1. 0.50 to about 2.90, or about 1.50 to about 2.80, or about 1.50 to about 2.70, or about 1.50 to about 2.60, or about 1.50 to about 2.40, or about 1.50 to about 2.50, or about 1.50 to about 2.30, or about 1.50 to about 2.10, or about 1.50 to about 2.00, or about 1.50 to about 1.94, or about 1.50 to about 1.90, or about 1.50 to about 1.80, or about 1.50 to about 1.70, or about 1.50 to about 2.50, or about 1.60 to about 2.50, or about 1.62 to about 2.50, or about 1.70 to about 2.50, or about 1.80 to about 2.50, or about 1.90 to about 2.50, or about 1.50 to about 2.30, or about 1.60 to about 2.30, or about 1.62 to about 2.30, or about 1.70 to about 2.30, or about 1.80 to about 2.30, or about 1.90 to about 2.30, or about 1.50 to about 2.10, or about 1.60 to about 2.10, or about 1.62 to about 2.10, or about 1.70 to about 2.10, or about 1.80 to about 2.10, or about 1.90 to about 2.10, or about 1.50 to about 2.00, or about 1.60 to about 2.00, or about 1.62 to about 2.00, or about 1.70 to about 2.00, or about 1.80 to about 2.00 , or about 1.90 to about 2.00, or about 1.50 to about 1.94, or about 1.60 to about 1.94, or about 1.62 to about 1.94, or about 1.70 to about 1.94, or about 1.80 to about 1.94, or about 1.90 to about 1.94, or about 1.50 to about 1.90, or about 1.60 to about 1.90, or about 1.62 to about 1.90, or about 1.70 to about 1.90, or about 1.80 to about 1.90, or about 1.50 to about 1.80, or about 1.60 to about 1.80, or about 1.62 to about 1.80, or about 1.70 to about 1.80, or about 1.50 to about 1.70, or about 1.60 to about 1.70, or a reinforcement index, M, of about 1.62 to about 1.70. 300 / M 100(j) about 6 MPa to about 15 MPa, for example, about 6 MPa to about 12 MPa, or about 6 MPa to about 11 MPa, or about 6 MPa to about 10.8 MPa, or about 6 MPa to about 10 MPa, or about 8 MPa to about 15 MPa, or about 9 MPa to about 15 MPa, or about 9.3 MPa to about 15 MPa, or about 10 MPa to about 15 MPa, or about 8 MPa to about 12 MPa, or about 9 MPa to about 12 MPa, or about 9.3 MPa to about 12 MPa, or about 10 MPa to about 12 MPa, or about 8 MPa to about 11 MPa, or about 9 MPa to about 11 MPa, or about 9.3 MPa to about 11 MPa, or about 10 MPa to about 11 MPa, or about 8 MPa to about 10.8 MPa, or about 9 MPa to about 10.8 MPa, or about 9 MPa to about 10.8 MPa, or about 9.3 MPa to about 10.8 MPa, or about 10 MPa to about 10.8 MPa, or about 8 MPa to about 10 MPa, or about 9 MPa to about 10 MPa, or about 9.3 MPa to about 10 MPa, according to ISO 37 (k) a tensile strength measured from about 500% to about 1500%, e.g., from about 600% to about 1500%, or from about 700% to about 1500%, or from about 710% to about 1500%, or from about 1000% to about 1500%, or from about 500% to about 1200%, or from about 600% to about 1200%, or from about 700% to about 1200%, or from about 710% to about 1200%, or from about 1000% to about 1200%, or from about 500% to about 1100%, or from about 600% to about 1100%, or may have an elongation at break, measured according to ISO 37, of about 700% to about 1100%, or about 710% to about 1100%, or about 1000% to about 1100%, or about 500% to about 1010%, or about 600% to about 1010%, or about 700% to about 1010%, or about 710% to about 1010%, or about 1000% to about 1010%, or about 500% to about 800%, or about 600% to about 800%, or about 700% to about 800%, or about 710% to about 800%;(l) about 20 N / mm to about 40 N / mm, for example, about 25 N / mm to about 40 N / mm, or about 29 N / mm to about 40 N / mm, or about 30 N / mm to about 40 N / mm, or about 20 N / mm to about 35 N / mm, or about 25 N / mm to about 35 N / mm, or about 29 N / mm to about 35 N / mm, or about 30 N / mm to about 35 N / mm, or about 20 N / mm to about 32 N / mm, or about 25 N / mm to about 32 N / mm, or about 29 N / mm to about 32 N / mm, or about 30 N / mm to about 32 N / mm, or about 20 N / mm to about 30 N / mm, or about 25 N / mm to about 3 (m) a Shore A hardness measured according to ISO 7619-1 of about 30 to about 70, for example, about 40 to about 70, or about 50 to about 70, or about 30 to about 60, or about 40 to about 60, or about 50 to about 60, or about 30 to about 55, or about 40 to about 55, or about 50 to about 55, or about 30 to about 52, or about 40 to about 52, or about 50 to about 52; (n) a Shore A hardness measured according to ISO 7619-1 of about 10% to about 50%, for example, about 20% to about 50%, or about 30% to about 50%, or about 35% to about (o) a compression set, measured according to ISO 815, of about 50%, or about 38% to about 50%, or about 10% to about 45%, or about 20% to about 45%, or about 30% to about 45%, or about 35% to about 45%, or about 38% to about 45%, or about 10% to about 43%, or about 20% to about 43%, or about 30% to about 43%, or about 35% to about 43%, or about 38% to about 43%; (o) a compression set, measured according to ISO 815, of about 0.200 g to about 0.450 g, for example, about 0.210 g to about 0.450 g, or about 0.250 g to about 0.450 g, or about 0.300 g to about 0.450 g, or about 0.200 g to about 0.425 g, or about 0.210 g to about 0.425 g, or about 0.250 g to about 0.425 g, or about 0.300 g to about 0.425 g, or about 0.200 g to about 0.400 g, or about 0.210 g to about 0.400 g, or about 0.250 g to about 0.400 g, or about 0.300 g to about 0.400 g, or about 0.200 g to about 0.300 g, or about 0.210 g to about 0.300 g, or about 0.250 g to about 0.300 g, or about 0.300 g to about 0.300 g; and (p) about 0.20 cm;3 ~about 0.60cm 3 , for example, about 0.25 cm 3 ~about 0.60cm 3 , or about 0.30 cm 3 ~about 0.60cm 3 , or about 0.20 cm 3 ~ approx. 0.55cm 3 , or about 0.25 cm 3 ~ approx. 0.55cm 3 , or about 0.30 cm 3 ~ approx. 0.55cm 3 , about 0.20cm 3 ~about 0.50cm 3 , or about 0.25 cm 3 ~about 0.50cm 3 , or about 0.30 cm 3 ~about 0.50cm 3 It may have abrasion resistance according to ISO 4649.
[0111] Method for making a polymer composition The polymer composition can be prepared by combining a polymer or polymer precursor with the talc particles (e.g., microcrystalline talc particles) of the present invention and any other optional ingredients. When the talc particles (e.g., microcrystalline talc particles) (and any other optional ingredients) are combined with the polymer precursor, the resulting combination of the polymer precursor, the talc particles (e.g., microcrystalline talc particles) (and any other optional ingredients) can be cured. The polymer composition can be prepared by intimately mixing together its components (except for the talc particles (e.g., microcrystalline talc particles)). In that case, the talc particles (e.g., microcrystalline talc particles) can be suitably blended, e.g., dry blended, with the mixture of components and any desired additional components prior to processing to form the final polymer composite or article.
[0112] The polymer composition can be, for example, according to any embodiment disclosed herein. The preparation of the polymer composition of the present invention can be accomplished by any suitable mixing method known in the art, as will be readily apparent to those skilled in the art. Such methods include, for example, dry blending of the individual components or their precursors, and subsequent processing in a conventional manner. Certain of the components can be premixed, if desired, before being added to the compounded mixture.
[0113] In the case of thermoplastic polymer compositions, such processing may include melt mixing directly in an extruder for making articles from the composition, or premixing in a separate mixing device, or a dry blend of the individual components may be directly injection molded without premelt mixing. The polymer composition can be prepared by intimately mixing the components together, in which case the talc particles (e.g., microcrystalline talc particles) can be suitably dry blended with the polymer and any desired additional components before being treated as described above. Other filler compounds may be added and blended in during the mixing stage.
[0114] To prepare the crosslinked or cured polymer composition, the blend of uncured components or precursors thereof, and, if desired, talc particles (e.g., microcrystalline talc particles) and any desired non-talc components, are contacted under suitable conditions of heat, pressure, and / or light with an effective amount of any suitable crosslinking agent or curing system, according to the nature and amount of polymer used, to crosslink and / or cure the polymer. To prepare a polymer composition in which the talc particles (e.g., microcrystalline talc particles) and any other desired components are present in situ upon polymerization, a blend of monomers and any other desired polymer precursors, talc particles (e.g., microcrystalline talc particles) and any other components are contacted under appropriate conditions of heat, pressure, and / or light, according to the nature and amount of monomer used, to polymerize the monomers in situ with the talc particles (e.g., microcrystalline talc particles) and any other components.
[0115] In certain embodiments, talc particles (e.g., microcrystalline talc particles) are dispersed in a mixture containing a polymer and, optionally, a curing agent under stirring. The mixture may further include a mold release agent. The resulting dispersion may be degassed to remove entrapped air. The resulting dispersion may then be poured into a suitable mold (if liquid), placed in a compression mold (if solid), or poured into a mold (if solid) and cured. Suitable curing temperatures range from 20 to 200°C, for example, from 20 to 120°C, or from 60 to 90°C, or from 150 to 200°C, depending on the polymer and curing agent. The starting polymer mixture can further include a prepolymer, which may or may not correspond to the starting polymer. The viscosity of the starting polymer or polymer / monomer solution, the amount of curing agent, release agent and talc particles (e.g., microcrystalline talc particles) can be varied according to the requirements of the final cured product. In general, the more talc particles (e.g., microcrystalline talc particles) added, the higher the viscosity of the dispersion. A dispersant can be added to reduce the viscosity of the dispersion. Alternatively, the amount of polymer in the starting solution can be reduced.
[0116] Suitable curing agents will be readily apparent to those skilled in the art and include organic peroxides, hydroperoxides and azo compounds. Examples of peroxide and hydroperoxide curing agents include dimethyldibutylperoxyhexane, benzyl peroxide, dicumyl peroxide, methyl ethyl ketone peroxide, lauryl peroxide, cyclohexanone peroxide, t-butyl perbenzoate, t-butyl hydroperoxide, t-butyl benzene hydroperoxide, cumene hydroperoxide and t-butyl peroctoate. The compounded composition may further include additional ingredients such as slip aids (eg, erucamide), processing aids (eg, Polybatch® AMF-705), mold release agents, and antioxidants.
[0117] Suitable release agents will be readily apparent to those skilled in the art and include fatty acids, as well as zinc, calcium, magnesium and lithium salts of fatty acids and organic phosphate esters. Specific examples are stearic acid, zinc stearate, calcium stearate, magnesium stearate, lithium stearate, calcium oleate, zinc palmitate. Typically, slip and processing aids and release agents are added in amounts less than about 5% by weight based on the weight of the masterbatch. The polymeric article can then be extruded, compression molded, or injection molded using conventional techniques known in the art, as will be readily apparent to those skilled in the art. Thus, as described below, the present invention also relates to articles formed from the polymeric compositions of the present invention.
[0118] In embodiments where the polymer composition comprises an elastomer (e.g., rubber), curing (e.g., vulcanization) of the elastomer (e.g., rubber) may require the presence of sulfur. Curing (e.g., vulcanization) may also be accelerated using accelerators. Suitable accelerators include guanidine, dithiocarbamate, thiuram, 2-mercaptobenzothiazole, zinc-2-mercaptobenzothiazole, mercaptobenzothiazole disulfide, tetramethylthiuram disulfide, thiourea, benzothiazole sulfenamide, and isopropyl xanthate.
[0119] In certain embodiments, the polymer composition includes a colorant, if present, that is added during compounding of the polymer composition. The colorant may be added in the form of a masterbatch. Suitable colors are varied. In certain embodiments, talc particles (e.g., microcrystalline talc particles) are added to a twin-screw extruder into which an unfilled polymer is fed and melted. The talc particles (e.g., microcrystalline talc particles) are fed into the extruder through a hopper, e.g., via gravity feed, and are homogeneously blended with the polymer. The mixture exits the extruder and can be cooled. The mixture can then be further compression molded or injection molded into a useful shape, for example.
[0120] The above method may include compounding and extrusion. Compounding may be performed using a twin screw compounder, such as a Clextral BC21 twin screw extruder or a Leistritz ZSE 18 twin screw extruder or a Baker Perkins 25mm twin screw compounder. The polymer, talc particles (e.g., microcrystalline talc particles) and any additional ingredients may be premixed and fed from a single hopper. The resulting melt may be cooled, for example, in a water bath, and then pelletized. Test specimens, such as Charpy bars or tensile dumbbells, may be injection molded or compression molded or cast or blown into a film. The screw temperature may be between about 100°C and about 300°C, for example, between about 150°C and about 280°C, for example, between about 180°C and about 250°C, or between about 200 and 230°C. The screw speed can be between about 100 and 1200 rpm, for example, between about 100 and 1000 rpm, for example, between about 200 and 800 rpm, for example, between about 250 and 650 rpm, for example, between about 200 and 400 rpm, or between about 500 and 700 rpm. In certain embodiments, the screw speed is about 300 rpm. In other embodiments, the screw speed is about 600 rpm. Suitable injection molding equipment includes, for example, a Billion 50T Proxima press. The polymer composition can be dried before molding. Drying can be carried out at any suitable temperature, for example, about 60° C., for a suitable period of time, for example, about 1 hour to 20 hours, for example, about 2 to 18 hours, or about 1 to 3 hours, or about 4 to 8 hours, or about 12 to 18 hours. The temperature during drying can be kept constant or can be varied. In certain embodiments, the temperature during drying is between about 70 and 120° C., for example, between about 80 and 100° C., for example, about 90° C. Molding is generally performed at a temperature at which the polymer composition is fluid. For example, the molding temperature can be between about 100 and 300° C., for example, between about 200 and 300° C., or between about 240 and about 280° C. After molding, the molded piece is cooled and hardened.
[0121] The polymer composition may be prepared using a two-roll mill as is commonly used to process elastomeric polymer compositions such as rubber. A two-roll mill comprises two horizontally opposed cylinders or rolls that rotate in opposite directions at variable speeds. The distance between the rolls and the rotational speed can be adjusted to vary the shear and compression forces applied to the polymer and other ingredients introduced between the rolls. One or more of the rolls can be hollow and / or cooled. The polymer composition may be prepared by compounding the polymer with talc particles (e.g., microcrystalline talc particles) and any other ingredients in the two-roll mill. The preparation process may be carried out in two or more stages. In a first mastication stage, raw polymer (e.g., rubber) can be passed through the two-roll mill to plasticize the polymer. In one or more second compounding stages, fillers and / or additives can be mixed into the polymer using the two-roll mill. In one example, the preparation process includes passing a polymer (e.g., rubber) through a two-roll mill to plasticize the polymer (e.g., rubber); mixing the polymer with additives (e.g., stearic acid, zinc oxide, PEG, etc.) in the two-roll mill; compounding the polymer with talc particles (e.g., microcrystalline talc particles) in the two-roll mill and alternately adding talc particles (e.g., microcrystalline talc particles) and oil to the polymer; and mixing accelerators and / or sulfur into the polymer in the two-roll mill.
[0122] Alternatively, the polymer composition may be prepared using an internal mixer, such as a Banbury internal mixer, as commonly used in processing elastomeric polymer compositions such as rubber. The internal mixer comprises two or more rotors enclosed within a mixing chamber that rotate towards each other at different speeds. The rotors may comprise spiral blades. One or more of the rotors may be heated or cooled. The material to be mixed may be fed into the mixing chamber through a hopper, and a floating weight may be placed on top of the feed to trap the material within the mixing chamber. The polymer composition may be prepared in the internal mixer by compounding the polymer with talc particles (e.g., microcrystalline talc particles) and any other ingredients. Alternatively, the polymer composition can be prepared using a two-roll mill and an internal mixer. For example, the polymer composition can be prepared first in an internal mixer (e.g., to plasticize the polymer and incorporate mineral fillers, including talc particles, oils, surface treatments and / or additives) and then in a two-roll mill (e.g., to compound the polymer composition with stearic acid, sulfur, zinc oxide, accelerators and / or other additives).
[0123] Other suitable processing techniques include gas-assisted injection molding, calendaring, vacuum forming, thermoforming, blow molding, drawing, spinning, film casting, lamination, or any combination thereof. Any suitable equipment may be used, as will be apparent to one skilled in the art. The polymer composition can be processed in any suitable manner as described herein to form or incorporate into an article of manufacture. There are a wide variety of articles of manufacture that can be formed from the polymer composition. Examples include tires, shoe soles (e.g., shoe outsoles), conveyor belts, V-belts, and caterpillar treads (e.g., caterpillar tread blocks).
[0124] Use of talc particles Talc particles (eg, microcrystalline talc particles) can be used in the polymer composition. Talc particles (e.g., microcrystalline talc particles) can be used to reinforce the polymer composition (i.e., by adding talc particles (e.g., microcrystalline talc particles) to the polymer composition). For example, talc particles (e.g., microcrystalline talc particles) can be used to increase the stiffness of the polymer composition (e.g., by 50% (i.e., M 50 ), 100% (i.e., M 100 ) and / or 300% (M 300 ) by increasing the modulus of elasticity of the polymer composition at elongation; to increase the strength of the polymer composition (e.g., by increasing the tensile strength of the polymer composition); to increase the wear resistance of the polymer composition; the reinforcement index, M 300 / M 100and / or to increase the tear resistance of the polymer composition.
[0125] Talc particles (e.g., microcrystalline talc particles) can improve the stiffness (e.g., M) of a polymer composition compared to a polymer composition that does not include talc particles (e.g., microcrystalline talc particles) according to the present invention. 50 , M 100 Or M 300 ), strength (e.g., tensile strength), abrasion resistance, reinforcement index (i.e., M 300 / M 100 In particular, talc particles (e.g., microcrystalline talc particles) may increase the stiffness (e.g., M) and / or tear resistance of the polymer composition compared to polymer compositions filled with talc particles not according to the invention. 50 , M 100 Or M 300 ), strength (e.g., tensile strength), abrasion resistance, reinforcement index (i.e., M 300 / M 100 For example, talc particles (e.g., microcrystalline talc particles) may increase the stiffness (e.g., M) and / or tear resistance of a polymer composition compared to a polymer composition filled with an equivalent amount of talc particles not according to the invention. 50 , M 100 Or M 300 ), strength (e.g., tensile strength), abrasion resistance, reinforcement index (i.e., M 300 / M 100 ) and / or tear resistance.
[0126] Additionally or alternatively, talc particles (e.g., microcrystalline talc particles) can be used to reduce the viscosity of the polymer composition (i.e., by adding talc particles (e.g., microcrystalline talc particles) to the polymer composition). For example, talc particles (e.g., microcrystalline talc particles) can be used to reduce the Mooney viscosity of the polymer composition at 100° C. The talc particles (e.g., microcrystalline talc particles) can reduce the viscosity of the polymer composition (e.g., the Mooney viscosity of the polymer composition at 100° C.) compared to a polymer composition that does not include talc particles (e.g., microcrystalline talc particles) according to the present invention (e.g., compared to a polymer composition filled with the same amount of talc particles not according to the present invention). Additionally or alternatively, talc particles (e.g., microcrystalline talc particles) can be used to increase the crosslink density of the polymer composition (i.e., by adding talc particles (e.g., microcrystalline talc particles) to the polymer composition). The talc particles (e.g., microcrystalline talc particles) can increase the crosslink density of the polymer composition compared to a polymer composition that does not include talc particles (e.g., microcrystalline talc particles) according to the present invention (e.g., compared to a polymer composition filled with an equivalent amount of talc particles not according to the present invention).
[0127] Additionally or alternatively, talc particles (e.g., microcrystalline talc particles) can be used to reduce the vulcanization time of the polymer composition (i.e., by adding talc particles (e.g., microcrystalline talc particles) to the polymer composition). The talc particles (e.g., microcrystalline talc particles) can reduce the vulcanization time of the polymer composition compared to a polymer composition that does not include talc particles (e.g., microcrystalline talc particles) according to the present invention (e.g., compared to a polymer composition filled with an equivalent amount of talc particles not according to the present invention). Additionally or alternatively, talc particles (e.g., microcrystalline talc particles) can be used to reduce the shear modulus of the polymer composition (i.e., by adding talc particles (e.g., microcrystalline talc particles) to the polymer composition). For example, talc particles (e.g., microcrystalline talc particles) can be used to reduce the storage shear modulus G' of the polymer composition (i.e., by adding talc particles (e.g., microcrystalline talc particles) to the polymer composition). The talc particles (e.g., microcrystalline talc particles) can reduce the storage shear modulus G' of the polymer composition compared to a polymer composition that does not include talc particles (e.g., microcrystalline talc particles) according to the present invention (e.g., compared to a polymer composition filled with an equivalent amount of talc particles not according to the present invention).
[0128] The polymer composition may include a filler other than talc particles (e.g., microcrystalline talc particles). For example, the polymer composition may include one or more minerals other than talc particles (e.g., microcrystalline talc particles). For example, the polymer composition may include synthetic silica or silicate (e.g., precipitated silica or silicate), natural silica or silicate, clay minerals (e.g., hydrous kandite clays such as kaolin, halloysite, or ball clay), carbon black, alkaline earth metal carbonates or sulfates, such as calcium carbonate, magnesium carbonate, dolomite, gypsum, anhydrous (calcined) kandite clays, such as metakaolin or fully calcined kaolin, mica, perlite, feldspar, nepheline syenite, wollastonite, diatomaceous earth, barite, and / or glass. In certain embodiments, the polymer composition includes precipitated silica, clay minerals such as kaolin, and / or carbon black in addition to talc particles (e.g., microcrystalline talc particles). In certain embodiments, the polymer composition may include talc other than the talc particles of the present invention (e.g., microcrystalline talc particles). The talc particles of the present invention (e.g., microcrystalline talc particles) may be used as a replacement for one or more other fillers. The use of the talc particles of the present invention (e.g., microcrystalline talc particles) may allow a reduction in the amount of one or more other fillers used without substantial loss of reinforcement, stiffness, strength, tear resistance or crosslink density, and / or without substantial increase in viscosity, shear modulus (e.g., storage shear modulus) or vulcanization time. The talc particles of the present invention (e.g., microcrystalline talc particles) may be used in particular to replace (e.g., part of) precipitated silica in a polymer composition that includes precipitated silica, without substantial loss of reinforcement, stiffness, strength, tear resistance or crosslink density, and / or without substantial increase in viscosity, shear modulus (e.g., storage shear modulus) or vulcanization time. That is, by including talc particles (e.g., microcrystalline talc particles) in a polymer composition, it may be possible to use less precipitated silica while achieving desired properties such as reinforcement, stiffness, strength, tear resistance, crosslink density, viscosity, shear modulus (e.g., storage shear modulus) or vulcanization time.
[0129] It will be understood that the present invention is not limited to the above-described embodiments, and various modifications and improvements can be made without departing from the concepts described herein. Except where mutually exclusive, any of the features may be employed separately or in combination with any other feature, and the present disclosure extends to and includes all combinations and subcombinations of one or more features described herein. For the avoidance of doubt, this application is directed to the subject matter described in the following numbered paragraphs:
[0130] 1.About 35m 2 / g or more, and (a) a Sedigraph d 50 and (b) a laser-induced d of about 5.0 μm or less. 50 Talc particles (e.g., microcrystalline talc particles) having one or both of the following: 2.(a) Sedigraph 50 is about 1.5 μm or less, for example, about 1.0 μm or less, or is about 0.1 μm to about 2.0 μm, for example, about 0.1 μm to about 1.5 μm, or about 0.1 μm to about 1.0 μm; (c) d by a laser 50 is about 4.0 μm or less, for example, about 3.0 μm or less, or is about 1.0 μm to about 5.0 μm, for example, about 1.0 μm to about 4.0 μm, or about 1.0 μm to about 3.0 μm; and / or (c) a BET specific surface area of about 40 m 2 / g or more.
[0131] 3. (a) Laser d of about 10.0 μm or less, for example, about 7.0 μm or less, or about 4.0 μm to about 10.0 μm, or about 4.0 μm to about 7.0 μm 95 (b) a laser d of about 7.0 μm or less, e.g., about 5.0 μm or less, or about 2.0 μm to about 7.0 μm, or about 2.0 μm to about 5.0 μm 75(c) a laser d of about 3.0 μm or less, e.g., about 2.0 μm or less, or about 0.5 μm to about 3.0 μm, or about 0.5 μm to about 2.0 μm 25 (d) a Sedigraph d of about 5.0 μm or less, e.g., about 3.0 μm or less, or about 0.5 μm to about 5.0 μm, or about 0.5 μm to about 3.0 μm; 95 (e) a Sedigraph d of about 3.0 μm or less, e.g., about 2.0 μm or less, or about 0.1 μm to about 3.0 μm, or about 0.1 μm to about 2.0 μm; 75 (f) a Sedigraph d of about 1.0 μm or less, e.g., about 0.5 μm or less, or about 0.1 μm to about 1.0 μm, or about 0.1 μm to about 0.5 μm; 25 and / or (g) about 7.5 g / m 2 For example, about 0.01 g / m or less 2 ~about 7.5g / m 2 , or about 0.01 g / m 2 ~about 4.0g / m 2 3. The talc particles (e.g. microcrystalline talc particles) of paragraph 1 or paragraph 2 having a crystallinity index, CI, of:
[0132] 4. A method for preparing talc particles (e.g., microcrystalline talc particles) according to any of paragraphs 1-3, comprising: (a) dry-milling a talc feed material (e.g., a microcrystalline talc feed material) in an agitator bead mill to produce a ground talc material (e.g., a ground microcrystalline talc material); and (b) classifying the ground talc material (e.g., the ground microcrystalline talc material) to remove a coarse fraction.
[0133] 5. The method of paragraph 4, comprising dry-grinding the talc feed material (e.g., microcrystalline talc feed material) in an agitator bead mill using grinding media comprising grinding beads having a diameter of about 2 mm to about 10 mm, e.g., about 4 mm to about 6 mm, wherein the grinding beads may be made of ceramic, e.g., alumina or zirconia; plastic; or metal, e.g., steel. 6. The method of paragraph 4 or paragraph 5, comprising returning the coarse fraction to the agitator bead mill for further dry grinding.
[0134] 7. The talc feed material (e.g., microcrystalline talc feed material) has a diameter of about 5.0 μm to about 20 mm, e.g., about 5.0 μm to about 10 mm, or about 5.0 μm to about 1 mm, or about 5.0 μm to about 20.0 μm, or about 5.0 μm to about 10.0 μm, of 50 μm or less. 50 The values are from Sedigraph and for d > 50 μm 50 The value of d is determined by screening. 50 (b) about 5.0 μm to about 20 mm, e.g., about 5.0 μm to about 10 mm, or about 5.0 μm to about 1 mm, or about 5.0 μm to about 40.0 μm, or about 5.0 μm to about 20.0 μm, d of 1 mm or less 50 The values of d by laser and d > 1 mm 50 The value of d is determined by screening. 50 (c) a Minolta Y whiteness of about 80 or greater, e.g., about 85 or greater; (d) a CIELAB L whiteness of about 85 or greater, e.g., about 90 or greater. * (e) a CIELAB a of about 1.0 or less, e.g., about 0.5 or less; * (f) a CIELAB b of about 1.0 to about 4.0, for example, about 2.0 to about 3.0 * ;(g) approx. 30m 2 / g or less, for example, about 20m 2 / g or less, or about 10m 2 (h) a talc content of about 60% or more, e.g., about 80% or more, of talc, and an optional chlorite content of about 40% or less, e.g., about 20% or less; and / or (i) a BET specific surface area of about 7.5 g / m 2 For example, about 0.01 g / m or less 2 ~about 7.5g / m 2 , or about 0.01 g / m 2 ~about 4.0g / m 2 7. The method of any of paragraphs 4 to 6, having a crystallinity index, CI, of
[0135] 8. A polymer composition comprising talc particles (e.g., microcrystalline talc particles) according to any of paragraphs 1 to 3. 9. The polymer composition of paragraph 8, (a) comprising at least about 5 phr, e.g., at least about 10 phr, or at least about 50 phr, of talc particles (e.g., microcrystalline talc particles); (b) further comprising a mineral other than talc particles (e.g., microcrystalline talc particles), e.g., precipitated silica, or a clay mineral such as kaolin, or carbon black; and / or (c) comprising an elastomer, such as synthetic or natural rubber, e.g., styrene-butadiene rubber.
[0136] 10. A method of making a polymer composition according to paragraph 8 or paragraph 9, comprising combining a polymer or a polymer precursor with talc particles (e.g., microcrystalline talc particles) according to any of paragraphs 1-3. 11. Compared to a polymer composition containing an equivalent amount of talc particles not described in any of paragraphs 1-3, (a) the modulus of elasticity at 50% elongation, M 50 (b) the modulus at 100% elongation of the polymer composition, M 100 (c) the modulus of elasticity at 300% elongation of the polymer composition, M 300 (d) to increase the abrasion resistance of the polymer composition; (e) to increase the reinforcement index M of the polymer composition. 300 / M 100 (f) to increase the tensile strength of the polymer composition; (g) to increase the tear resistance of the polymer composition; (h) to increase the crosslink density of the polymer composition; (i) to reduce the vulcanization time of the polymer composition; (j) to reduce the Mooney viscosity of the polymer composition; and / or (k) to reduce the shear modulus of the polymer composition.
[0137] 12. Compared to a reference polymer composition comprising a reference amount of talc particles not described in any of paragraphs 1-3, (a) the modulus of elasticity at 50% elongation, M 50 (b) the modulus at 100% elongation of the polymer composition, M 100 (c) the modulus of elasticity at 300% elongation of the polymer composition, M 300 (d) increasing the abrasion resistance of the polymer composition; (e) increasing the reinforcement index M of the polymer composition. 300 / M 100 (f) increasing the tensile strength of a polymer composition; (g) increasing the tear resistance of a polymer composition; (h) increasing the crosslink density of a polymer composition; (i) decreasing the vulcanization time of a polymer composition; (j) decreasing the Mooney viscosity of a polymer composition; and / or (k) decreasing the shear modulus of a polymer composition, the method comprising the step of adding talc particles (e.g., microcrystalline talc particles) described in any of paragraphs 1 to 3 to a polymer composition in a reference amount.
[0138] 13. The use according to paragraph 11 or the method according to paragraph 12, wherein the polymer composition is an elastomeric polymer composition comprising an elastomer such as a synthetic or natural rubber, for example styrene-butadiene rubber. 14. The use or method of any of paragraphs 11 to 13, wherein (a) the polymer composition comprises about 5 phr or more, e.g., about 10 phr or more, or about 50 phr or more of talc particles (e.g., microcrystalline talc particles); and / or (b) the polymer composition further comprises a mineral other than talc particles (e.g., microcrystalline talc particles), e.g., precipitated silica, a clay mineral such as diatomaceous earth and / or kaolin, or carbon black. EXAMPLES
[0139] Example 1 Three different microcrystalline talc particles (Examples 1, 2, and 3) were prepared by grinding and classifying a microcrystalline talc feedstock. The microcrystalline talc feedstock is (by Sedigraph)50 is 7.8μm, and (laser) d 50 The BET specific surface area is 9.2m 2 / g and containing 95% talc (i.e. magnesium silicate) and 4% chlorite (by thermogravimetric analysis), obtained from the Three Springs Talc mine in Australia. Figure 7 shows a plot of water sorption as a function of relative humidity for four different talc materials A through D. Talc material D corresponds to the reference microcrystalline talc.
[0140] The microcrystalline talc feed material was ground using 52 kg of 4-6 mm diameter steel (Example 1) or alumina (Examples 2 and 3) grinding beads in a NETZSCH Ecutec PAMIR 30 agitator bead mill (available from NETZSCH-Feinmahltechnik GmbH, Germany). The NETZSCH Ecutec PAMIR 30 agitator bead mill has an installed power of 22 kW, an absorbed power of 6-8 kW (when used with ceramic beads) and an operating speed of 400 rpm. The ground microcrystalline talc was classified into coarse and fine fractions using a NETZSCH Ecutec BORA 50 turbo air classifier (available from NETZSCH-Feinmahltechnik GmbH, Germany). The NETZSCH Ecutec BORA 50 turbo air classifier has a maximum air flow rate of 1800 m 3 / hour, maximum rotor speed 8700rpm, installed power 10kW, maximum supply volume 1800kg / hour and main fan installed power 30kW. The agitator bead mill and air classifier were arranged in the grinding / classifying circuit as shown in FIG. 1 such that the coarse fraction was fed back to the agitator bead mill for further grinding. The operating conditions of the NETZSCH Ecutec PAMIR 30 agitator bead mill and the NETZSCH Ecutec BORA 50 turbo air classifier are shown in Table 1.
[0141] [Table 1]
[0142] Particle size distribution (by both Sedigraph and Malvern laser scattering), BET specific surface area, Minolta Y brightness, and CIElab L * and b * The values were analyzed for each of the examples. The methods for obtaining the particle size distribution and BET specific surface area are shown in more detail in Examples 5, 6 and 7. The results are shown in Table 2 in comparison with a commercial talc particle (Reference 1). For Examples 1, 2 and 3, Table 2 also shows the percentage increase in BET specific surface area (ΔBET) compared with Reference 1.
[0143] [Table 2]
[0144] The crystallinity index, CI, defined as the ratio of the number of TOT layers per coherent scattering domain, N(TOT), to the BET specific surface area, was determined for Examples 1 and 2 by the method described above. The results are shown in Figure 2. Figure 2 also shows the measured CI values for reference talc particles T.1, T.2, T.3 and T.4. Reference talc particles T.1 and T.2 are commercially available macrocrystalline talcs. Reference talc particles T.3 and T.4 are commercially available microcrystalline talcs.
[0145] Six styrene-butadiene white rubber (SBR) compounds (F.1 to F.6) having the compositions shown in Table 3 (measured in parts per hundred rubber (phr)) were prepared on a laboratory two-roll mill (available from Gibitre Instruments srl) with a friction ratio of 18:24 by the process shown in Table 4.
[0146] [Table 3]
[0147] [Table 4]
[0148] Table 5 shows the minimum torque reading (ML), maximum torque reading (MH), crosslink density (ΔC), ts2 scorch time, cure time to 50% cure (t50), cure time to 90% cure (t90) and Mooney viscosity at 100° C. (MV) for each of Formulations F.1-F.6. ML, MH, ΔC, ts2, t50 and t90 were measured using a moving die rheometer according to ISO-6502. Mooney viscosity was measured using a Mooney viscometer according to ISO 289-1.
[0149] [Table 5]
[0150] Density, modulus of elasticity at 50% elongation (M 50 ), modulus of elasticity at 100% elongation (M 100 ), modulus of elasticity at 300% elongation (M 300 ), reinforcement index M 300 / M 100 Physical properties including tensile strength (TS), elongation at break (Elong.), tear resistance (TR), Shore A hardness (H) and compression set (CS) were measured for each of formulations F.1-F.6. Each property was measured from 10 different samples and an average was obtained. The results are shown in Table 6 along with the corresponding standard deviation (σ) below each measurement. Density was measured according to ISO 2781. Tensile properties were measured according to ISO 37. Tear resistance was measured according to ISO 34. Shore A hardness was measured according to ISO 7619-1. Compression set was measured according to ISO 815. Abrasion resistance was measured according to ISO 4649.
[0151] [Table 6]
[0152] Example 2 Six styrene-butadiene white rubber (SBR) compounds (F.7-F.12) having the compositions shown in Table 7 (measured in parts per hundred rubber (phr)) were prepared using the process described in Example 1.
[0153] [Table 7]
[0154] Table 8 shows the minimum torque measurement (ML), maximum torque measurement (MH), crosslink density (ΔC), ts1 scorch time, ts2 scorch time, cure time to 50% cure (t50), cure time to 90% cure (t90) and Mooney viscosity at 100° C. (MV) for each of the formulations, measured as shown in Example 1.
[0155] [Table 8] The tensile strength, elongation at break, tear resistance and compression set were measured for each of the formulations by the methods set forth in Example 1. The results are shown in Figures 3, 4, 5 and 6.
[0156] Next, the density and the modulus of elasticity at 50% elongation (M 50 ), modulus of elasticity at 100% elongation (M 100 ), modulus of elasticity at 300% elongation (M 300 ), reinforcement index M 300 / M 100Physical properties including tensile strength (TS), elongation at break (Elong.), tear resistance (TR), Shore A hardness (H), compression set (CS), wear volume and abrasion resistance (AR) were measured for each of formulations F.7-F.12. Each property was measured from 10 different samples and an average was obtained. The results are shown in Table 9 along with the corresponding standard deviation (σ) below each measurement. Density was measured according to ISO 2781. Tensile properties were measured according to ISO 37. Tear resistance was measured according to ISO 34. Shore A hardness was measured according to ISO 7619-1. Compression set was measured according to ISO 815. Abrasion resistance was measured according to ISO 4649.
[0157] [Table 9]
[0158] Elastic modulus at 50% elongation (M 50 ), modulus of elasticity at 100% elongation (M 100 ), modulus of elasticity at 300% elongation (M 300 The properties of the composition F.7 to F.12 were also measured after aging for 168 hours at 70°C. Each property was measured from 10 different samples and the average was taken. The results are shown in Table 10 with the corresponding standard deviation (σ) under each measurement and the percentage change (Δ) compared to the corresponding measurement before aging.
[0159] [Table 10]
[0160] Example 3 Eight styrene-butadiene white rubber (SBR) compounds (F.13-F.20) having the compositions shown in Table 11 (measured in parts per hundred rubber (phr)) were prepared using the process described in Example 1.
[0161] [Table 11]
[0162] Table 12 shows the minimum torque measurement (ML), maximum torque measurement (MH), crosslink density (ΔC), ts1 scorch time, ts2 scorch time, cure time to 50% cure (t50), and cure time to 90% cure (t90) for each of the formulations, measured as described in Example 1. Table 12 also includes measurements of storage modulus G' (of complex dynamic modulus G=G'+iG'') at 150% elongation, obtained using a moving die rheometer according to ISO 13145. G' is comparable to Mooney viscosity.
[0163] [Table 12]
[0164] Next, the density and the modulus of elasticity at 50% elongation (M 50 ), modulus of elasticity at 100% elongation (M 100 ), modulus of elasticity at 300% elongation (M 300 ), reinforcement index M 300 / M 100 Physical properties including tensile strength (TS), elongation at break (Elong.), tear resistance (TR) and Shore A hardness (H) were measured for formulations F.13-F.17 and F.20. Each property was measured from 10 different samples and an average was taken. The results are shown in Table 13 with the corresponding standard deviation (σ) under each measurement. Density was measured according to ISO 2781. Tensile properties were measured according to ISO 37. Tear resistance was measured according to ISO 34. Shore A hardness was measured according to ISO 7619-1.
[0165] [Table 13] Compression set (CS), wear volume and abrasion resistance (AR) were also measured for formulations F.13 to F.20. Each property was measured from 10 different samples and the average was obtained. The results are shown in Table 14 with the corresponding standard deviation (σ) under each measurement. Compression set was measured according to ISO 815. Abrasion resistance was measured according to ISO 4649.
[0166] [Table 14]
[0167] Elastic modulus at 50% elongation (M 50 ), modulus of elasticity at 100% elongation (M 100 ), modulus of elasticity at 300% elongation (M 300 The properties of the composition F.13 to F.20 were also measured after aging for 168 hours at 70°C. Each property was measured from 10 different samples and the average was obtained. The results are shown in Table 15 with the corresponding standard deviation (σ) under each measurement and the percentage change (Δ) compared to the corresponding measurement before aging.
[0168] [Table 15]
[0169] Example 4 Nine styrene-butadiene / butadiene rubber (SBR / BR) compounds (F.21-F.29) having the compositions (measured in parts per hundred rubber (phr)) shown in Tables 16 and 17 were prepared in a Banbury® mixer (for stages 1 and 2) and a two-roll mill (for stage 3) by the process shown in Tables 18 and 19. Oil, polyethylene glycol, stearic acid, sulfur, zinc oxide and accelerators were also included in the compositions as shown in Tables 18 and 19.
[0170] [Table 16]
[0171] [Table 17]
[0172] [Table 18]
[0173] [Table 19]
[0174] Tables 20 and 21 show the minimum torque reading (ML), maximum torque reading (MH), crosslink density (ΔC), ts1 scorch time, ts2 scorch time, cure time to 50% cure (t50), cure time to 90% cure (t90), Mooney viscosity at 100°C (MV), shear storage modulus (G'), shear loss modulus (G'') and shear loss tangent (tan δ) for each of formulations F.21-F.29. ML, MH, ΔC, ts1, ts2, t50 and t90 were measured using a moving die rheometer according to ISO-6502. Mooney viscosity was measured using a Mooney viscometer according to ISO289-1. Tables 20 and 21 also show the increase or decrease in ΔC, ts2 and t90 with inclusion of silane treatment compared to the corresponding results obtained without the use of silane.
[0175] [Table 20]
[0176] [Table 21]
[0177] When rubber is filled with silica only, the use of silane reduces ΔC. In contrast, replacing 10% and 20% of the silica with talc increases ΔC compared to rubber filled with silane-treated silica.
[0178] The use of silanes tends to increase the t90 cure time of rubbers filled with silica, talc or kaolin. Partial replacement of silica with talc reduces the t90 cure time. The use of silanes results in a reduction in Mooney viscosity, especially for rubbers filled with silica. Partial replacement of silica with talc reduces the Mooney viscosity. Partial replacement of silica with talc reduces the shear tan δ. Use of silane reduces G'. Partial replacement of silica with talc gives G' values slightly higher than those obtained with rubbers filled with silica and silane.
[0179] Density, modulus of elasticity at 50% elongation (M 50 ), modulus of elasticity at 100% elongation (M 100 ), modulus of elasticity at 300% elongation (M 300 Physical properties including density, tensile strength (TS), elongation at break (Elong.), tear resistance by die C (TR die C), tear resistance by trouser method (TR trouser), Shore A hardness (H), compression set (CS), abrasion (A) and abrasion resistance (AR) were measured for each of formulations F.21-F.29. Each property was measured from 10 different samples and an average was obtained. The results are shown in Tables 22 and 23 along with the corresponding standard deviation (σ) below each measurement. Density was measured according to ISO 2781. Tensile properties were measured according to ISO 37. Tear resistance was measured according to ISO 34. Shore A hardness was measured according to ISO 7619-1. Compression set was measured according to ISO 815. Abrasion resistance was measured according to ISO 4649. Tables 22 and 23 also show the increase or decrease in various properties with the inclusion of silane treatment compared to the corresponding results obtained without the use of silane.
[0180] [Table 22]
[0181] [Table 23]
[0182] All compounds exhibit hardness values in a similar range. The presence of talc improves the tensile strength and elongation at break. The tear resistance achieved by combining silica with silane is effectively maintained when the silica is partially replaced with talc. The use of silanes increases abrasion resistance. Partial replacement of silica with talc increases abrasion resistance. The tensile strength achieved using talc filled rubber is higher than that of kaolin filled rubber.
[0183] Elastic modulus at 50% elongation (M 50 ), modulus of elasticity at 100% elongation (M 100 ), modulus of elasticity at 300% elongation (M 300 ), tensile strength (TS), elongation at break (Elong.), tear resistance by die C (TR die C), tear resistance by trouser method (TR trouser) and Shore A hardness (H) were also measured for each of the formulations F.21 to F.29 after aging for 168 hours at 70°C. Each property was measured from 10 different samples and an average was obtained. The results are shown in Tables 24 and 25 with the corresponding standard deviation (σ) under each measurement and the percentage change compared to the corresponding measurement before aging (i.e. "initial") and compared to the corresponding measurement obtained without the use of silane.
[0184] [Table 24]
[0185] [Table 25]
[0186] Example 5 How to determine particle size distribution (by Sedigraph) Particle size distribution (PSD) was determined using a Sedigraph III from Micromeritics Instruments.
[0187] A dispersion solution was prepared by weighing (using an analytical balance) 250 mg of Calgon (sodium metaphosphate) into a beaker containing 1 liter of demineralized water and dissolving it completely (by mechanical stirring). This step took 45-60 minutes. Then 1 ml of Triton X (polyethylene glycol octylphenyl ether) was added to the solution with stirring for at least 10 minutes. Calgon and Triton X are wetting and dispersing agents.
[0188] A sample of talc particles was prepared for sedimentation analysis by combining 4.8 g of the talc particle sample with 80 ml of the dispersion solution. First, the talc particles were combined with a few drops of the 80 ml dispersion solution in a beaker, and the mixture was mixed using a manual stirrer until a paste consistency was achieved. The remainder of the 80 ml dispersion solution was then added to the beaker. The beaker was placed in an ultrasonic bath for 30 seconds to remove any air bubbles.
[0189] Sedimentation analysis was then performed on the dispersed samples using a Sedigraph III with the following settings: - Dispersion solution viscosity: 0.7523mPa.sec - Dispersion solution density: 0.9948g / cm 3 - Sample density: 2.78g / cm for talc powder 3 - Maximum diameter: 52μm - Minimum diameter: 0.4μm - Mode: Fast - Air bubble detection: coarse Results were considered valid if the following criteria were met: - The Reynolds number was less than 0.3; - Baseline (dispersion solution only) was between 125-130 kcounts / sec; - Full scale (sample suspension) was between 95 and 105 kcounts / sec; and - The difference between base / full scale was less than 35kcounts / sec.
[0190] Example 6 How to determine particle size distribution (by laser diffraction) Particle size distribution (PSD) was determined using a Mastersizer 2000 from Malvern instruments. Talc particle samples were prepared for laser diffraction analysis. The required amount of talc particles was weighed into a 50 ml beaker. 50 For talc particles having a d (by Sedigraph) of less than 10 μm, an amount of talc particles between 1 g and 2 g was used. 50 For talc particles having a pH of 10, an amount of between 0.2 g and 0.5 g of talc particles was used.
[0191] Coarse talc particles (10 μm or more, Sedigraph d 50 For the samples with 0.1% ethanol, the samples were combined with absolute ethanol (99.5%) wetting agent. In particular, the powder samples were well distributed at the bottom of the beaker. A few drops of ethanol were added to the powder and mixed using a manual stirrer until a paste consistency was achieved. Between 2ml and 2.5ml of ethanol was added to the beaker using a 3ml disposable pipette and the suspension was mixed with a manual stirrer. The beaker was placed in an ultrasonic bath for 30 seconds to remove any air bubbles.
[0192] Laser diffraction analysis was then performed on the samples using a Mastersizer 2000 with the following settings: - Sampler: Hydro 2000G - Measurement theory: Mie 1.589-0.01 (i.e., talc refractive index) - Water refractive index: 1.33 - Measurement range: 0.02~2000μm - Result calculation model: Standard analysis - Number of snaps: Measurement duration: 8 seconds Number of snaps per measurement: 8000 snaps Background noise time: 8000 snaps Background Noise Snap: 8 seconds - Obscuration limit: Low: 5% High: 20% - Background noise alarm (value of background noise for detector number 1): less than 150 units - Sampler measurement parameters: Pump: 1800 rpm Mixing: 700 rpm Ultrasonic: 100%
[0193] The analysis was carried out as follows: Ensured that the lower absorbance limit was set to 5% and the upper absorbance limit was set to 20%. Set the stirrer speed to 700 rpm, the pump to 1800 rpm, and the ultrasound to 100%. Checked the laser intensity. If the laser intensity is less than 77.5%, ensured that the measurement cell is clean; there are no air bubbles; and that there is no condensation on the measurement cell window. The background noise was measured and the laser (red and blue) intensities were measured. After adjusting the laser position, the laser intensity and the background noise intensity (which should decrease continuously from detector number 1 to detector number 51) were checked. Using a disposable pipette, a 2 ml sample was taken from the beaker containing the talc particle suspension and added drop by drop to the measurement cell until the required absorbance was obtained: d above 10 μm (by Sedigraph) 50 For products with absorbance between 15 and 20%, measurements were used; for products with absorbance between 15 and 20%, measurements with absorbance between 15 and 20% were used; for products ... 50For products with an absorbance between 5 and 12% a measurement with an absorbance between 5 and 12% was used. The suspension was homogenized in the cell for approximately 60 seconds.
[0194] The software directly tracks the PSD curve, expressed as a percentage of fines. The validity of the curve is controlled by the value of the weighted residual, the signal-to-noise ratio and the distribution of the light intensity of the background noise as a function of the detector. The obtained results are valid as long as the weighted residual is less than 1.5% and there are no anomalies in the curve. The intensity of the measured signal and the background noise of the detectors can be examined using the data report tab. The intensity of the background noise should steadily decrease from detector number 1 to detector number 51. The intensity of the measured signal should be significantly greater than the intensity of the background noise. The intensity of the background noise depends on the cleanliness of the cell. The intensity of the signal depends mainly on the sample concentration (i.e., absorbance). It has been found that if the pressure is too high or the water temperature is too low, some problems may occur in the measuring cell, such as air bubbles or condensation. To avoid such problems, it is recommended to install a filtration system to improve the water cleanliness and reduce the pressure, and to install a mixer tap to adjust the water temperature to between 20-25°C before it is fed into the tank. It is also recommended not to turn off the optical bench (laser).
[0195] Example 7 How to Determine BET Specific Surface Area The BET specific surface area was determined using a method based on standard NF X 11-621 entitled "Determination of the mass area (specific surface) of powders by gas adsorption - BET method - Volumetric measurement by nitrogen adsorption at low temperature" (Determination of the mass area (specific surface) of powders by gas adsorption - BET method - Volumetric measurement by nitrogen adsorption at low temperature). The method used a Micromeritics measurement instrument (available from Micromeritics Instrument Corp., USA) equipped with a vacuum pump, a VacPrep 061 degassing section, a Tristar 3000S measurement section and sample holder, a Mettler AG204 scale with an accuracy of 0.1 mg, a Dewar flask, nitrogen adsorption gas and helium carrier gas.
[0196] The sample was weighed (to an accuracy of 0.1 mg) near the empty sample holder and its mass M0 was recorded in g. The pre-homogenized powder sample was then introduced into the sample holder using a funnel. Sufficient space (dead volume) was left between the sample and the top of the sample holder to allow free circulation of gas. The sample holder was placed in one of the degassing stations and degassed at 250 °C under a primary vacuum of 10 Pa for about 20 min. After degassing, a sufficient amount of nitrogen was added to the sample holder to avoid introducing air during the transfer of the sample holder from the degassing station to the measurement station.
[0197] The sample holder was then attached to the measurement station and a Dewar flask containing liquid nitrogen was placed around the sample holder. The device control software was used to start the BET measurement. The device then automatically performed the following operations: - Vacuum removal of the nitrogen introduced for the transfer of the sample holder; - Leak test; - Addition of helium carrier gas; - Determination of dead volume at ambient temperature; - Determination of cold dead volume using liquid nitrogen; - Helium vacuum removal; - Leak test; - Addition of nitrogen at 950mmHg and measurement of saturation pressure; and - Obtaining analytical values.
[0198] The data acquisition and processing software of the instrument plotted a BET line converted from the five measured adsorption points. The Dewar flask and then the sample holder were removed. The apparatus was returned to ambient temperature, and then the sample was weighed again (to an accuracy of 0.1 mg) adjacent to the sample holder and the mass was recorded as M2 (g). The mass of the test portion of the sample, M, was calculated according to the following (g): M=M2-M0
[0199] The value M was then introduced into a software calculation program to calculate the BET specific surface area (m 2 / g) was calculated automatically.
Claims
1. Approximately 35m 2 / g or more BET specific surface area, and (a) d by Sedigraph of about 2.0 μm or less 50 and (b) Laser-induced d of about 5.0 μm or less 50 Microcrystalline talc particles having one or both of the following:
2. (a) Sedigraph 50 is about 1.5 μm or less, e.g., about 1.0 μm or less, or is from about 0.1 μm to about 2.0 μm, e.g., from about 0.1 μm to about 1.5 μm, or from about 0.1 μm to about 1.0 μm; (b) Laser 50 is about 4.0 μm or less, e.g., about 3.0 μm or less, or is from about 1.0 μm to about 5.0 μm, e.g., from about 1.0 μm to about 4.0 μm, or from about 1.0 μm to about 3.0 μm; and / or (c) BET specific surface area is about 40 m 2 / g or more; 2. The microcrystalline talc particles of claim 1.
3. (a) a laser d of about 10.0 μm or less, e.g., about 7.0 μm or less, or from about 4.0 μm to about 10.0 μm, or from about 4.0 μm to about 7.0 μm; 95 ; (b) a laser d of about 7.0 μm or less, e.g., about 5.0 μm or less, or from about 2.0 μm to about 7.0 μm, or from about 2.0 μm to about 5.0 μm 75 ; (c) a laser d of about 3.0 μm or less, e.g., about 2.0 μm or less, or about 0.5 μm to about 3.0 μm, or about 0.5 μm to about 2.0 μm 25 ; (d) a Sedigraph d of about 5.0 μm or less, e.g., about 3.0 μm or less, or about 0.5 μm to about 5.0 μm, or about 0.5 μm to about 3.0 μm 95 ; (e) a d by Sedigraph of about 3.0 μm or less, e.g., about 2.0 μm or less, or about 0.1 μm to about 3.0 μm, or about 0.1 μm to about 2.0 μm 75 ; (f) a d by Sedigraph of about 1.0 μm or less, e.g., about 0.5 μm or less, or about 0.1 μm to about 1.0 μm, or about 0.1 μm to about 0.5 μm 25 and / or (g) Approximately 7.5g / m 2 For example, about 0.01 g / m or less 2 ~Approx. 7.5g / m 2 , or about 0.01 g / m 2 ~Approx. 4.0g / m 2 of the crystallinity index, CI 2. The microcrystalline talc particles of claim 1, having a molecular weight of about 1.0 or more.
4. 2. A method for preparing the microcrystalline talc particles of claim 1, comprising the steps of: (a) dry milling a microcrystalline talc feed material in an agitator bead mill to produce a milled microcrystalline talc material; (b) classifying the ground microcrystalline talc material to remove the coarse fraction; The method includes:
5. 5. The method of claim 4, comprising dry grinding the microcrystalline talc feed material in an agitator bead mill using grinding media comprising grinding beads having a diameter of about 2 mm to about 10 mm, e.g., about 4 mm to about 6 mm, the grinding beads may be made of ceramic, e.g., alumina or zirconia; plastic; or metal, e.g., steel.
6. 5. The method of claim 4 including the step of returning the coarse fraction to the agitator bead mill for further dry grinding.
7. 1. The microcrystalline talc feed material comprising: (a) a d of 50 μm or less, for example, about 5.0 μm to about 20 mm, for example, about 5.0 μm to about 10 mm, or about 5.0 μm to about 1 mm, or about 5.0 μm to about 20.0 μm, or about 5.0 μm to about 10.0 μm 50 The values of d are calculated by Sedigraph and d > 50 μm. 50 The value of d is determined by screening. 50 ; (b) about 5.0 μm to about 20 mm, e.g., about 5.0 μm to about 10 mm, or about 5.0 μm to about 1 mm, or about 5.0 μm to about 40.0 μm, or about 5.0 μm to about 20.0 μm, with a d of 1 mm or less 50 The values of d and d > 1 mm were measured by laser. 50 The value of d is determined by screening. 50 ; (c) a Minolta Y brightness of about 80 or greater, e.g., about 85 or greater; (d) a CIELAB L of about 85 or more, for example, about 90 or more * ; (e) a CIELAB a of about 1.0 or less, for example, about 0.5 or less. * ; (f) a CIELAB b of about 1.0 to about 4.0, for example, about 2.0 to about 3.
0. * ; (g) Approximately 30m 2 / g or less, for example, about 20m 2 / g or less, or about 10m 2 / g or less BET specific surface area; (h) a talc content of about 60% or more, e.g., about 80% or more, and an optional chlorite content of about 40% or less, e.g., about 20% or less; and / or (i) Approximately 7.5g / m 2 For example, about 0.01 g / m or less 2 ~Approx. 7.5g / m 2 , or about 0.01 g / m 2 ~Approx. 4.0g / m 2 of the crystallinity index, CI The method according to any one of claims 4 to 6, comprising:
8. A polymer composition comprising microcrystalline talc particles according to any one of claims 1 to 3.
9. (a) about 5 phr or more, e.g., about 10 phr or more, or about 50 phr or more, of microcrystalline talc particles; (b) further comprising minerals other than microcrystalline talc particles, for example precipitated silica, or clay minerals such as kaolin, or carbon black; and / or (c) synthetic or natural rubber, including elastomers such as styrene-butadiene rubber; The polymer composition of claim 8.
10. A method of making the polymer composition of claim 8, comprising combining a polymer or a polymer precursor with the microcrystalline talc particles of any of claims 1 to 3.
11. compared to a polymer composition containing the same amount of talc particles not described in any of claims 1 to 3 (a) The elastic modulus at 50% elongation of the polymer composition, M 50 To increase; (b) The elastic modulus at 100% elongation of the polymer composition, M 100 To increase; (c) The elastic modulus at 300% elongation of the polymer composition, M 300 To increase; (d) to increase the abrasion resistance of the polymer composition; (e) the reinforcement index M of the polymer composition 300 / M 100 To increase; (f) to increase the tensile strength of the polymer composition; (g) to increase the tear resistance of the polymer composition; (h) to increase the crosslink density of the polymer composition; (i) To reduce the vulcanization time of the polymer composition; (j) to reduce the Mooney viscosity of the polymer composition; and / or (k) reducing the shear modulus of the polymer composition; Use of the microcrystalline talc particles according to any one of claims 1 to 3 in a polymer composition.
12. The use according to claim 11, wherein the polymer composition is an elastomeric polymer composition comprising an elastomer such as a synthetic or natural rubber, for example styrene-butadiene rubber. (a) the polymer composition comprises about 5 phr or more, e.g., about 10 phr or more, or about 50 phr or more, of microcrystalline talc particles; and / or (b) the polymer composition further comprises minerals other than microcrystalline talc particles, for example, precipitated silica, diatomaceous earth and / or clay minerals such as kaolin or carbon black; 12. The use according to claim 11.
14. compared to a reference polymer composition comprising a reference amount of talc particles not described in any of claims 1 to 3, (a) The elastic modulus at 50% elongation of the polymer composition, M 50 Increase (b) The elastic modulus at 100% elongation of the polymer composition, M 100 Increase (c) The elastic modulus at 300% elongation of the polymer composition, M 300 Increase (d) increasing the abrasion resistance of the polymer composition; (e) the reinforcement index M of the polymer composition 300 / M 100 Increase (f) increasing the tensile strength of the polymer composition; (g) increasing the tear resistance of the polymer composition; (h) increasing the crosslink density of the polymer composition; (i) reducing the vulcanization time of the polymer composition; (j) reducing the Mooney viscosity of the polymer composition; and / or (k) decreasing the shear modulus of the polymer composition 1. A method comprising: A method comprising the step of adding the microcrystalline talc particles according to any one of claims 1 to 3 in a reference amount to a polymer composition.
15. The method of claim 14, wherein the polymer composition is an elastomeric polymer composition comprising an elastomer such as a synthetic or natural rubber, for example, styrene-butadiene rubber.
16. (a) the polymer composition comprises about 5 phr or more, e.g., about 10 phr or more, or about 50 phr or more, of microcrystalline talc particles; and / or (b) the polymer composition further comprises minerals other than microcrystalline talc particles, for example, precipitated silica, clay minerals such as diatomaceous earth and / or kaolin, or carbon black; The method of claim 14.